Novel materials with extremely long-lasting lithium intercalation and methods of making same
By depositing silicon in the pore volume of the porous carbon material to form silicon-impregnated carbon material, the problem of expansion and contraction of the anode material of the lithium-ion battery during circulation is solved, and a longer-lasting lithium embedding and higher battery performance is achieved.
Patent Information
- Application Number
- CN202411549259.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-03-22
- Filing Date
- 2016-08-26
- Publication Date
- 2025-02-11
AI Technical Summary
The anode materials of existing lithium-ion batteries are prone to expansion and contraction during the cycle, resulting in instability of the solid electrolyte mesophase (SEI), which in turn affects the capacity attenuation and power performance of the battery.
Using a porous carbon material as a bracket, silicon impregnated carbon material is formed by depositing silicon in its pore volume. The material further enhances the durability of its lithium embedding by carbonizing polymers and high temperature treatment in the presence of silicon-containing gas.
It significantly improves the storage and application properties of lithium, extends the cycle life of the battery, improves power performance, and reduces capacity attenuation.
Smart Images

Figure CN119419246A_ABST
Abstract
Description
[0001] Government Interest Statement
[0002] This invention was made in part with government support under Grant No. DE-EE0007312 from the Office of Energy Efficiency and Renewable Energy of the Department of Energy. The U.S. Government has certain rights in this invention. background Technical Field
[0004] The present invention generally relates to novel materials that exhibit extremely durable lithium intercalation, methods for making them, and methods for using them, such as for energy storage applications. The novel materials include porous supports, such as carbon that exhibits pore volume (including micropores, mesopores, and / or macropores), wherein the volume is impregnated with silicon, and in some embodiments, the impregnated silicon is nano-sized and / or nano-featured. The silicon-impregnated porous support can also be coated to reduce any remaining surface area, such as with carbon or a conductive polymer. Such silicon-impregnated carbon materials and carbon-coated or conductive polymer-coated silicon-impregnated carbon materials exhibit significant persistence with respect to their lithium intercalation. Therefore, the disclosed materials have utility alone or in combination with other materials, for example, in combination with carbon particles, binders, or other components, to provide a composition of matter for energy storage applications. The energy storage application includes using the materials herein as electrode materials, particularly anode materials, for lithium ion batteries and related energy storage devices using lithium or lithium ions, such as lithium air batteries. In certain embodiments, the materials disclosed herein have utility as anode materials for energy storage devices, such as lithium ion batteries and related energy storage devices that employ lithium or lithium ions. Thus, the present invention also relates to compositions and devices containing such materials and methods involving such materials.
[0005] Description of Related Technology
[0006] Lithium-based electrical storage devices have the potential to replace devices currently used in many applications. For example, due to the formation of irreversible, stable sulfates during discharge, current lead-acid automotive batteries are not competent for the next generation of fully electrified vehicles and hybrid electric vehicles. Due to the capacity and other considerations of lead-based systems, lithium-ion batteries are a viable alternative to the lead-based systems currently used. Carbon is one of the main materials used in lithium secondary batteries and hybrid lithium-ion capacitors (LICs). Carbon anodes usually store lithium between layered graphene sheets through a mechanism known as intercalation. Conventional lithium-ion batteries consist of a graphite carbon anode and a metal oxide cathode; however, such graphite anodes usually suffer from low power performance and limited capacity.
[0007] Silicon, tin and other lithium alloying electrochemical modifiers have also been proposed based on their ability to store very large amounts of lithium per unit weight. However, these materials are fundamentally limited by the large amount of expansion that occurs when they are fully embedded with lithium. When lithium is removed, this expansion and contraction causes the electrode to have a limited cycle life and low power. So far, the solution has used a very small amount of alloying electrochemical modifier in most carbon electrodes, but this method will not increase the lithium capacity as desired. It is expected to find a way to increase the alloying electrochemical modifier content in the anode composition and maintain cycle stability at the same time to increase capacity. Many approaches have been utilized, including nanostructured alloying electrochemical modifiers, carbon and alloying electrochemical modifier blends or using vacuum or high temperature to deposit alloying electrochemical modifiers on carbon. However, these methods do not have a proven scalable method that can be combined to produce desired properties.
[0008] The previously mentioned expansion associated with certain materials, such as silicon materials, when they are intercalated with lithium is a key factor in the stability, i.e., the cycle life of the material for its application in energy storage and distribution, such as use in rechargeable batteries. Over many cycles, the capacity of the material tends to fade. This capacity fade can be promoted by various different mechanisms, and one of the key mechanisms described here involves the formation of a solid electrolyte interphase (SEI) in the negative electrode and competing with the reversible lithium intercalation. It is known in the art that the SEI is a key component of capacity fade as a standard degradation mechanism, which can be modeled over long periods of time based on accelerated aging for short periods of time and high temperatures.
[0009] It is expected in the art that the SEI layer plays an important role in the safety, power capacity and cycle life of Li-ion batteries. It is said that the formation of a chemically and mechanically stable SEI layer is important for improving lithium-ion batteries. Due to the reduction of organic solvents and anions on the electrode during the charge and discharge cycle of the battery, an SEI layer is formed on the silicon of the anode, and a considerable degree of formation occurs during the first cycle. In addition, certain electrolyte additives can significantly improve the cycle efficiency of silicon-based anodes, such as vinylene carbonate, propylene carbonate, difluoro-oxalatoborate lithium and fluorine-ethylene carbonate and other substances known in the art, and combinations thereof. In addition to the common Li2CO3, alkyl Li carbonate (ROCO2Li) (lithium carboxylate), LiF, ROLi (lithium alcohol) and polyethylene oxide that appear on graphite electrodes, the SEI layer may include fluorinated carbon and silicon substances. Formation of SEI on the negative electrode is an irreversible reaction that consumes cyclable Li ions from the positive electrode, which results in most of the capacity loss observed in the first lithiation and delithiation cycles of secondary lithium-ion batteries. In addition to the loss of capacity during the first cycle, the continued formation of this layer increases the resistance to Li-ion diffusion (ie, the internal impedance of the battery).
[0010] Repeated expansion and contraction of silicon-based anode materials leads to SEI instabilities, such as cracking and reformation, with attendant capacity fading of the anode. To this end, the art describes various preferred silicon sizes and geometries in order to avoid cracking and reduce the propensity for chemical and mechanical degradation that can occur when lithium-ion batteries are cycled. To this end, the art (RSCA advances, 2013, 3, 7398, "Critical silicon-anode size foraverting lithiation-induced mechanical failure of lithium-ion batteries, Ma et al.) describes critical sizes of 90 nm for nanoparticles, 70 nm for nanowires and 33 nm for nanofilms, below which (for their respective geometries) the silicon nanostructure remains undamaged during lithiation. Another report in the art (DOI: 10.1002 / anie.200906287, "A Critical Size of Silicon Nano-Anodes for Lithium Rechargeable Batteries," Angewandte Chemie, Vol. 49, No. 12, pp. 2146-2149, 2010, Kim et al.) describes well-dispersed silicon nanocrystals, with sizes of about 10 nm showing higher capacity retention than sizes of 5 nm or 20 nm.
[0011] Additionally, nano features are important for preventing silicon from shattering during expansion and contraction and maintaining an amorphous structure throughout cycling. Shattering is believed to be a mechanical failure of silicon due to extreme strain gradients through the bulk structure. As silicon is lithiated, its volume will expand (up to 300%). Lithium ions move very slowly through solid silicon. During lithium insertion, silicon particles can hold large amounts of lithium on the surface of the particle and none in the center of the particle. The concentration gradient produces uneven expansion across the cross section. Extreme surface volume expansion will cause silicon particles to tear apart, crack, and break from the inside. Once the silicon has shattered, the battery will fail as there is no known way to salvage performance.
[0012] Thus, for energy storage applications, the preferred silicon size is less than 1 micron, preferably less than 800 nm, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 nm, preferably less than 90 nm, preferably less than 70 nm, preferably less than 50 nm, preferably less than 33 nm, preferably less than 20 nm. In some cases, the preferred silicon size is 5 nm to 20 nm. In certain cases, the preferred silicon size is less than 90 nm for nanoparticles. In certain cases, the preferred silicon size is less than 70 nm for nanowires. In certain cases, the preferred silicon size is less than 33 nm for nanofilms.
[0013] Silicon particles of the sizes described above are generally referred to as nano-sized silicon particles. Particle size is generally described as Dv50 or silicon size at 50% volume distribution, as measured by various methods known in the art, such as by laser scattering particle screening techniques.
[0014] Alternatively, or in addition to silicon exhibiting an original particle size in the above-described range, the silicon particles may also exhibit nanometer features. Silicon nanometer features preferably include nanometer feature sizes less than 1 micron, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 um, preferably less than 50 nm, preferably less than 30 nm, preferably less than 15 nm. Silicon particles having the above-described features are generally referred to as silicon particles having nanometer-scale features. Nanometer-scale features may be identified by various methods known in the art, such as by scanning electron microscopy.
[0015] The existing technology for realizing nanoscale silicon is expensive and difficult to scale. For example, the first generally recognized successful product of Si nanoclusters was reported by Heath and colleagues (Science 1992, 258, 1131; PE Batson, JR Heath, Phys. Rev. Lett. 1993, 71, 911), and involves reducing SiCl4 in a high-pressure bottle (bomb) installed in a heating jacket at high temperature and high pressure. In another example, the method utilizes SiCl4 reduction at room temperature and an inert atmosphere, however, the product obtained at room temperature is not completely crystallized and requires further high temperature annealing. Similar solution synthesis at low or high temperatures has been reported after reducing silicon salts with LiAlH4 or alkylsilanes, however, all such methods produce wide particle size distributions or involve aggregation of nanoparticles. In addition, these approaches are not suitable for commercial applications; scalability and material yield are not enough to make it used for anode production of lithium secondary battery packs.
[0016] Therefore, there remains a need in the art for readily scalable, inexpensive and improved methods for producing porous silicon materials that include nanoscale particles and / or exhibit nanofeatures and that, when combined with suitable hard carbon materials, can produce desired electrochemical properties. The present invention satisfies such a need and provides further related advantages. SUMMARY OF THE INVENTION
[0018] In general, the present invention relates to composite materials, wherein silicon is deposited in the pore volume of a porous scaffold material. The porous scaffold material may comprise a variety of different materials. In certain preferred embodiments, the porous scaffold material is a porous carbon material comprising micropores, mesopores and / or macropores. In particular, the porous carbon material provides pores of 5nm to 1000nm, which are subsequently filled with silicon. Therefore, the present disclosure also relates to a method for making a composite material, wherein silicon is deposited in the pore volume of a porous scaffold material. These composites exhibit significant and lasting lithium insertion, thus providing optimal lithium storage and application properties. These novel composites have found utility in a variety of electrical energy storage devices, such as in lithium-based electrical energy storage devices (e.g., lithium-ion batteries) as electrode materials. Electrodes comprising the novel composites disclosed herein show reversible capacity, high first cycle efficiency, high power performance, or any combination thereof. The present invention has found that such improved electrochemical performance is related to the size of silicon, the integrity of silicon and carbon materials during the cycle, the formation of a stable SEI layer, the physicochemical properties of the scaffold material (e.g., the surface area and pore volume characteristics of the carbon scaffold), and the approach to manufacturing and mixing materials.
[0019] Thus, in one embodiment, the present disclosure provides for the manufacture of novel composite materials with durable lithium intercalation, wherein the composite comprises a porous scaffold and silicon. For example, the method may include the following steps:
[0020] a) producing a porous scaffold material, wherein the porous scaffold material comprises a pore volume of 5 nm to 1000 nm,
[0021] b) Impregnating silicon into a porous scaffold material to produce a silicon-impregnated carbon material.
[0022] Thus, in one embodiment, the present disclosure provides for the manufacture of a novel composite material with durable lithium intercalation, wherein the composite comprises carbon and silicon. For example, the method may include the following steps:
[0023] a) mixing polymers and / or polymer precursors and storing them at a temperature and for a period of time sufficient to polymerize the precursors,
[0024] b) carbonizing the resulting polymer material to produce a porous carbon material,
[0025] c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to produce a silicon-impregnated carbon material.
[0026] Thus, in one embodiment, the present disclosure provides for the manufacture of a novel composite material with durable lithium intercalation, wherein the composite comprises a carbon layer surrounding a silicon-impregnated carbon material. For example, the method may include the following steps:
[0027] a) mixing polymers and / or polymer precursors and storing them at a temperature and for a period of time sufficient to polymerize the precursors,
[0028] b) carbonizing the resulting polymer material to produce a porous carbon material,
[0029] c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to produce a silicon-impregnated carbon material,
[0030] d) coating a carbon layer on the silicon-impregnated carbon material to produce a carbon-coated, silicon-impregnated carbon material.
[0031] Thus, in one embodiment, the present disclosure provides for the manufacture of a novel composite material with durable lithium intercalation, wherein the composite comprises a conductive polymer layer surrounding a silicon-impregnated carbon material. For example, the method may include the following steps:
[0032] a) mixing polymers and / or polymer precursors and storing them at a temperature and for a period of time sufficient to polymerize the precursors,
[0033] b) carbonizing the resulting polymer material to produce a porous carbon material,
[0034] c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to produce a silicon-impregnated carbon material,
[0035] d) coating a conductive polymer around the silicon-impregnated carbon material to produce a silicon-impregnated carbon material further embedded within the conductive polymer network.
[0036] Thus, in one embodiment, the present disclosure provides for the manufacture of a novel composite material with durable lithium intercalation, wherein the composite comprises a conductive polymer layer surrounding a carbon-coated, silicon-impregnated carbon material. For example, the method may include the following steps:
[0037] a) mixing polymers and / or polymer precursors and storing them at a temperature and for a period of time sufficient to polymerize the precursors,
[0038] b) carbonizing the resulting polymer material to produce a porous carbon material,
[0039] c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing gas to produce a silicon-impregnated carbon material,
[0040] d) coating a carbon layer on the silicon-impregnated carbon material to produce a carbon-coated, silicon-impregnated carbon material,
[0041] e) coating a conductive polymer around the carbon-coated, silicon-impregnated carbon material to produce a carbon-coated, silicon-impregnated carbon material further embedded within the conductive polymer network. The conductive polymer may optionally be subjected to pyrolysis.
[0042] In other embodiments, a composite comprising a porous carbon scaffold and silicon is provided, wherein the composite comprises 15 wt % to 85 wt % silicon, and wherein the composite has a micropore size of less than 10%, a mesopore size of greater than 30%, a macropore size of greater than 30%, and a micropore size of less than 0.5 cm 3 / g of pore structure with a total pore volume, the total pore volume being measured by nitrogen adsorption.
[0043] In other embodiments, a composite comprising a porous carbon scaffold and silicon is provided, wherein the composite comprises 15 wt % to 85 wt % silicon, and wherein the porous carbon scaffold has a micropore size of less than 10%, a mesopore size of greater than 30%, a macropore size of greater than 30%, and a micropore size of less than 0.5 cm 3 / g of pore structure with a total pore volume determined by nitrogen adsorption.
[0044] In further embodiments, a composite comprising a porous carbon scaffold and silicon is provided, wherein the composite comprises 35 wt % to 65 wt % silicon, and wherein the composite has a micropore size of less than 20%, a mesopore size of greater than 60%, a macropore size of less than 30%, and a pore size of 0.1 cm 3 / g to 0.5cm 3 / g of pore structure with a total pore volume determined by nitrogen adsorption.
[0045] In further embodiments, a composite comprising a porous carbon scaffold and silicon is provided, wherein the composite comprises 35 wt % to 65 wt % silicon, and wherein the porous carbon scaffold has a micropore content of less than 20%, a mesopore content of greater than 60%, a macropore content of less than 30%, and a pore size of 0.1 cm 3 / g to 0.5cm 3 / g of pore structure with a total pore volume determined by nitrogen adsorption.
[0046] Thus, the present disclosure provides novel compositions of matter and additional methods of making the same, wherein the materials exhibit remarkably durable lithium intercalation when incorporated into electrodes of lithium-based energy storage devices. In some embodiments, the lithium-based electrical energy storage device is a lithium-ion battery or a lithium-ion capacitor.
[0047] These and other aspects of the invention will become apparent with reference to the following detailed description.To this end, various references are cited herein that describe in more detail certain background information, procedures, compounds and / or compositions, and each is incorporated herein by reference in its entirety. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Schematic diagram of composite particles achieved by microwave-enabled silicon deposition on a microwave-absorbing porous carbon support.
[0050] Figure 2 .Pore volume distribution of microporous carbon scaffolds and silicon-containing composites derived therefrom.
[0051] Figure 3 .Pore volume distribution of mixed microporous carbon scaffolds, mesoporous carbon scaffolds, macroporous carbon scaffolds and silicon-containing composites derived therefrom.
[0052] Figure 4 .Pore volume distribution of macroporous carbon scaffolds and silicon-containing composites derived therefrom.
[0053] Figure 5 . Pore volume distribution of microporous carbon before and after CVD treatment to cap off the micropores.
[0054] Figure 6 Data on the anode expansion of bare carbon versus carbon composite nano-silicon relative to weight capacity.
[0055] Figure 7 Anode expansion data for sample carbon-silicon composites versus gravimetric capacity.
[0056] Figure 8 .Data on anode expansion versus volumetric capacity for sample carbon-silicon composites.
[0057] Fig. 9 Full cell data relative to Wh / L of graphite for each sample.
[0058] Fig.10 .Pore volume distribution of mixed microporous and mesoporous carbon scaffolds and silicon-containing composites derived therefrom.
[0059] Fig.11 Capacity retention (solid symbols) and Coulombic efficiency (dashed lines) of Si-C composites produced from mixed microporous and mesoporous carbon scaffolds generated at different pyrolysis temperatures (PC).
[0060] Fig.12 A to Fig.12D. Effect of carbon coating on silicon-carbon composites. Data shown represent uncoated samples (striped bars) and coated samples (solid bars) measured by electrochemistry in half cells: (12A) calculated average silicon capacity (mAh / g), (12B) observed average composite capacity (mAh / g), (12C) average coulombic efficiency, and (12D) average capacity retention at the 20th cycle.
[0061] Fig.13 Anode expansion relative to volumetric capacity when various carbon-silicon composites are fully lithiated.
[0062] Fig.14 Full-cell cycling stability of silicon-carbon composites generated from porous carbon scaffolds of relatively smaller size (triangles) versus larger size (diamonds).
[0063] Fig.15 Full cell cycling stability of silicon-carbon composites produced from porous carbon scaffolds coated with carbon (triangles) versus uncoated carbon (diamonds).
[0064] Fig.16 .Capacity retention of full battery cycle and pouch battery cycle of the C-coated silicon-carbon composite according to Example 29.
[0065] Fig.17 . Gravimetric capacity of full cell cycle and pouch cell cycle of C-coated silicon-carbon composite according to Example 29.
[0066] Fig.18 .Extraction capacity of various materials according to Example 30 at various circulation rates.
[0067] Fig.19 .Percentage of maximum extraction capacity at various circulation rates for various materials according to Example 30.
[0068] Fig. 20 . Cycling stability of the novel silicon-carbon composite according to Example 31 at various anode densification degrees.
[0069] Fig.21 . Cycling stability of the silicon oxide comparator according to Example 31 at various anode densification levels.
[0070] Fig. 22 . Full cell cycling stability of the silicon-carbon composite produced by the carbon-coated porous carbon scaffold according to Example 35 relative to the uncoated porous carbon scaffold.
[0071] Fig.23 . Full cell cycling stability of C-coated silicon carbon composite compared to graphite in full cell, button cell according to Example 36.
[0072] Fig.24 . Full cell cycling stability of C-coated silicon carbon composite versus differential voltage plot of anode in a full cell, coin cell according to Example 36 compared to graphite.
[0073] Fig.25 . Full cell cycling stability of C-coated silicon carbon composite versus graphite in a full cell, coin cell according to Example 36, differential voltage plot for the cathode.
[0074] Fig.26 . Determination of particle expansion of silicon-carbon composite by in situ TEM according to Example 39.
[0075] Fig. 27 . Determination of particle expansion of carbon-coated silicon-carbon composites by in situ TEM according to Example 39.
[0076] Details
[0077] In the following description, certain specific details are set forth in order to provide a comprehensive understanding of various embodiments. However, it will be understood by those skilled in the art that the present invention can be practiced without these details. In other cases, well-known structures are not shown or described in detail to avoid unnecessary obscure descriptions of the embodiments. Unless the context otherwise requires, throughout the specification and the claims that follow, the words "comprise" and their variants such as "include" and "contain" will be interpreted in an open, inclusive sense, that is, "including, but not limited to". In addition, the titles provided herein are merely for convenience and do not explain the scope or meaning of the claimed invention.
[0078] References to "one embodiment" or "embodiment" throughout this specification are intended to include, in at least one embodiment, a particular feature, structure, or characteristic associated with the embodiment being described. Thus, the phrases "in one embodiment" or "in an embodiment" appearing in different places throughout this specification do not necessarily all refer to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. Additionally, as used throughout this specification and the appended claims, the singular forms "a", "an," and "the" include plural referents unless the context clearly dictates otherwise. It should also be noted that the term "or" is generally used in its sense including "and / or," unless the context clearly dictates otherwise.
[0079] definition
[0080] As used herein, the following terms have the meanings specified below, unless the context requires otherwise.
[0081] "Energy storage material" refers to a material that is capable of storing an electric charge, such as in the form of a physically entrained electrolyte. Energy storage materials are capable of charging and discharging. Examples of energy storage materials include, but are not limited to, carbon (e.g., activated carbon), silicon, sulfur, lithium, and combinations thereof. The energy storage material may be used in particulate form or in a combination of inter-particle blends and / or intra-particle blends of particles. The energy storage particles may be assembled into electrodes using a dry method as described in the art or an aqueous slurry method or a non-aqueous slurry method.
[0082] "Carbon material" refers to a material or substance substantially including carbon. Examples of carbon materials include, but are not limited to, activated carbon, pyrolytic carbon, hard carbon, graphite, and other allotropes of carbon.
[0083] "Impurity" or "impurity element" refers to a foreign substance (e.g., a chemical element) within a material that is different from the chemical composition of the base material. For example, an impurity in a carbon material refers to any element or combination of elements other than carbon present in the carbon material. Impurity levels are typically expressed in parts per million (ppm).
[0084] "TXRF impurities" are impurity elements measured by total X-ray fluorescence (TXRF). The phrases "total TXRF impurity content" and "total TXRF impurity level" both refer to the sum of all impurities present in a sample, such as a polymer gel or a carbon material, a silicon material, or a composite material comprising carbon and silicon.
[0085] "Ash content" refers to the non-volatile inorganic matter remaining after subjecting a material to high decomposition temperatures. Herein, the ash content of a carbon material is calculated from the total PIXE impurity content measured by proton induced X-ray emission, which assumes complete conversion of non-volatile elements to the expected combustion products (i.e., oxides).
[0086] "Polymer" refers to a macromolecule comprised of two or more structural repeating units.
[0087] "Synthetic polymer precursor material" or "polymer precursor" refers to a compound used to prepare a synthetic polymer. Examples of polymer precursors that can be used in the formulations disclosed herein include, but are not limited to, aldehydes (i.e., HC(=O)R, where R is an organic group), such as formaldehyde (methanal / formaldehyde), acetaldehyde (ethanal / acetaldehyde), propanal / propionaldehyde, butanal / butyraldehyde); glucose; benzaldehyde and cinnamaldehyde. Other exemplary polymer precursors include, but are not limited to, phenolic compounds, such as phenol and polyhydroxybenzenes, such as dihydroxy or trihydroxybenzenes, such as resorcinol (i.e., 1,3-dihydroxybenzene), catechol, hydroquinone, and phloroglucinol. Mixtures of two or more polyhydroxybenzenes are also encompassed within the meaning of polymer precursors.
[0088] "Sol" refers to a colloidal suspension of precursor particles (eg, polymer precursors), and the term "gel" refers to a wet three-dimensional porous network obtained by coagulation or reaction of the precursor particles.
[0089] "Polymer gel" refers to a gel in which the network components are polymers; typically a polymer gel is a wet (water-based or non-aqueous), three-dimensional structure comprising polymers formed from synthetic precursors or polymer precursors.
[0090] "Sol-gel" refers to a subclass of polymer gels in which the polymer is a colloidal suspension that forms a wet three-dimensional porous network obtained by reacting polymer precursors.
[0091] "Polymer hydrogel" or "hydrogel" refers to a polymer gel or subclass of gels in which the solvent used to synthesize the precursors or monomers is water or a mixture of water and one or more water-miscible solvents.
[0092] "Acid" refers to any substance that can lower the pH of a solution. Acids include Arrhenius acids, Bronsted acids, Acids and Lewis acids. "Solid acid" refers to a dry or granular compound that produces an acidic solution when dissolved in a solvent. The term "acidic" means having the properties of an acid.
[0093] "Base" refers to any substance that can increase the pH of a solution. Bases include Arrhenius bases, Bronsted bases, Bases and Lewis bases. "Solid base" refers to a dry or granular compound that produces a basic solution when dissolved in a solvent. The term "basic" means having the properties of a base.
[0094] A "catalyst" is a substance that changes the rate of a chemical reaction. The catalyst participates in the reaction in a cyclic manner, so the catalyst is regenerated cyclically. The present disclosure encompasses sodium-free catalysts. The catalyst used to prepare the polymer gel as described herein can be any compound that promotes the polymerization of polymer precursors to form a polymer gel. A "volatile catalyst" is a catalyst that has a tendency to evaporate at atmospheric pressure or below. Exemplary volatile catalysts include, but are not limited to, ammonium salts, such as ammonium bicarbonate, ammonium carbonate, ammonium hydroxide, and combinations thereof.
[0095] "Carbonizing," "pyrolyzing," "carbonization," and "pyrolysis" all refer to the process of heating a carbonaceous material under an inert atmosphere (e.g., argon or nitrogen) or in a vacuum at a pyrolysis dwell temperature so that the target material collected at the end of the process is primarily carbon. "Pyrolyzed" refers to a material or substance (e.g., a carbon material) that has undergone a pyrolysis process.
[0096] "Density" as used with respect to an electrode refers to the total density of the active material (eg, carbon-silicon fluoride), any optional binder, conductivity enhancers, etc. The density of an electrode does not include the mass or volume associated with the current collector of the associated electrode.
[0097] "Dwell temperature" refers to the temperature of the furnace during the portion of the process that is reserved for maintaining a relatively constant temperature (i.e., not increasing or decreasing the temperature). For example, the pyrolysis dwell temperature refers to the relatively constant furnace temperature during pyrolysis, and the activation dwell temperature refers to the relatively constant furnace temperature during activation.
[0098] "Pore" refers to an opening or depression in a surface, or a channel in a carbon material (e.g., activated carbon), pyrolyzed dried polymer gel, pyrolyzed polymer cryogel, pyrolyzed polymer xerogel, pyrolyzed polymer aerogel, active dried polymer gel, active polymer cryogel, active polymer xerogel, active polymer aerogel, etc. A pore can be a single channel or connected to other channels in a continuous network throughout the structure.
[0099] "Pore structure" refers to the surface layout of internal pores within a carbon material (e.g., an activated carbon material). The composition of the pore structure includes pore size, pore volume, surface area, density, pore size distribution, and pore length. Typically, the pore structure of an activated carbon material includes micropores and mesopores.
[0100] "Mesopores" generally refer to pores having a diameter of about 2 nanometers to about 50 nanometers, while the term "micropores" refers to pores having a diameter less than about 2 nanometers. Mesoporous carbon materials have greater than 50% of the total pore volume in mesopores, while microporous carbon materials have greater than 50% of the total pore volume in micropores. Pores greater than about 50 nanometers are referred to as "macroporous."
[0101] "Surface area" refers to the total specific surface area of a substance that can be measured by the BET technique. Surface area is usually measured in m 2 The BET (Brunauer / Emmett / Teller) technique uses an inert gas (such as nitrogen) to measure the amount of gas adsorbed on a material and is commonly used in the art to determine the accessible surface area of a material.
[0102] "Connected" when used in reference to mesopores and micropores refers to the spatial orientation of such pores.
[0103] "Binder" refers to a material that is capable of holding together individual particles of carbon so that after mixing the binder and carbon together, the resulting mixture can be formed into a sheet, pellet, disk, or other shape. Non-exclusive examples of binders include fluoropolymers such as PTFE (polytetrafluoroethylene, Teflon), PFA (perfluoroalkoxy polymer resin, also known as Teflon), FEP (fluorinated ethylene propylene, also known as Teflon), ETFE (polyethylene tetrafluoroethylene, sold as Tefzel and Fluon), PVF (polyvinyl fluoride, sold as Tedlar), ECTFE (polyethylene chlorotrifluoroethylene, sold as Halar), PVDF (polyvinylidene fluoride, sold as Kynar), PCTFE (polychlorotrifluoroethylene, sold as Kel-F and CTFE), trifluoroethanol, and combinations thereof.
[0104] "Composite material" refers to a composition comprising multiple (2 or more) different chemical species within the same particle, such as a particle comprising a porous carbon material and a silicon material.
[0105] "Allotropes" refers to materials that can exist in different forms. C60, graphene, diamond, hard carbon, soft carbon, graphite, and carbon nanotubes are all examples of carbon allotropes. "Hard carbon" refers to non-graphitized carbon materials. At high temperatures (e.g., >1500°C), hard carbon remains essentially amorphous, while "soft" carbon will undergo crystallization and become graphitized.
[0106] "Lithium uptake" refers to the ability of carbon to intercalate, absorb or store lithium, measured as the ratio between the maximum number of lithium atoms to six carbon atoms.
[0107] "SEI" as known in the art refers to the solvent-electrolyte interphase.
[0108] "Young's modulus", also known as tensile modulus or elastic modulus, is a mechanical property of a linear elastic solid material. It measures the force (per unit area) required to stretch (or compress) the material.
[0109] "Bulk modulus" describes bulk elasticity or the tendency of an object to deform in all directions when loaded uniformly in all directions; it is defined as the ratio of volume stress over volume strain, and is the inverse of compressibility. Bulk modulus is the extension of Young's modulus to three dimensions.
[0110] "Coulombic efficiency" herein refers to the amount of capacitive discharge due to lithium extraction from a lithium-ion based energy storage device divided by the amount of capacitive charge or uptake due to lithium insertion. Coulombic efficiency is reported as a percentage or fraction (eg, 99% = 0.99).
[0111] "Nanoscale" means a material (e.g., silicon) having at least one dimension that is nanoscale, such as at least one dimension that is less than 1 micron. For energy storage applications, preferred silicon sizes are less than 1 micron, preferably less than 800 nm, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 nm, preferably less than 50 nm, preferably less than 30 nm, preferably less than 15 nm. Silicon particles of the sizes described above are generally referred to as nanoscale silicon particles. Particle size is generally described as Dv50 or silicon size at 50% volume distribution, which is measured according to various methods known in the art, such as by laser scattering particle screening techniques.
[0112] Alternatively, or in addition to the original particle size in the above-described range exhibited by silicon, the silicon particles may also exhibit nano-features. "Nano-features" refer to features (e.g., holes, etc.) with nano-scale dimensions, e.g., less than 1 micron. "Nano-featured" materials are materials comprising nano-features. Silicon nano-features preferably include nano-feature sizes less than 1 micron, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 nm, preferably less than 50 nm, preferably less than 30 nm, preferably less than 15 nm. Silicon particles having the above-described features are generally referred to as silicon particles having nano-features. Nano-features can be identified by various methods known in the art, such as by scanning electron microscopy.
[0113] A. Porous Scaffold Materials
[0114] For the purposes of the present invention, a porous support in which silicon is to be impregnated is required. In this article, the porous support can take into account various materials. In a preferred embodiment, the porous support material mainly comprises carbon, such as hard carbon. Other allotropes of carbon are also conceivable, such as graphite, amorphous carbon, diamond, C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene and / or carbon fiber. Porosity can be introduced into carbon materials in various ways. For example, the porosity in the carbon material can be achieved by adjusting the polymer precursor and / or processing conditions to produce the porous carbon material, and described in detail in the subsequent section.
[0115] In other embodiments, the porous support can include polymer materials. For this reason, it is envisioned that various polymers have utility, and the polymer includes but is not limited to inorganic polymers, organic polymers and addition polymers. Examples of inorganic polymers herein include but are not limited to homochain polymers of silicon-silicon, such as polysilane, silicon carbide, polygermane and polystannane. Other examples of inorganic polymers include but are not limited to heterochain polymers, such as polyborane (polyborazylene), polysiloxanes such as polydimethylsiloxane (PDMS), polymethylhydrogensiloxane (PMHS) and polydiphenylsiloxane, polysilazane such as hydrogenated polysilazane (PHPS), polyphosphazene and poly (dichlorophosphazene), polyphosphate, polythiazole and polysulfide. Examples of organic polymers include, but are not limited to, low density polyethylene (LDPE), high density polyethylene (HDPE), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), nylon, nylon 6, nylon 6,6, Teflon (polytetrafluoroethylene), thermoplastic polyurethane (TPU), polyurea, poly (lactide), poly (glycolide) and combinations thereof, phenolic resins, polyamides, polyaramids, polyethylene terephthalate, polychloroprene, polyacrylonitrile, polyaniline, polyimide, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PDOT:PSS) and other substances known in the art. The organic polymer may be synthetic or of natural origin. In some embodiments, the polymer is a polysaccharide, such as starch, cellulose, cellobiose, amylose, amylopectin, gum arabic, lignin, and the like. In some embodiments, the polysaccharide is derived from the caramelization of monosaccharides or oligosaccharides, such as fructose, glucose, sucrose, maltose, raffinose, and the like.
[0116] With the numerous polymers envisioned to have the potential to provide porous matrices, it is envisioned that various processing approaches will achieve the porosity. In this article, the general methods for producing porosity in various materials are numerous, as known in the art, including but certainly not limited to the following methods: including emulsification, micelle generation, gasification, dissolution followed by solvent removal (e.g., freeze drying), axial compaction and sintering, gravity sintering, powder rolling and sintering, isostatic compaction and sintering, metal spraying, metal coating and sintering, metal injection molding and sintering, etc. Other approaches to producing porous polymer materials are also envisioned, including the production of porous gels, such as freeze-dried gels, etc.
[0117] In certain embodiments, the porous scaffold material comprises a porous ceramic material. In certain embodiments, the porous scaffold material comprises a porous ceramic foam. In this article, the general method of creating porosity in a ceramic material is different, as known in the art, including but certainly not limited to creating porous. In this article, the general method and materials suitable for including porous ceramics include but are not limited to porous alumina, porous zirconia toughened alumina, porous partially stabilized zirconia, porous alumina, porous sintered silicon carbide, sintered silicon nitride, porous cordierite, porous zirconia, clay-bonded silicon carbide, etc.
[0118] In certain embodiments, the porous support comprises porous silica or other oxygen-containing silicon materials.The production of silica gels (including sol-gels) and other porous silicas is known in the art.
[0119] In certain embodiments, porous material includes porous metal. Suitable metals in this regard include but are not limited to porous aluminum, porous steel, porous nickel, porous Inconel (Inconcel), porous Hastelloy (Hasteloy), porous titanium, porous copper, porous brass, porous gold, porous silver, porous germanium and other metals capable of forming porous structures, as known in the art. In certain embodiments, porous support material includes porous metal foam. Such metals and their manufacture methods are known in the art. Such methods include but are not limited to casting (including foaming, infiltration and low foam casting), deposition (chemical and physical), gas eutectic formation and powder metallurgy technology (for example, powder sintering, compaction in the presence of foaming agent and fiber metallurgy technology).
[0120] B. Porous Carbon Materials
[0121] Methods for preparing porous carbon materials from polymer precursors are known in the art. For example, methods for preparing carbon materials are described in U.S. Patents Nos. 7,723,262, 8,293,818, 8,404,384, 8,654,507, 8,916,296, 9,269,502, U.S. Patent Applications Nos. 12 / 965,709 and 13 / 486,731, and International Patent Application PCT / US2014 / 029106, all of which are incorporated herein by reference in their entirety for all purposes. Therefore, in one embodiment, the present disclosure provides a method for preparing any of the carbon materials or polymer gels described above. Carbon materials can be synthesized by pyrolysis of a single precursor, such as a carbohydrate material, such as sucrose, fructose, glucose, dextrin, maltodextrin, starch, amylopectin, amlyose, lignin, gum arabic, and other carbohydrates known in the art, and combinations thereof. Alternatively, carbon materials can be synthesized by pyrolysis of a composite resin, such as a polymer precursor formed by a sol-gel method in a suitable solvent using a cross-linking agent, such as phenol, resorcinol, bisphenol A, urea, melamine, and other suitable compounds known in the art, and combinations thereof, such as water, ethanol, methanol, and other solvents known in the art, and combinations thereof, such as formaldehyde, furfural, and other cross-linking agents known in the art, and combinations thereof. The resin can be an acid or a base and can contain a catalyst. The catalyst can be volatile or non-volatile. The pyrolysis temperature and residence time can vary as known in the art.
[0122] In some embodiments, the method comprises a sol-gel method, a condensation method, or a cross-linking method involving a monomer precursor and a cross-linking agent, two existing polymers and a cross-linking agent, or a single polymer and a cross-linking agent to prepare a polymer gel, and then pyrolyzing the polymer gel. The polymer gel can be dried (e.g., freeze-dried) before pyrolysis; however, drying is not necessarily required.
[0123] In some embodiments, the polymer gel is freeze-dried or lyophilized to leave a porosity of the desired degree and properties, such as macroporosity. The porosity in the freeze-dried gel or crystal gel is not subject to theoretical constraints. In some embodiments, the gel in the freeze-drying is first reduced to particles by the size of the monolithic material, and then extremely quickly frozen, dried under vacuum, so as to achieve crystal gel. Particle size reduction can be achieved by methods known in the art, such as by crushing, grinding, grinding by various means, etc. Such methods are suitable for producing particles with a volume average particle size (Dv50) less than 10cm, such as less than 5cm, such as less than 2cm, such as less than 1cm, such as less than 5mm, such as less than 1mm, such as less than 100 microns, such as less than 10 microns. Extremely rapid freezing can be achieved by subjecting the particles to extremely cooling liquids (such as liquid nitrogen) or other rapid freezing known in the art. Not subject to theoretical constraints, extremely rapid freezing produces a large degree of ice surface area, and sublimates under vacuum known in the art, producing a large surface area in freeze-dried polymers or crystal gels.
[0124] The sol-gel method provides flexibility for incorporating various electrochemical modifiers, which can be incorporated in many steps. In one embodiment, a method for preparing a polymer gel containing an electrochemical modifier is provided. In another embodiment, a method for preparing a pyrolysis polymer gel is provided. The details of the variable method parameters of various embodiments of the disclosed method are described below.
[0125] The target carbon properties can be derived from various polymer chemistries, provided the polymerization reaction produces a resin / polymer with the desired carbon backbone. Different polymer families include novolacs, resols, acrylates, styrenics, ureathanes, rubbers (chloroprene, styrene-butadiene, etc.), nylons, etc. Any of these polymer resins can be prepared via a number of different methods including sol-gel, emulsion / suspension, solid state, molten state, etc. for the polymerization and crosslinking processes.
[0126] The polymer gel can be prepared by a sol-gel method. For example, the polymer gel can be prepared by copolymerizing one or more polymer precursors in an appropriate solvent. In one embodiment, one or more polymer precursors are copolymerized under acidic conditions. In some embodiments, the first polymer precursor is a phenolic compound and the second polymer precursor is an aldehyde compound. In one embodiment of the method, the phenolic compound is phenol, resorcinol, catechol, hydroquinone, phloroglucinol, or a combination thereof; and the aldehyde compound is formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, benzaldehyde, cinnamaldehyde, or a combination thereof. In other embodiments, the phenolic compound is resorcinol, phenol, or a combination thereof, and the aldehyde compound is formaldehyde. In other embodiments, the phenolic compound is resorcinol and the aldehyde compound is formaldehyde. Other polymer precursors include nitrogen-containing compounds such as melamine, urea, and ammonia.
[0127] In some embodiments, the electrochemical modifier is incorporated into a material as a polymer. For example, an organic or carbon-containing polymer, such as RF, is copolymerized with a polymer containing an electrochemical modifier. In one embodiment, the polymer containing the electrochemical modifier contains silicon. In one embodiment, the polymer is tetraethyl orthosilicate (TEOS). In one embodiment, a TEOS solution is added to an RF solution before or during polymerization. In another embodiment, the polymer is a polysilane with an organic side group. In some cases, these side groups are methyl, in other cases, these groups are phenyl, and in other cases, the side chain includes phenyl, pyrrolidone (pyrol), acetate, vinyl, siloxane fragments. In some cases, the side chain includes a 14th group element (silicon, germanium, tin or lead). In other cases, the side chain includes a 13th group element (boron, aluminum, boron, gallium, indium). In other cases, the side chain includes a 15th group element (nitrogen, phosphorus, arsenic). In other cases, the side chain includes a 16th group element (oxygen, sulfur, selenium).
[0128] In another embodiment, the electrochemical modifier is silole. In some cases, it is phenol-silole or silafluorene. In other cases, it is polysilole or polysilafluorene. In some cases, silicon is replaced by germanium (germole or germafluorene), tin (stannole or stannaflourene), nitrogen (carbazole) or phosphorus (phosphole or phosphofluorene). In all cases, the material containing heteroatoms can be small molecules, oligomers or polymers. The phosphorus atom can also be bonded to oxygen or not bonded to oxygen.
[0129] In some embodiments, the reactant contains phosphorus. In certain other embodiments, phosphorus is in the form of phosphoric acid. In certain other embodiments, phosphorus can be in the form of a salt, wherein the anion of the salt comprises one or more phosphates, phosphites, phosphonium ions, hydrogen phosphates, dihydrogen phosphates, hexafluorophosphates, hypophosphites, polyphosphates or pyrophosphate ions, or combinations thereof. In certain other embodiments, phosphorus can be in the form of a salt, wherein the cation of the salt comprises one or more phosphonium ions. Any of the above embodiments can be selected to contain non-phosphate anions or cation pairs for those known and described in the art. In this case, exemplary cations paired with phosphate-containing anions include but are not limited to ammonium ions, tetraethylammonium ions and tetramethylammonium ions. In this case, exemplary anions paired with phosphate-containing cations include but are not limited to carbonate, bicarbonate and acetate.
[0130] In some cases, the crosslinker is important because of its chemical and electrochemical properties. In other cases, the crosslinker is important because it locks into the polymer geometry. In other cases, the polymer geometry and chemical composition are important.
[0131] Crosslinking agents can react at low or high temperatures. In some cases, part of the reaction will occur at low temperatures, while the remainder of the reaction occurs at higher temperatures. The degree of crosslinking and reaction kinetics can be measured by various chemical techniques (TGA, FTIR, NMR, XRD, etc.) and physical techniques (indentation, tensile testing, modulus, hardness, etc.).
[0132] In some cases, it will be advantageous to have the electrochemical modifier and / or crosslinker uniformly distributed throughout the initial copolymer-homogeneous mixture. In other cases, it is important to have a non-uniform distribution of the crosslinker and / or electrochemical modifier throughout the initial copolymer.
[0133] The structure of the polymer precursor is not particularly limited, provided that the polymer precursor is capable of reacting with another polymer precursor or with a second polymer precursor to form a polymer. In some embodiments, the polymer precursor is selected from alcohols, phenols, polyols, sugars, alkylamines, aromatic amines, aldehydes, ketones, carboxylic acids, esters, ureas, acyl halides, olefins, alkynes, acrylates, epoxides, and isocyanates.
[0134] Various monomers, molecular components, oligomers and polymeric materials can be combined to prepare various polymers, including novolacs, resols, novolacs epoxides (including one or more of phenol, resorcinol, formaldehyde, epichlorohydrin, bisphenol-A, bisphenol-F, epoxides), rubbers (isoprene, styrene-butadiene, styrene-butadiene-styrene, isobutylene, polyacrylate rubber, ethylene-acrylate rubber, bromo-isobutylene, isoprene, polybutadiene, chloroisoprene isoprene, polychloroprene, epichlorohydrin, ethylene propylene, ethylene propylene diene monomer, polyether urethane, perfluorocarbon rubber, fluorosilicone, hydrogenated nitrile butadiene, acrylonitrile butadiene, polyurethane), nylons (including nylon-6; nylon-6,6; nylon- 6,9; nylon-6,10; nylon-6,12; nylon-11, nylon-12 and nylon-4,6), acrylates (methyl acrylate, ethyl acrylate, 2-chloroethyl-vinyl ether, 2-ethylhexyl acrylate, hydroxyethyl methacrylate, butyl acrylate, butyl methacrylate, acrylonitrile), polystyrene, and polyurethane (composed of ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, tripropylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,6-hexanediol, ethanolamine, diethanolamine, methyldiethanolamine, phenyldiethanolamine, glycerol, trimethylolpropane, 1,2,6-hexanetriol, triethanolamine, pentaerythritol, diethyltoluenediamine, dimethylthiotoluenediamine).
[0135] In some cases, the polymer precursor material includes (a) alcohols, phenolic compounds and other monohydroxy or polyhydroxy compounds and (b) aldehydes, ketones, and combinations thereof. In this article, representative alcohols include linear and branched, saturated and unsaturated alcohols. Another exemplary phenolic compound is bisphenol A and related bisphenol molecules. Suitable phenolic compounds include polyhydroxybenzenes, such as dihydroxy or trihydroxybenzenes. Another exemplary phenolic compound is bisphenol A and related bisphenol molecules. Representative polyhydroxybenzenes include meta-diphenol (i.e., 1,3-dihydroxybenzene), catechol, hydroquinone and phloroglucinol. Mixtures of two or more polyhydroxybenzenes can also be used. Phenol (monohydroxybenzene) can also be used. Representative polyhydroxy compounds include sugars (e.g., glucose) and other polyols (e.g., mannitol). In this article, aldehydes include: straight-chain saturated aldehydes, such as formaldehyde (methanal / formaldehyde), acetaldehyde (ethanal / acetaldehyde), propanal / propionaldehyde, butanal / butyraldehyde, etc.; straight-chain unsaturated aldehydes, such as vinyl ketone and other ketones, 2-propenal (propenal / acrylaldehyde), 2-butenal (crotonaldehyde), 3-butenal, etc.; branched saturated and unsaturated aldehydes; and aromatic aldehydes, such as benzaldehyde, salicylaldehyde, hydrocinnamaldehyde, etc. Suitable ketones include: straight-chain saturated ketones, such as acetone and 2-butanone, etc.; straight-chain unsaturated ketones, such as propenone, 2-butenone and 3-butenone (methyl vinyl ketone), etc.; branched saturated and unsaturated ketones; and aromatic ketones, such as methyl benzyl ketone (phenylacetone), ethyl benzyl ketone, etc. The polymer precursor material can also be a combination of the above-mentioned precursors.
[0136] In one embodiment, the method includes using a first polymer precursor and a second polymer precursor, and in some embodiments, the first polymer precursor or the second polymer precursor is a carbonyl-containing compound and the remaining first polymer precursor or the second polymer precursor is an alcohol-containing compound. In some embodiments, the first polymer precursor is a phenolic compound and the second polymer precursor is an aldehyde compound (e.g., formaldehyde). In one embodiment of the method, the phenolic compound is phenol, resorcinol, catechol, hydroquinone, phloroglucinol, or a combination thereof; and the aldehyde compound is formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, benzaldehyde, cinnamaldehyde, or a combination thereof. In other embodiments, the phenolic compound is resorcinol, phenol, or a combination thereof, and the aldehyde compound is formaldehyde. In other embodiments, the phenolic compound is resorcinol and the aldehyde compound is formaldehyde. In some embodiments, the polymer precursors are alcohols and carbonyl compounds (e.g., resorcinol and acetaldehyde), and they are present in a ratio of about 0.5:1.0, respectively.
[0137] In some embodiments, a polymer precursor is an alcohol-containing substance, and another polymer precursor is a carbonyl-containing substance. The relative amount of the alcohol-containing substance (for example, alcohol compound, phenolic compound and monohydroxy compound or polyol or its combination) reacted with a carbonyl-containing substance (for example, aldehyde, ketone or its combination) can change significantly. In some embodiments, select the ratio of alcohol-containing substance and aldehyde substance, so that the total mole number of the reactive alcohol group in the alcohol-containing substance is approximately the same as the total mole number of the reactive carbonyl in the aldehyde substance. Similarly, the ratio of alcohol-containing substance and ketone substance can be selected, so that the total mole number of the reactive alcohol group in the alcohol-containing substance is approximately the same as the total mole number of the reactive carbonyl in the ketone substance. When the carbonyl-containing substance comprises the combination of aldehyde substance and ketone substance, the same general 1:1 mol ratio is equally applicable.
[0138] In other embodiments, the polymer precursor is a urea-containing or amine-containing compound. For example, in some embodiments, the polymer precursor is urea or melamine. Other embodiments include polymer precursors selected from isocyanates or other reactive carbonyl compounds (e.g., acyl halides, etc.). Other embodiments use phenolic precursors, including but not limited to phenol, resorcinol, and molecules containing other hydroxyl groups and aromatic rings.
[0139] In some embodiments of the methods described herein, the molar ratio of the phenolic precursor to the catalyst is from about 5:1 to about 2000:1, or the molar ratio of the phenolic precursor to the catalyst is from about 20:1 to about 200:1. In other embodiments, the molar ratio of the phenolic precursor to the catalyst is from about 25:1 to about 100:1. In other embodiments, the molar ratio of the phenolic precursor to the catalyst is from about 5:1 to about 10:1. In other embodiments, the molar ratio of the phenolic precursor to the catalyst is from about 100:1 to about 5:1.
[0140] In a specific embodiment, where one of the polymer precursors is resorcinol and / or phenol and the other polymer precursor is formaldehyde, the ratio of resorcinol and / or phenol to the catalyst can be varied to obtain the desired properties of the resulting polymer gel and carbon material. In some embodiments of the methods described herein, the molar ratio of resorcinol and / or phenol to the catalyst is from about 10:1 to about 2000:1, or the molar ratio of resorcinol and / or phenol to the catalyst is from about 20:1 to about 200:1. In other embodiments, the molar ratio of resorcinol and / or phenol to the catalyst is from about 25:1 to about 100:1. In other embodiments, the molar ratio of resorcinol and / or phenol to the catalyst is from about 5:1 to about 10:1. In other embodiments, the molar ratio of resorcinol and / or phenol to the catalyst is from about 100:1 to about 5:1.
[0141] The total solid content of the solution or suspension can be changed before the polymer gel is formed. The weight ratio of resorcinol to water is from about 0.05-1 to about 0.70-1. Alternatively, the ratio of resorcinol to water is from about 0.15-1 to about 0.6-1. Alternatively, the ratio of resorcinol to water is from about 0.15-1 to about 0.35-1. Alternatively, the ratio of resorcinol to water is from about 0.25-1 to about 0.5-1. Alternatively, the ratio of resorcinol to water is from about 0.3-1 to about 0.35-0.6.
[0142] Examples of solvents for preparing polymer gels disclosed herein include, but are not limited to, water or alcohol, such as ethanol, tert-butyl alcohol, methanol or a combination thereof and aqueous mixtures thereof. Such solvents can be used to dissolve polymer precursor materials, such as dissolving phenolic compounds. In addition, in some methods, such solvents are used for solvent exchange in polymer gels (before freezing and drying), wherein the solvent from the polymerization of precursors (such as resorcinol and formaldehyde) is exchanged for pure alcohol. In one embodiment of the application, polymer gels are prepared by a method that does not include solvent exchange.
[0143] Suitable catalysts in the preparation of polymer gels include volatile alkaline catalysts that promote the polymerization of precursor materials into monolithic polymers. The catalyst may also include various combinations of the above-described catalysts. In embodiments comprising phenolic compounds or other polymer precursors, such catalysts may be used in a molar ratio of phenolic compounds: catalyst of 5:1 to 200:1. For example, in some specific embodiments, such catalysts may be used in a molar ratio of phenolic compounds: catalyst of 5:1 to 10:1.
[0144] In some embodiments, the gel polymerization process is carried out under catalytic conditions. Thus, in some embodiments, the method includes mixing the catalyst with the solvent-free mixture. In some embodiments, the catalyst is solid at room temperature and pressure.
[0145] In some embodiments, the catalyst is a liquid at room temperature and pressure. In some embodiments, the catalyst is a liquid at room temperature and pressure that does not provide for dissolution of one or more other polymer precursors.
[0146] In some embodiments, the catalyst comprises a basic volatile catalyst. For example, in one embodiment, the basic volatile catalyst comprises ammonium carbonate, ammonium bicarbonate, ammonium acetate, ammonium hydroxide, or a combination thereof. In other embodiments, the basic volatile catalyst is ammonium carbonate. In yet another other embodiment, the basic volatile catalyst is ammonium acetate.
[0147] The molar ratio of the catalyst to the polymer precursor (e.g., phenolic compound) can have an effect on the final properties of the polymer gel and the final properties of the carbon material. Therefore, in some embodiments, such catalysts are used in a molar ratio of 5:1 to 2000:1 of polymer precursor: catalyst. In some embodiments, such catalysts can be used in a molar ratio of 10:1 to 400:1 of polymer precursor: catalyst. For example, in other embodiments, such catalysts can be used in a molar ratio of 5:1 to 100:1 of polymer precursor: catalyst. For example, in some embodiments, the molar ratio of the catalyst to the polymer precursor is about 400:1. In other embodiments, the molar ratio of the catalyst to the polymer precursor is about 100:1. In other embodiments, the molar ratio of the catalyst to the polymer precursor is about 50:1. In other embodiments, the molar ratio of the catalyst to the polymer precursor is about 10:1. In some of the aforementioned embodiments, the polymer precursor is a phenolic compound, such as resorcinol or phenol.
[0148] In other embodiments, the method includes mixing the acid. In certain embodiments, the acid is solid at room temperature and pressure. In some embodiments, the acid is liquid at room temperature and pressure. In some embodiments, the acid is liquid at room temperature and pressure that does not provide dissolution of one or more other polymer precursors.
[0149] Acid can be selected from many acids suitable for polymerization process. For example, in some embodiments, acid is acetic acid, and in other embodiments, acid is oxalic acid. In other embodiments, acid is mixed with the first solvent or the second solvent in a ratio of 99:1, 90:10, 75:25, 50:50, 25:75, 20:80, 10:90 or 1:90 acid and solvent. In other embodiments, acid is acetic acid, and the first solvent or the second solvent is water. In other embodiments, acidity is provided by adding solid acid.
[0150] The total amount of acid in the mixture can be varied to change the properties of the final product. In some embodiments, the acid is present in about 1% to about 50% of the mixture weight. In other embodiments, the acid is present in about 5% to about 25%. In other embodiments, the acid is present in about 10% to about 20%, such as about 10%, about 15%, or about 20%.
[0151] In certain embodiments, the polymer precursor components are blended together and subsequently maintained at a time and temperature sufficient to achieve polymerization. One or more of the polymer precursor components may have a particle size less than about 20 mm, such as less than 10 mm, such as less than 7 mm, such as less than 5 mm, such as less than 2 mm, such as less than 1 mm, such as less than 100 microns, such as less than 10 microns. In some embodiments, during the blending process, the particle size of one or more polymer precursor components is reduced.
[0152] The mixing of one or more polymer precursor components in the absence of solvent can be achieved by methods described in the art, such as ball milling, jet milling, Fritsch milling, planetary mixing, and other mixing methods for mixing or blending solid particles, while controlling process conditions (e.g., temperature). The mixing or blending process can be achieved before, during, and / or after (or a combination thereof) incubation at the reaction temperature.
[0153] Reaction parameters include aging the blended mixture at a temperature and time sufficient to react one or more polymer precursors with each other and form a polymer. In this regard, a suitable aging temperature is a temperature from about room temperature to a temperature that is or is close to the melting point of one or more polymer precursors. In some embodiments, a suitable aging temperature is a temperature from about room temperature to a temperature that is or is close to the glass transition temperature of one or more polymer precursors. For example, in some embodiments, the solvent-free mixture is aging at a temperature of about 20°C to about 600°C, for example, from about 20°C to about 500°C, for example, from about 20°C to about 400°C, for example, from about 20°C to about 300°C, for example, from about 20°C to about 200°C. In certain embodiments, the solvent-free mixture is aging at a temperature of about 50°C to about 250°C.
[0154] The reaction time is generally sufficient to allow the polymer precursor to react and form a polymer, for example, the mixture can be aged at any time from 1 hour to 48 hours, more or less depending on the desired result. Typical embodiments include a time period of about 2 hours to about 48 hours of aging, for example, in some embodiments, aging includes about 12 hours, and in other embodiments, aging includes about 4 hours-8 hours (e.g., about 6 hours).
[0155] In certain embodiments, the electrochemical modifier is incorporated during the polymerization process described above. For example, in some embodiments, the electrochemical modifier in the form of metal particles, metal slurry, metal salt, metal oxide or molten metal can be dissolved or suspended in the mixture that produces the gel resin.
[0156] Exemplary electrochemical modifiers for producing composite materials can fall into more than one chemical category. In some embodiments, the electrochemical modifier is a sugar, including but not limited to chitin, chitosan, glucose, sucrose, fructose, cellulose and combinations thereof. In one embodiment, the electrochemical modifier is a biopolymer, such as lignin. In one embodiment, the electrochemical modifier is a protein, such as gelatin. In one embodiment, the electrochemical modifier is a biopolymer, such as lignin. In one embodiment, the electrochemical modifier is an amine compound, such as urea or melamine, or a combination thereof. In certain embodiments, the electrochemical modifier is a halogen salt, including but not limited to sodium chloride, lithium bromide, potassium fluoride and combinations thereof. In certain embodiments, the electrochemical modifier is a nitrate, including but not limited to lithium nitrate, sodium nitrate and combinations thereof. In certain embodiments, the electrochemical modifier is a carbide compound, including but not limited to calcium carbide, silicon carbide and combinations thereof. In certain embodiments, the electrochemical modifier includes a metal, and exemplary substances include but are not limited to aluminum isopropoxide, manganese acetate, nickel acetate, iron acetate, tin chloride, silicon chloride and combinations thereof. In certain embodiments, the electrochemical modifier is a phosphoric acid compound, including but not limited to phytic acid, phosphoric acid, ammonium dihydrogen phosphate, and combinations thereof. In certain embodiments, the electrochemical modifier comprises silicon, and exemplary materials include but are not limited to silicon powder, silicon nanotubes, polycrystalline silicon, nanocrystalline silicon, amorphous silicon, porous silicon, nano-sized silicon, nano-featured silicon, nano-sized and nano-featured silicon, silicyne, and black silicon, and combinations thereof.
[0157] Electrochemical modifiers can be combined with various polymer systems with potential (or secondary) polymer functional groups by physical mixing or chemical reaction. Examples of potential polymer functional groups include but are not limited to epoxy, unsaturated groups (double bonds and triple bonds), acid groups, alcohol groups, amine groups, basic groups. Crosslinking with potential functional groups can occur via heteroatoms (for example, with sulfur vulcanization, acid / base / with phosphoric acid ring-opening reaction), with organic acid or base (described above) reaction, with transition metal (including but not limited to Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ag, Au) coordination, ring-opening or ring-closure reaction (rotaxane, spiro compounds, etc.).
[0158] The polymerization of forming polymer gel can be achieved by various means described in the art, and may include the addition of electrochemical modifiers. For example, polymerization can be achieved by incubating suitable polymer precursor materials and optional electrochemical modifiers in the presence of suitable catalysts for a sufficient period of time. The polymerization time can be a period of several minutes or hours to several days, depending on the temperature (the higher the temperature, the faster the reaction rate, and accordingly, the shorter the time required). The polymerization temperature can be room temperature to a temperature close to (but lower than) the boiling point of the starting solution. For example, in some embodiments, the polymer gel is matured at a temperature of about 20°C to about 120°C, for example, about 20°C to about 100°C. Other embodiments include a temperature of about 30°C to about 90°C, for example, about 45°C or about 85°C. In other embodiments, the temperature is about 65°C to about 80°C, and other embodiments include maturation at two or more temperatures, for example, about 45°C and about 75°C to 85°C or about 80°C to 85°C.
[0159] Electrochemical modifiers can also be added to the polymer system by physical blending. Physical blending can include, but is not limited to, melt blending of polymers and / or copolymers, addition of discrete particles, chemical vapor deposition of electrochemical modifiers, and co-precipitation of electrochemical modifiers and primary polymer materials.
[0160] In another embodiment, the electrochemical modifier is a particle. The particles of the electrochemical modifier can be added with different particle size distributions. In one embodiment, the electrochemical modifier particles have a D50 of 10nm, or 50nm, or 100nm, or 150nm, or 200nm, or 500nm, or 1um, or 1.5um, or 2um, or 3um, or 5um, or 10um, or 20um, or 40um, or up to 50um, or up to 100um. In some embodiments, polymer and particle form a mixture. In other embodiments, the particle is covalently bonded to the polymer. In other embodiments, the particle is ionically bonded to the polymer. In some cases, the particle is silicon, and in other cases, the particle is different 14th group elements (Ge, Sn, Pb), 15th group elements (P, As, Sb), 16th group elements (S, Se, Te). In some cases, the particle comprises a single element, and in other cases, it comprises a mixture of two or more elements.
[0161] The electrochemical modifier particles can be dispersed in the organic polymer solution or prepolymer in various ways. In one embodiment, the particles are dispersed by ultrasonic treatment. In another embodiment, the particles are dispersed by mixing. In another embodiment, the particles are dispersed by changing the surface chemistry of the particles or the pH of the solution. In another embodiment, the particles are dispersed by using a surfactant. In one embodiment, the surfactant is SPAN 80. In one embodiment, the particles are dispersed in an emulsion or suspension. In one embodiment, the surfactant is used in combination with a hydrocarbon solvent. In one embodiment, the hydrocarbon is cyclohexane. In one embodiment, the hydrocarbon is a mineral oil. In another embodiment, the hydrocarbon is a vegetable oil.
[0162] In some cases, the electrochemical modifier can be added via a metal salt solution. The metal salt solution or suspension can include an acid and / or an alcohol to improve the solubility of the metal salt. In another variation, the polymer gel (before or after an optional drying step) is contacted with a slurry containing an electrochemical modifier. In another variation, the polymer gel (before or after an optional drying step) is contacted with a metal or metal oxide sol containing a desired electrochemical modifier.
[0163] In addition to the electrochemical modifiers exemplified above, the composite material may include one or more other forms (i.e., allotropes) of carbon. In this regard, it has been found that including different allotropes of carbon (e.g., graphite, amorphous carbon, diamond, C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene and / or carbon fiber) in the composite material is effective for optimizing the electrochemical properties of the composite material. Various allotropes of carbon can be incorporated into the carbon material during any stage of the preparation method described herein. For example, during the solution stage, during the gelation stage, during the curing stage, during the pyrolysis stage, during the grinding stage or after grinding. In some embodiments, the second carbon form is incorporated into the composite material by adding the second carbon form before or during the polymerization of the polymer gel as described in more detail herein. The polymer gel containing the polymerization of the second carbon form is then processed according to the general techniques described herein to obtain a carbon material containing the second allotrope of carbon.
[0164] In some embodiments, the organic polymer and the electrochemical modifier have different solvents, ratios of solvents, mixtures of solvents, catalyst types, catalyst ratios, solvent pH, types of acids or bases.
[0165] It is expected that the electrochemical modifier content of the final composite can be changed by changing the relative solid concentration of the carbon-containing polymer solution and / or the relative solid concentration of the polymer solution containing the electrochemical modifier. In one embodiment, the solid concentration of the organic polymer solution can be changed from 1% solid to 99% solid, or 10% solid to 90% solid, or 20% solid to 80% solid, or 20% solid to 50% solid, or 30% solid to 40% solid. In one embodiment, the solid concentration of the polymer solution is 35%. In one embodiment, the solid concentration of the electrochemical modifier polymer solution can be changed from 1% solid to 99% solid, or 10% solid to 90% solid, or 20% solid to 80% solid, or 20% solid to 50% solid, or 30% solid to 40% solid. In one embodiment, the solid concentration of the electrochemical modifier solution is 35%. In one embodiment, the electrochemical modifier is a TEOS polymer and is mixed with ethanol. In other embodiments, the TEOS polymer is mixed with acetone or isopropyl alcohol.
[0166] It is desirable to vary the ratio of the organic polymer to the electrochemical modifier polymer solution in any given mixture to vary the final ratio of carbon to electrochemical modifier in the final composite. In one embodiment, the ratio of the organic polymer to the electrochemical modifier polymer is about 10:1, or 9:1, or 8:1, or 7:1, or 6:1, or 5:1, or 4:1, or 3:1, or 2:1, or 1:1, or 1:2, or 1:3, or 1:4, or 1:5, or 1:6, or 1:7, or 1:8, or 1:9, or 1:10.
[0167] In one embodiment, the organic polymer / electrochemical modifier polymer solution is heated until a gel is formed. In one embodiment, the TEOS / RF solution is heated until a gel is formed. In one embodiment, the heating is performed in a sealed container. In one embodiment, the heating is performed in a polymer reactor. For example, a stirred polymer reactor. In one embodiment, the solution is heated in an emulsion, or in an inverse emulsion, or in a suspension. The temperature at which gelation occurs is known to affect the structure of the polymer and can be modified to control the structure of the final composite material. In one embodiment, the gel is formed at 40°C, or 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C, or 120°C, or 130°C. In one embodiment, the gel is formed in a two-step reaction. For example, the organic polymer is caused to gel at one temperature, and the electrochemical modifier polymer is caused to gel at a different temperature. In one embodiment, the two-step polymerization is carried out at 40°C, or 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C, or 120°C, or 130°C, and then the second step is carried out at 40°C, or 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C, or 120°C, or 130°C. In some embodiments, the organic polymer is completely gelled and then the electrochemical modifier polymer solution is added to dope the organic polymer by solvent exchange. In some embodiments, the electrochemical modifier polymer is completely gelled and then the organic polymer solution is added to dope the electrochemical modifier polymer by solvent exchange.
[0168] In some embodiments, the solvent portion in the reaction mixture is low, or the reaction can be substantially solvent-free. For example, the portion of the solvent in the reaction mixture can be less than 80% of the total mass of the reaction mixture, such as less than 70%, such as less than 60%, such as less than 50%, such as less than 40%, such as less than 30%, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 1%, such as less than 0.1%, such as less than 0.01%. Without being bound by theory, the yield of pyrolytic carbon from polymeric material can be about 50%. Therefore, the ratio of pyrolytic carbon produced per unit mass of processed polymer can be less than about 10, less than about 7, less than about 5, less than about 4, less than about 3, less than about 2.5, less than about 2.1. In some embodiments, the ratio of pyrolytic carbon produced per unit mass of processed polymer is about 2. In some embodiments, the ratio of pyrolytic carbon produced per unit mass of processed polymer is less than 2.
[0169] The pyrolytic carbon from a low solvent or substantially solvent-free reaction mixture can be activated, and the ratio of activated carbon to processed polymer is higher than the ratio of pyrolytic carbon to processed polymer, depending on the desired activation level. Without being bound by theory, the yield of activated carbon from pyrolytic carbon material can be about 50%. Therefore, the ratio of activated carbon produced per unit mass of processed polymer can be less than about 14, less than about 10, less than about 8, less than about 6, less than about 5, less than about 4.5, less than about 4.1. In some embodiments, the ratio of activated carbon produced per unit mass of processed polymer is about 4 or less.
[0170] The structure of the polymer precursor suitable for use in the low solvent or substantially solvent-free reaction mixture is not particularly limited, provided that the polymer precursor is capable of reacting with another polymer precursor or with a second polymer precursor to form a polymer. The polymer precursor includes amine-containing compounds, alcohol-containing compounds, and carbonyl-containing compounds, for example, in some embodiments, the polymer precursor is selected from alcohols, phenols, polyols, sugars, alkylamines, aromatic amines, aldehydes, ketones, carboxylic acids, esters, ureas, acyl halides, and isocyanates.
[0171] In one embodiment of a reaction mixture with low solvent or substantially no solvent, the method includes using a first polymer precursor and a second polymer precursor, and in some embodiments, the first polymer precursor or the second polymer precursor is a carbonyl-containing compound and the remaining first polymer precursor or the second polymer precursor is an alcohol-containing compound. In some embodiments, the first polymer precursor is a phenolic compound and the second polymer precursor is an aldehyde compound (e.g., formaldehyde). In one embodiment of the method, the phenolic compound is phenol, resorcinol, catechol, hydroquinone, phloroglucinol, or a combination thereof; and the aldehyde compound is formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, benzaldehyde, cinnamaldehyde, or a combination thereof. In other embodiments, the phenolic compound is resorcinol, phenol, or a combination thereof, and the aldehyde compound is formaldehyde. In other embodiments, the phenolic compound is resorcinol and the aldehyde compound is formaldehyde. In some embodiments, the polymer precursors are alcohols and carbonyl compounds (e.g., resorcinol and acetaldehyde), and they are present in a ratio of about 0.5:1.0, respectively.
[0172] Polymer precursor materials suitable for low solvent or substantially solvent-free reaction mixtures as disclosed herein include (a) alcohol compounds, phenolic compounds and other monohydroxy or polyhydroxy compounds and (b) aldehydes, ketones, and combinations thereof. In this article, representative alcohols include linear and branched, saturated and unsaturated alcohols. Suitable phenolic compounds include polyhydroxybenzenes, such as dihydroxybenzenes or trihydroxybenzenes. Representative polyhydroxybenzenes include meta-diphenol (i.e., 1,3-dihydroxybenzene), catechol, hydroquinone and phloroglucinol. In this regard, other suitable compounds are bisphenols, such as bisphenol A. Mixtures of two or more polyhydroxybenzenes may also be used. Phenol (monohydroxybenzene) may also be used. Representative polyhydroxy compounds include sugars, such as glucose, sucrose, fructose, chitin and other polyols, such as mannitol. In this article, aldehydes include: straight-chain saturated aldehydes, such as formaldehyde (methanal / formaldehyde), acetaldehyde (ethanal / acetaldehyde), propanal / propionaldehyde, butanal / butyraldehyde, etc.; straight-chain unsaturated aldehydes, such as vinyl ketone and other ketones, 2-propenal (propenal / acrylaldehyde), 2-butenal (crotonaldehyde), 3-butenal, etc.; branched saturated and unsaturated aldehydes; and aromatic aldehydes, such as benzaldehyde, salicylaldehyde, hydrocinnamaldehyde, etc. Suitable ketones include: straight-chain saturated ketones, such as acetone and 2-butanone, etc.; straight-chain unsaturated ketones, such as propenone, 2-butenone and 3-butenone (methyl vinyl ketone), etc.; branched saturated and unsaturated ketones; and aromatic ketones, such as methyl benzyl ketone (phenylacetone), ethyl benzyl ketone, etc. The polymer precursor material can also be a combination of the above-mentioned precursors.
[0173] In some embodiments, a polymer precursor in a low solvent or substantially solvent-free reaction mixture is an alcohol-containing substance, and another polymer precursor is a carbonyl-containing substance. The relative amount of the alcohol-containing substance (for example, alcohol, phenolic compound and monohydroxy or polyhydroxy compound or its combination) reacted with a carbonyl-containing substance (for example, aldehyde, ketone or its combination) can vary significantly. In some embodiments, the ratio of alcohol-containing substance and aldehyde substance is selected to make the total mole number of the reactive alcohol group in the alcohol-containing substance approximately the same as the total mole number of the reactive carbonyl group in the aldehyde substance. Similarly, the ratio of alcohol-containing substance and ketone substance can be selected to make the total mole number of the reactive alcohol group in the alcohol-containing substance approximately the same as the total mole number of the reactive carbonyl group in the ketone substance. When the carbonyl-containing substance comprises a combination of aldehyde substance and ketone substance, the same general 1:1 mol ratio is equally applicable.
[0174] In other embodiments, the polymer precursor in the low solvent or substantially solvent-free reaction mixture is a urea- or amine-containing compound. For example, in some embodiments, the polymer precursor is urea, melamine, hexamethylenetetramine (HMT) or a combination thereof. Other embodiments include polymer precursors selected from isocyanates or other reactive carbonyl compounds (e.g., acyl halides, etc.).
[0175] Some embodiments of the disclosed method include preparing a low solvent or solvent-free polymer gel (and carbon material) comprising an electrochemical modifier. Such electrochemical modifiers include, but are not limited to, nitrogen, silicon, and sulfur. In other embodiments, the electrochemical modifier includes fluorine, iron, tin, silicon, nickel, aluminum, zinc, or manganese. The electrochemical modifier can be included in any step of the preparation process. For example, in some, the electrochemical modifier is mixed with a mixture, a polymer phase, or a continuous phase.
[0176] The mixing of one or more polymer precursor components in the absence of solvent can be achieved by methods described in the art, such as ball milling, jet milling, Fritsch milling, planetary mixing, and other mixing methods for mixing or blending solid particles, while controlling process conditions (e.g., temperature). The mixing or blending process can be achieved before, during, and / or after (or a combination thereof) incubation at the reaction temperature.
[0177] Reaction parameters include aging the blended mixture at a temperature and time sufficient to react one or more polymer precursors with each other and form a polymer. In this regard, a suitable aging temperature is a temperature from about room temperature to a temperature that is or is close to the melting point of one or more polymer precursors. In some embodiments, a suitable aging temperature is a temperature from about room temperature to a temperature that is or is close to the glass transition temperature of one or more polymer precursors. For example, in some embodiments, the solvent-free mixture is aging at a temperature of about 20°C to about 600°C, for example, from about 20°C to about 500°C, for example, from about 20°C to about 400°C, for example, from about 20°C to about 300°C, for example, from about 20°C to about 200°C. In certain embodiments, the solvent-free mixture is aging at a temperature of about 50°C to about 250°C.
[0178] Porous carbon materials can be realized via the pyrolysis of polymers produced from precursor materials as described above. The temperature and residence time of pyrolysis can vary, for example, the residence time can vary from 1 min to 10 min, 10 min to 30 min, 30 min to 1 h, 1 h to 2 h, 2 h to 4 h, 4 h to 24 h. The temperature can vary, for example, the pyrolysis temperature can vary from 200 ° C to 300 ° C, 250 to 350 ° C, 350 ° C to 450 ° C, 450 ° C to 550 ° C, 540 ° C to 650 ° C, 650 ° C to 750 ° C, 750 ° C to 850 ° C, 850 ° C to 950 ° C, 950 ° C to 1050 ° C, 1050 ° C to 1150 ° C, 1150 ° C to 1250 ° C. Pyrolysis can be realized in an inert gas (such as nitrogen or argon). In some embodiments, an alternative gas is used, or a mixture of an inert gas (such as nitrogen) and an alternative gas. In this context, suitable alternative gases include, but are not limited to, carbon dioxide, carbon monoxide, water (steam), air, oxygen, and further combinations thereof.
[0179] The porous carbon particles may be subjected to particle size reduction prior to and / or after pyrolysis. Particle size reduction may be achieved by various techniques known in the art, such as by jet milling in the presence of various gases, including air, nitrogen, argon, helium, supercritical steam, and other gases known in the art. Other particle size reduction methods are also envisioned, such as milling, ball milling, jet milling, water jet milling, and other approaches known in the art.
[0180] In some embodiments, the surface area of the porous carbon material may comprise greater than 500 m 2 / g surface area, for example greater than 750m 2 / g, for example, greater than 1000m 2 / g, for example, greater than 1250m 2 / g, for example, greater than 1500m 2 / g, for example, greater than 1750m 2 / g, for example, greater than 2000m 2 / g, for example, greater than 2500m 2 / g, for example, greater than 3000m 2 In other embodiments, the surface area of the porous carbon material may be less than 500 m 2 In some embodiments, the surface area of the porous carbon material is 200 m 2 / g to 500m 2 In some embodiments, the surface area of the porous carbon material is 100 m 2 / g to 200m 2 / g. In some embodiments, the surface area of the porous carbon material is 50m 2 / g to 100m2 / g. In some embodiments, the surface area of the porous carbon material is 10m 2 / g to 50m 2 In some embodiments, the surface area of the porous carbon material may be less than 10 m 2 / g.
[0181] The pore volume of porous carbon materials is greater than 0.5 cm 3 / g, for example, greater than 0.6cm 3 / g, for example, greater than 0.7cm 3 / g, for example, greater than 0.8cm 3 / g, for example, greater than 0.9cm 3 / g, for example, greater than 1.0 cm 3 / g, for example, greater than 1.1cm 3 / g, for example, greater than 1.2cm 3 / g, for example, greater than 1.4cm 3 / g, for example, greater than 1.6cm 3 / g, for example, greater than 1.8cm 3 / g, for example, greater than 2.0cm 3 In other embodiments, the pore volume of the porous silicon material is less than 0.5 cm 3 , for example 0.1cm 3 / g to 0.5cm 3 In certain other embodiments, the pore volume of the porous silicon material is 0.01 cm 3 / g to 0.1cm 3 / g.
[0182] In some other embodiments, the porous carbon material comprises less than 1.0 g / cm 3 The tap density is less than 0.8 g / cm 3 , for example, less than 0.6 g / cm 3 , for example, less than 0.5 g / cm 3 , for example, less than 0.4 g / cm 3 , for example, less than 0.3 g / cm 3 , for example, less than 0.2 g / cm 3 , for example, less than 0.1 g / cm 3 .
[0183] The surface functionality of the porous carbon material can vary. One property of the surface functionality that can be predicted is the pH of the porous carbon material. The porous carbon materials disclosed herein comprise a pH value of less than 1 to about 14, such as less than 5, 5 to 8, or greater than 8. In some embodiments, the pH of the porous carbon is less than 4, less than 3, less than 2, or even less than 1. In other embodiments, the pH of the porous carbon is about 5 to 6, about 6 to 7, about 7 to 8, or 8 to 9 or 9 to 10. In other embodiments, the pH is high, and the pH of the porous carbon is greater than 8, greater than 9, greater than 10, greater than 11, greater than 12, or even greater than 13.
[0184] The pore volume distribution of the porous carbon scaffold can vary. For example, the micropore % can account for less than 30%, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 4%, such as less than 3%, such as less than 2%, such as less than 1%, such as less than 0.5%, such as less than 0.2%, such as less than 0.1%. In some embodiments, there is no detectable micropore volume in the porous carbon scaffold.
[0185] The mesopores that make up the porous carbon scaffold can vary. For example, the mesopore % can account for less than 30%, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 4%, such as less than 3%, such as less than 2%, such as less than 1%, such as less than 0.5%, such as less than 0.2%, such as less than 0.1%. In some embodiments, there is no detectable mesopore volume in the porous carbon scaffold.
[0186] In some embodiments, the pore volume distribution of the porous carbon scaffold material comprises greater than 50% macropores, such as greater than 60% macropores, such as greater than 70% macropores, such as greater than 80% macropores, such as greater than 90% macropores, such as greater than 95% macropores, such as greater than 98% macropores, such as greater than 99% macropores, such as greater than 99.5% macropores, such as greater than 99.9% macropores.
[0187] In certain preferred embodiments, the pore volume of the porous carbon scaffold comprises a blend of micropores, mesopores, and macropores. Thus, in certain embodiments, the porous carbon scaffold comprises 0-20% micropores, 30%-70% mesopores, and less than 10% macropores. In certain other embodiments, the porous carbon scaffold comprises 0-20% micropores, 0-20% mesopores, and 70%-90% macropores. In certain other embodiments, the porous carbon scaffold comprises 20%-50% micropores, 50%-80% mesopores, and 0-10% macropores. In certain other embodiments, the porous carbon scaffold comprises 40%-60% micropores, 40%-60% mesopores, and 0-10% macropores. In certain other embodiments, the porous carbon scaffold comprises 80%-95% micropores, 0-10% mesopores, and 0-10% macropores. In certain other embodiments, the porous carbon scaffold comprises 0-10% micropores, 30%-50% mesopores, and 50%-70% macropores. In certain other embodiments, the porous carbon scaffold comprises 0-10% micropores, 70%-80% mesopores, and 0-20% macropores. In certain other embodiments, the porous carbon scaffold comprises 0-20% micropores, 70%-95% mesopores, and 0-10% macropores. In certain other embodiments, the porous carbon scaffold comprises 0-10% micropores, 70%-95% mesopores, and 0-20% macropores.
[0188] In certain embodiments, to The pore volume % in the porous carbon scaffold with pores of (10nm to 100nm) comprises greater than 30% of the total pore volume, for example greater than 40% of the total pore volume, for example greater than 50% of the total pore volume, for example greater than 60% of the total pore volume, for example greater than 70% of the total pore volume, for example greater than 80% of the total pore volume, for example greater than 90% of the total pore volume, for example greater than 95% of the total pore volume, for example greater than 98% of the total pore volume, for example greater than 99% of the total pore volume, for example greater than 99.5% of the total pore volume, for example greater than 99.9% of the total pore volume.
[0189] In certain preferred embodiments, to The pore volume of the porous carbon scaffold with pores of 10 nm to 100 nm is greater than 0.1 cm 3 / g, for example, greater than 0.2cm 3 / g, for example, greater than 0.3cm 3 / g, for example, greater than 0.4cm 3 / g, for example, greater than 0.5cm 3 / g, for example, greater than 0.6cm 3 / g, for example, greater than 0.7cm 3 / g, for example, greater than 0.8cm3 / g, for example, greater than 0.9cm 3 / g, for example, greater than 1.0 cm 3 / g, for example, greater than 1.1cm 3 / g, for example, greater than 1.2cm 3 / g, for example, greater than 1.3cm 3 / g, for example, greater than 1.4cm 3 / g, for example, greater than 1.5cm 3 / g, for example, greater than 2.0cm 3 / g.
[0190] In certain preferred embodiments, the porous carbon support comprises a porous carbon support having a thickness greater than 0.5 cm 3 / g of total pore volume, and the macropore % is greater than 80%. In certain other embodiments, the porous carbon scaffold comprises a pore volume greater than 1.0 cm 3 / g of total pore volume, and the macropore % is greater than 90%. In certain preferred embodiments, the porous carbon support comprises a pore volume greater than 0.5 cm 3 / g total pore volume, and to The pore percentage is greater than 80%. In certain other preferred embodiments, the porous carbon support comprises a porous carbon support having a pore percentage greater than 1.0 cm 3 / g total pore volume, and to The pore % is greater than 90%.
[0191] The porous carbon support (i.e., carbon without an electrochemical modifier) can contain a majority (e.g., >50%) of the total pore volume belonging to pores of certain diameters. For example, in some embodiments, greater than 50%, greater than 60%, greater than 70%, greater than 80%, greater than 90%, or even greater than 95% of the total pore volume belongs to pores with a diameter of 1 nm or less. In other embodiments, greater than 50%, greater than 60%, greater than 70%, greater than 80%, greater than 90%, or even greater than 95% of the total pore volume belongs to pores with a diameter of 100 nm or less. In other embodiments, greater than 50%, greater than 60%, greater than 70%, greater than 80%, greater than 90%, or even greater than 95% of the total pore volume belongs to pores with a diameter of 0.5 nm or less.
[0192] In some embodiments, the tap density of the electrochemical modifier-free carbon can predict its ability to incorporate an electrochemical modifier and the resulting electrochemical performance, such as volumetric capacity. Although not limited in any way, the pore volume of the electrochemical modifier-free carbon can be related to its tap density, and electrochemical modifier-free carbon with low pore volume is sometimes found to have a high tap density (and vice versa). Therefore, a low tap density (e.g., <0.3 g / cc), a medium tap density (e.g., 0.3 g / cc to 0.5 g / cc), or a high tap density (e.g., >0.5 g / cc) of electrochemical modifier-free carbon is provided.
[0193] In some other embodiments, the carbon without electrochemical modifiers comprises a tap density greater than or equal to 0.3 g / cc. In some other embodiments, the carbon without electrochemical modifiers comprises a tap density of about 0.3 g / cc to about 0.5 g / cc. In some embodiments, the carbon without electrochemical modifiers comprises a tap density of about 0.35 g / cc to about 0.45 g / cc. In some other embodiments, the carbon without electrochemical modifiers comprises a tap density of about 0.30 g / cc to about 0.40 g / cc. In some embodiments, the carbon without electrochemical modifiers comprises a tap density of about 0.40 g / cc to about 0.50 g / cc. In some of the foregoing embodiments, the carbon without electrochemical modifiers comprises a medium total pore volume (e.g., about 0.1 cc / g to about 0.6 cc / g).
[0194] In some other embodiments, the carbon without electrochemical modifiers comprises a tap density greater than about 0.5 g / cc. In some other embodiments, the carbon without electrochemical modifiers comprises a tap density of about 0.50 g / cc to about 2.0 g / cc. In some other embodiments, the carbon without electrochemical modifiers comprises a tap density of about 0.5 g / cc to about 1.0 g / cc. In some embodiments, the carbon without electrochemical modifiers comprises a tap density of about 0.5 g / cc to about 0.75 g / cc. In some embodiments, the carbon without electrochemical modifiers comprises a tap density of about 0.75 g / cc to about 1.0 g / cc, such as about 0.75 g / cc to about 0.95 g / cc, such as about 0.75 g / cc to about 1.2 g / cc. In some of the foregoing embodiments, the carbon without electrochemical modifiers comprises a low, medium or high total pore volume.
[0195] The skeleton density measured by helium pycnometry can also characterize the density of the carbon without electrochemical modifier. In certain embodiments, the skeleton density of the carbon without electrochemical modifier is about 1g / cc to about 3g / cc, such as about 1.5g / cc to about 2.3g / cc. In other embodiments, the skeleton density is about 1.5cc / g to about 1.6cc / g, about 1.6cc / g to about 1.7cc / g, about 1.7cc / g to about 1.8cc / g, about 1.8cc / g to about 1.9cc / g, about 1.9cc / g to about 2.0cc / g, about 2.0cc / g to about 2.1cc / g, about 2.1cc / g to about 2.2cc / g, or about 2.2cc / g to about 2.3cc / g, about 2.3cc to about 2.4cc / g, for example, about 2.4cc / g to about 2.5cc / g.
[0196] In all cases, the properties of the carbon without the electrochemical modifier can be easily measured before the electrochemical modifier is incorporated. The properties of the carbon without the electrochemical modifier can also be measured by removing the electrochemical modifier afterwards. In the case of silicon, this can be easily achieved by dissolving the silicon in a solvent that does not affect the carbon and then measuring the properties of the carbon without the electrochemical modifier.
[0197] C. Introducing silicon into scaffold materials to create composite materials
[0198] Nano-scale silicon is difficult to handle and difficult to process in traditional electrodes. Due to the high surface area and the tendency to aggregate, uniform dispersion and coating require specific procedures and / or adhesive systems. In order to truly descend in replacing existing graphite anode materials, the next generation of Si-C materials needs to be micron-sized. In a preferred embodiment, the size distribution of the composite is relatively uniform, with an upper and lower limit in a preferred range, such as a Dv10 of not less than 5nm, a Dv50 of 500nm to 5um, and a Dv90 of not more than 50um. In certain embodiments, the composite particles are composed of the following size distribution: a Dv10 of not less than 50nm, a Dv50 of 1um to 10um, and a Dv90 of not more than 30um. In certain other embodiments, the composite particles are composed of the following size distribution: a Dv10 of not less than 100nm, a Dv50 of 2um to 8um, and a Dv90 of not more than 20um. In certain other embodiments, the composite particles consist of the following size distribution: Dv10 of no less than 250 nm, Dv50 of 4 um to 6 um, and Dv90 of no greater than 15 um.
[0199] Unlike existing composite materials that embed silicon within a large amount of inactive material, we understand that in order to achieve optimal performance, silicon needs room to expand and contract. Our high pore volume carbon is seen as a revelation, in which silicon is embedded or deposited, and does so in a designed manner, filling a desired range of pore volumes to produce an impregnated carbon material of a desired size range. Therefore, the template, such as a porous carbon material, plays an important role as a framework and an in-situ template for expansion and contraction, as well as contributing to the overall electronic and ion conducting capabilities of the composite particles. This scaffolding structure will allow the movement of electrons and possibly ions, but its main role is to simply attach the silicon to a single location, allowing it to expand and contract outwardly while retaining the pores lodged inside.
[0200] In certain embodiments, silicon is introduced into the porous carbon by nanoparticle impregnation. Thus, nanoscale silicon or nanoscale and nanofeatured silicon is first produced. In a preferred embodiment, nanoscale silicon or nanoscale and nanofeatured silicon is produced according to the methods described in US No. 62 / 205,542 "Nano-Featured Porous Silicon Materials", US No. 62 / 208,357 "Nano-Featured Porous Silicon Materials" and / or US No. 62 / 209,651 "Composites of Porous Nano-Featured Silicon Materials and Carbon Materials", the entire disclosure of which is incorporated herein by reference in its entirety for all purposes.
[0201] Porous carbon can be mixed with nano silicon, for example, in a stirred reaction vessel, wherein carbon particles (for example micron-sized porous carbon particles) are suspended together with nano silicon of a desired particle size. The suspension environment can vary as known in the art, for example, can be aqueous or non-aqueous. In certain embodiments, the suspension fluid can be multi-component, comprising miscible or immiscible co-solvents. Suitable co-solvents for aqueous (water) environments include but are not limited to acetone, ethanol, methanol and other substances known in the art. Various non-water-soluble environments are known in the art, and include but are not limited to heptane, hexane, cyclohexane, oil (for example mineral oil, vegetable oil) etc. Without being bound by theory, mixing in a reaction vessel causes silicon nano particles to be dispersed in porous carbon particles. Then, for example, the carbon particles of nano silicon impregnation obtained are harvested by centrifugation, filtration and subsequent drying (all known in the art).
[0202] To this end, porous carbon particles having the desired degree and type of porosity are subjected to processing that results in the production of silicon within the porosity. For this processing, the porous carbon particles can first be size reduced, for example to provide a Dv50 of 1 micron to 1000 microns, such as 1 micron to 100 microns, such as 1 micron to 50 microns, such as 1 micron to 20 microns, such as 1 micron to 15 microns, such as 2 microns to 12 microns, such as 5 microns to 10 microns. Particle size reduction can be performed as known in the art and as described elsewhere herein, for example by jet milling.
[0203] In a preferred embodiment, silicon is produced in the pores of the porous carbon by subjecting the porous carbon particles to silane gas at high temperature and in the presence of a silicon-containing gas (preferably silane) so as to achieve silicon deposition via chemical vapor deposition (CVD). The silane gas may be mixed with other inert gases (e.g., nitrogen). The temperature and time of the processing may vary, for example, the temperature may be 300° C. to 400° C., for example, 400° C. to 500° C., for example, 500° C. to 600° C., for example, 600° C. to 700° C., for example, 700° C. to 800° C., for example, 800° C. to 900° C. The mixture of gases may contain 0.1% to 1% of silane and the remaining inert gas. Alternatively, the mixture of gases may contain 1% to 10% of silane and the remaining inert gas. Alternatively, the mixture of gases may contain 10% to 20% of silane and the remaining inert gas. Alternatively, the mixture of gases may contain 20% to 50% of silane and the remaining inert gas. Alternatively, the mixture of gases may contain more than 50% silane and the remainder inert gas. Alternatively, the gas may be substantially 100% silane gas. The reactor in which the CVD process is carried out may be of various designs known in the art, such as a fluidized bed reactor, a static bed reactor, a lifting kiln, a rotary kiln, a box kiln or other suitable reactor type. Reactor materials are suitable for this task, as known in the art. In a preferred embodiment, the porous carbon particles are processed under conditions that provide uniform gas phase entry, such as a reactor in which the porous carbon particles are fluidized, or stirred by other means to provide said uniform gas entry.
[0204] In some embodiments, the CVD process is a plasma enhanced chemical vapor deposition (PECVD) process. The process is known in the art to deposit a thin film from a gaseous state (gas phase) to a solid state on a substrate. A chemical reaction is involved in the process, which occurs after a plasma of a reactive gas is generated. Plasma is usually generated by a DC discharge between RF (AC) frequencies or two electrodes, and the space between the electrodes is filled with a reactive gas. In certain embodiments, the PECVD process is used to coat porous carbon on a substrate suitable for this purpose, such as a copper foil substrate. PECVD can be performed at various temperatures, such as 300°C to 800°C, such as 300°C to 600°C, such as 300°C to 500°C, such as 300°C to 400°C, such as 350°C. The power can vary, such as 25W RF, and the silane gas flow required for processing can vary, and the processing time can vary as known in the art.
[0205] Regardless of the processing, it is contemplated that silicon impregnated into porous carbon has certain properties that are optimal for practical use as an energy storage material. For example, while not being bound by theory, the size and shape of the silicon can be varied accordingly to match the extent and nature of the pore volume within the porous carbon particles. For example, silicon can be impregnated into pores within porous carbon particles by CVD deposition or other appropriate processes, and the porous carbon particles comprise pore sizes of 5nm to 1000nm, such as 10nm to 500nm, such as 10nm to 200nm, such as 10nm to 100nm, such as 33nm to 150nm, such as 20nm to 100nm. Other ranges of carbon pore sizes with respect to partial pore volume, whether microporous, mesoporous or macroporous, are also contemplated in the present disclosure as described elsewhere.
[0206] The oxygen content in silicon can be less than 50%, such as less than 30%, such as less than 20%, such as less than 15%, such as less than 10%, such as less than 5%, such as less than 1%, such as less than 0.1%. In some embodiments, the oxygen content in silicon is 1% to 30%. In some embodiments, the oxygen content in silicon is 1% to 20%. In some embodiments, the oxygen content in silicon is 1% to 10%. In some embodiments, the oxygen content in porous silicon material is 5% to 10%.
[0207] In certain embodiments where the silicon contains oxygen, the oxygen is incorporated so that the silicon is present as a mixture of silicon and silicon oxide of the general formula SiOx, where x is a non-integer (real number) that can vary continuously from 0.01 to 2. In certain embodiments, the fraction of oxygen present on the surface of the nanofeatured porous silicon is higher compared to the interior of the particle.
[0208] In certain embodiments, silicon comprises crystalline silicon. In certain embodiments, silicon comprises polycrystalline silicon. In certain embodiments, silicon comprises micron polycrystalline silicon. In certain embodiments, silicon comprises nano polycrystalline silicon. In certain other embodiments, silicon comprises amorphous silicon. In certain other embodiments, silicon comprises crystalline silicon and amorphous silicon.
[0209] In certain embodiments, the carbon support to be impregnated or otherwise impregnated with silicon may include various carbon allotropes and / or geometric structures. To this end, the carbon support to be impregnated or otherwise impregnated with silicon may include graphite, nanographite, graphene, nanographene, conductive carbon (e.g., carbon black, carbon nanowires, carbon nanotubes, etc.) and combinations thereof.
[0210] In certain embodiments, a carbon scaffold impregnated or otherwise impregnated with silicon is removed to obtain a templated silicon material having desired dimensional characteristics. Removal of the scaffold carbon can be achieved as known in the art, for example by thermochemical activation under conditions where the silicon does not undergo undesirable changes in its electrochemical properties. Alternatively, if the scaffold is a porous polymer or other material soluble in a suitable solvent, the scaffold can be removed by dissolution.
[0211] D. Coating composite materials with carbon
[0212] Without being bound by theory, the electrochemical performance of the composite produced by silicon impregnation in the porous carbon material can be achieved by coating, for example, coating the composite material in the carbon layer. In this article, the surface layer can include a carbon layer as described in this section, or another suitable layer, such as a conductive polymer layer described in the subsequent section.
[0213] It is envisioned that the surface layer provides a suitable SEI layer. In this article, the surface carbon layer needs to be a good ion conductor to shuttle Li ions. Alternatively, the carbon layer may include an artificial SEI layer, for example, the carbon layer may include poly (3,4-ethylenedioxythiophene)-co-poly (ethylene glycol) copolymer. The coating may include nitrogen and / or oxygen functional groups to further improve the layer for promoting a stable SEI layer. The coating needs to provide sufficient conductivity, adhesion, and cohesion between particles. The surface should provide a stable SEI layer, which is generally composed of substances such as LiF, Li2CO3, and Li2O. Inorganic materials with relatively low bulk modulus can provide a more stable SEI layer, for example, a more amorphous layer is preferably preferred relative to a crystalline layer, for example, Li2CO3 is preferred relative to LiF.
[0214] To this end, a carbon layer may be applied to the silicon-impregnated carbon material. Without being bound by theory, such a carbon layer should provide a low surface area, a low surface roughness, and / or a low degree of morphological defects, all in order to provide a more stable SEI layer, a higher first cycle efficiency, and better cycle stability in a lithium-ion battery. Various carbon allotropes may be envisioned in providing a surface layer to the silicon-impregnated porous carbon material, including graphite, graphene, hard carbon, or soft carbon, such as pyrolytic carbon.
[0215] In alternative embodiments, the aforementioned coating can be achieved with a precursor solution known in the art, followed by a carbonization process. For example, the particles can be coated by the wurster method or related spray drying methods known in the art to coat a thin layer of the precursor material on the particles. The precursor coating can then be pyrolyzed, for example, by further fluidizing the wurster-coated particles at elevated temperature and in the presence of an inert gas, consistent with the description disclosed elsewhere herein.
[0216] In alternative embodiments, the particles can be covered in a carbonaceous layer realized by chemical vapor deposition (CVD). Without wishing to be bound by theory, it is believed that the CVD method of depositing a carbon layer (e.g., from a hydrocarbon gas) results in a graphitizable carbion (also referred to as "soft" carbon in the art). The method of CVD generally described in the art can be applied to composite materials disclosed herein, such as porous silicon particles, in which nanoscale or nanoscale and nano-featured silicon has been impregnated or otherwise introduced into the pore volume of the pore size of the desired range. CVD is generally achieved by subjecting the porous silicon material to high temperature in the presence of a suitable deposition gas containing carbon atoms. In this article, suitable gases include, but are not limited to, methane, propane, butane, cyclohexane, ethane, propylene and acetylene. The temperature may vary, for example, from 350°C to 1050°C, for example, from 350°C to 450°C, for example, from 450°C to 550°C, for example, from 550°C to 650°C, for example, from 650°C to 750°C, for example, from 750°C to 850°C, for example, from 850°C to 950°C, for example, from 950°C to 1050°C. The deposition time may vary, for example, from 0 min to 5 min, for example, from 5 min to 15 min, for example, from 15 min to 30 min, for example, from 30 min to 60 min, for example, from 60 min to 120 min, for example, from 120 min to 240 min. In some embodiments, the deposition time is greater than 240 min. In certain embodiments, the deposition gas is methane and the deposition temperature is greater than or equal to 950°C. In certain embodiments, the deposition gas is propane and the deposition temperature is less than or equal to 750°C. In certain embodiments, the deposition gas is cyclohexane and the deposition temperature is greater than or equal to 800°C.
[0217] In certain embodiments, the reactor itself can be stirred so that the porous carbon support is stirred to be silicon-impregnated. For example, the impregnation process can be carried out in a static mode, wherein the particles are not stirred and the silicon-containing reactant flows through, around or otherwise contacts the particles to be coated. In other exemplary modes, the particles can be fluidized, for example, the impregnation with the silicon-containing reactant can be carried out in a fluidized bed reactor. In this article, as known in the art, a variety of different reactor designs can be used, including but not limited to lifting kilns, roller bottom kilns, rotary kilns, box kilns and modified fluidized bed designs.
[0218] Thus, the present disclosure provides for the manufacture of composite silicon-carbon materials, wherein the carbon support material is a porous carbon material, and wherein silicon impregnation is achieved by contacting the porous carbon material with a silicon-containing reactant. For example, the method may include the following steps:
[0219] a) mixing a polymer and / or a polymer precursor and storing the polymer precursor for a period of time and at a temperature sufficient to polymerize the precursor,
[0220] b) carbonizing the resulting polymer material to produce a porous carbon material,
[0221] c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing reactant in a static reactor or a stirred reactor to produce a silicon-impregnated carbon material.
[0222] In another embodiment, the present disclosure provides for the manufacture of a composite silicon-carbon material, wherein the carbon support material is a porous carbon material, and wherein silicon impregnation is achieved by contacting with a silicon-containing reactant, and wherein the final carbon coating is achieved by contacting the composite with a carbon-containing reactant. For example, the method may include the following steps:
[0223] a) mixing a polymer and / or a polymer precursor and storing the polymer precursor for a period of time and at a temperature sufficient to polymerize the precursor,
[0224] b) carbonizing the resulting polymer material to produce a porous carbon material,
[0225] c) subjecting the porous carbon material to an elevated temperature in a static reactor or a stirred reactor in the presence of a silicon-containing reactant to produce a silicon-impregnated carbon material,
[0226] d) subjecting the silicon-impregnated carbon material to an elevated temperature in the presence of a carbon-containing reactant in a static reactor or a stirred reactor to produce a final carbon-coated silicon-carbon composite material.
[0227] In another embodiment, the present disclosure provides for the manufacture of a composite silicon-carbon material, wherein the carbon scaffold material is a porous carbon material, and wherein silicon impregnation is achieved by contacting with a silicon-containing reactant, and wherein a final conductive polymer coating is achieved by contacting the composite with a conductive polymer, and optionally pyrolyzing the material. For example, the method may include the following steps:
[0228] a) mixing a polymer and / or a polymer precursor and storing the polymer precursor for a period of time and at a temperature sufficient to polymerize the precursor,
[0229] b) carbonizing the resulting polymer material to produce a porous carbon material,
[0230] c) subjecting the porous carbon material to an elevated temperature in a static reactor or a stirred reactor in the presence of a silicon-containing reactant to produce a silicon-impregnated carbon material,
[0231] d) subjecting the silicon-impregnated carbon material to an elevated temperature in the presence of a conductive polymer in a static reactor or a stirred reactor to produce a final conductive polymer-coated silicon-carbon composite material,
[0232] e) The material of (d) may optionally be pyrolyzed.
[0233] The porous carbon composite material impregnated with silicon can also be finally coated with carbon via hot liquid carbonization, wherein the particles are processed according to various modes in the art. Hot liquid carbonization can be achieved in an aqueous environment at high temperature and pressure to obtain a silicon-carbon composite. The example variation of the temperature for achieving hot liquid carbonization is, for example, 150°C to 300°C, for example, 170°C to 270°C, for example, 180°C to 260°C, for example, 200°C to 250°C. Alternatively, hot liquid carbonization can be performed at a higher temperature, for example, 200°C to 800°C, for example, 300°C to 700°C, for example, 400°C to 600°C. In some embodiments, hot liquid carbonization can be performed at temperature and pressure to achieve a graphite structure. The pressure range suitable for hot liquid carbonization is known in the art, and the pressure can change (for example, increase) during the reaction. The pressure of hot liquid carbonization can be changed to 0.1MPa to 200MPA. In certain embodiments, the pressure of hot liquid carbonization is 0.5MPa to 5MPa. In other embodiments, the pressure of the hydrothermal carbonization is 1MPa to 10MPa or 5MPa to 20MPa. In other embodiments, the pressure of the hydrothermal carbonization is 10MPa to 50MPa. In other embodiments, the pressure of the hydrothermal carbonization is 50MPa to 150MPa. In other embodiments, the pressure of the hydrothermal carbonization is 100MPa to 200MPa. The raw materials suitable as the carbon source of the hydrothermal carbonization are also known in the art. Such raw materials of the hydrothermal carbonization generally comprise carbon and oxygen, and these include but are not limited to the polymer precursors described elsewhere in sugar, oil, biowaste, polymers and the present disclosure.
[0234] Thus, the present disclosure provides for the manufacture of composite silicon-carbon materials, wherein the carbon support material is a porous carbon material, and wherein silicon impregnation is achieved by contact with a silicon-containing reactant, and wherein the final carbon coating is achieved by hydrothermal carbonization. For example, the method may include the following steps:
[0235] a) mixing a polymer and / or a polymer precursor and storing the polymer precursor for a period of time and at a temperature sufficient to polymerize the precursor,
[0236] b) carbonizing the resulting polymer material to produce a porous carbon material,
[0237] c) subjecting the porous carbon material to an elevated temperature in the presence of a silicon-containing reactant in a static reactor or a stirred reactor to produce a silicon-impregnated carbon material,
[0238] d) subjecting the silicon-impregnated carbon material to hydrothermal carbonization to produce a silicon-impregnated carbon material comprising a final carbon coating via hydrothermal carbonization. Particles of silicon alloy are suspended in a liquid medium containing.
[0239] Without being bound by theory, it is important that the surface of the carbon particles achieve the desired temperature to achieve reaction with the silicon-containing gas and the desired degree of deposition. Conventional engineering principles dictate that it is difficult to heat the interior of a particle compared to the exterior of the particle, e.g., the particle is heated from the exterior surface via convection heating (or possibly other mechanisms, such as but not limited to microwave or radiative heating), and then the temperature within the particle is heated via conductive heating from the exterior to the interior of the carbon particle. It is not obvious that in the case of porous particles, the interior of the particle is heated simultaneously with the exterior, provided that the interior contains equal surface area for gas molecules to enter, collide with carbon on the particle surface and generate heat via convection.
[0240] Without being bound by theory, the reaction conditions may be such that the mean free path length of the silicon-containing gas is similar to or lower than the diameter and / or depth of the pores desired to be filled. Such situations are known in the art as being controlled by Knudsen diffusion, i.e., the average value of the diffusion occurring when measuring the length of the system is comparable to or smaller than the mean free path of the particles involved. It is believed that the gas molecules diffuse through very small capillary pores. If the pore size is smaller than the mean free path of the diffusing gas molecules, and the density of the gas is low, the gas molecules collide with the pore walls more frequently than with each other. This process is called Knudsen flow or Knudsen diffusion. The Knudsen number is a good measure of the relative importance of Knudsen diffusion. Knudsen numbers much greater than 1 indicate that Knudsen diffusion is important. In practice, Knudsen diffusion applies only to gases because the mean free path of liquid molecules is very small, typically close to the diameter of the molecules themselves. In cases where the pore size is much larger than the mean free path of the gas, the diffusion is characterized as Fisk diffusion.
[0241] The process is different for the deposition process, for example, it can be ambient pressure, or about 101 kPa. In some embodiments, the pressure can be less than ambient pressure, for example, less than 101 kPa, for example, less than 10.1 kPa, for example, less than 1.01 kPa. In some embodiments, the gas comprises a mixture of a silicon-containing deposition gas and an inert gas, such as a combination of silane and nitrogen. In this case, the partial pressure of the deposition gas can be less than 101 kPa, for example, less than 10.1 kPa, for example, less than 1.01 kPa. In some embodiments, the pressure and temperature are such that the silicon-containing gas is supercritical.
[0242] Thus, in certain embodiments, the silicon-containing reactant may be a supercritical silane, such as a silane at a temperature greater than about 270K (-3C) and a pressure greater than about 45 bar. In other embodiments, the silicon-containing reactant may be a supercritical silane, such as a silane at a temperature of 0°C to 100°C and a pressure of 45 bar to 100 bar. In other embodiments, the silicon-containing reactant may be a supercritical silane, such as a silane at a temperature of 100°C to 600°C and a pressure of 45 bar to 100 bar. In other embodiments, the silicon-containing reactant may be a supercritical silane, such as a silane at a temperature of 300°C to 500°C and a pressure of 50 bar to 100 bar. In other embodiments, the silicon-containing reactant may be a supercritical silane, such as a silane at a temperature of 400°C to 550°C and a pressure of 50 bar to 80 bar.
[0243] In certain embodiments, during the silicon impregnation process of the porous carbon support, both pressure and temperature are varied over time. For example, the porous carbon support can be maintained at a certain temperature and pressure, such as at or above ambient temperature, and at a pressure below ambient pressure. In this case, the combination of low pressure and high temperature allows volatile components to desorb, which can potentially block or otherwise occupy pores within the porous carbon support, thereby facilitating the entry of silicon-containing reactants. Examples of temperature and pressure conditions include, for example, 50°C to 900°C and 0.1 kPa to 101 kPa, and various combinations thereof. These conditions can be used as a first step in the presence of a non-silicon-containing reactant and then as a second condition of temperature and pressure in the presence of a silicon-containing reactant. Examples of the latter temperature and pressure ranges are found throughout this disclosure.
[0244] The CVD process can be realized via various modes according to this area. For example, CVD can be carried out in a static mode, wherein the particles are not stirred, and the CVD gas flows through, surrounds or otherwise penetrates the particles to be coated. In other exemplary modes, the particles can be fluidized, for example, CVD can be carried out in a fluidized bed reactor. In this article, as known in the art, various different reactor designs can be adopted, including but not limited to lifting kilns, roller bottom kilns, rotary kilns, box kilns and fluidized bed designs. These designs can be combined with various silicon-containing gases to be used as deposition gases, and the deposition gases include but are not limited to silane, disilane, trisilane, tetrasilane, chlorosilane, dichlorosilane, trichlorosilane and tetrachlorosilane.
[0245] In the case of a rotary kiln, various methods are known in the art to promote proper dispersion and tumbling of the particles within the reactor and provide maximum contact between the porous carbon and the silicon-containing reactant. These methods include equipment modifications such as elevators, helical flights, various screw and / or impeller designs, etc. Strategies for loading the rotary kiln with other non-reactive particles to promote dispersion and minimize agglomeration of the porous carbon scaffold particles are also known in the art.
[0246] The CVD process may also employ microwaves to achieve heating of the carbon particles to be processed. Thus, the above reactor configuration may also be combined with microwaves as part of the process, employing engineering design principles known in the art. Without being bound by theory, carbon particles are efficient microwave absorbers, and reactors may be envisioned in which the particles are subjected to microwaves to heat them prior to the introduction of a silicon-containing gas for deposition onto the particles.
[0247] E. Dielectric Heating
[0248] Dielectric heating is a process in which a high-frequency alternating electric field, radio waves or microwave electromagnetic radiation heats a dielectric material. Molecular rotation occurs in materials containing polar molecules (with electric dipole moments), with the result that they will align themselves in the electromagnetic field. If the field is oscillating, as it is in electromagnetic waves or in a rapidly oscillating electric field, these molecules continue to rotate by aligning them. This is called dipole rotation or dipole polarization. As the field alternates, the molecules reverse direction. The rotating molecules push, pull and collide with other molecules (through electric field forces), distributing energy to neighboring molecules and atoms in the material. Once distributed, this energy manifests as heat.
[0249] Temperature is related to the average kinetic energy (energy of motion) of the atoms or molecules in a material, so agitating the molecules in this way raises the temperature of the material. Dipole rotation is therefore a mechanism by which energy in the form of electromagnetic radiation can raise the temperature of an object. Dipole rotation is a mechanism generally known as dielectric heating, and is most widely observed in microwave ovens, where it operates most efficiently on liquid water, among other things, but much less so on fats and sugars and other carbon-containing materials.
[0250] Dielectric heating involves heating an electrically insulating material through dielectric losses. Changing the electric field across the material causes energy to be dissipated as the molecules try to align in the face of a continuously changing electric field. This changing electric field can be caused by electromagnetic waves propagating in free space (as in a microwave oven), or it can be caused by rapidly alternating the electric field inside a capacitor. In the latter case, there are no freely propagating electromagnetic waves, and the changing electric field can be viewed as analogous to the electrical component of an antenna's near field. In this case, although heating is achieved by changing the electric field within a capacitive cavity at radio frequency (RF) frequencies, no actual radio waves are generated or absorbed. In this sense, the action is a direct electrical analogue of magnetic induction heating, which is also a near-field effect (and therefore does not involve radio waves).
[0251] Frequencies in the 10 MHz to 100 MHz range are required to cause effective dielectric heating, and although higher frequencies work equally or better, lower frequencies also have significant heating effects in some materials (especially liquids), usually due to more unusual mechanisms. Dielectric heating at low frequencies requires the distance between the electromagnetic radiator and the absorber to be less than 1 / 2π≈1 / 6 of the wavelength due to the near-field effect. Therefore, since it usually causes the material to be heated in a sandwich manner between metal plates, it is a contact process or a near-contact process, and the metal plates replace the dielectric, in which case very large capacitors are effective. However, no actual electrical contact is required for heating the dielectric inside the capacitor, because the electric field formed inside the capacitor subjected to the voltage does not require the capacitor plates to be in electrical contact with the (non-conductive) dielectric material between the plates. Because the lower frequency electric field penetrates non-conductive materials much deeper than microwaves, heating water pockets and organisms deep inside dry materials (such as wood), it can be used to quickly heat and prepare many non-conductive foods and agricultural crops as long as they fit between the capacitor plates.
[0252] At very high frequencies, the wavelength of the electromagnetic field becomes shorter than the distance between the metal walls of the heating cavity or the dimensions of the walls themselves. This is the case inside a microwave oven. In such cases, conventional far-field electromagnetic wave forms (the cavity no longer acts as a pure capacitor, but as an antenna) are absorbed for causing heating, but the dipole rotation mechanism of heat deposition remains the same. However, microwaves are ineffective for causing thermal effects of low-frequency fields that depend on slower molecular motions, such as those caused by ion drag.
[0253] Microwave heating is a subclass of dielectric heating at frequencies greater than 100MHz, in which electromagnetic waves can be emitted from a small-sized transmitter and directed to a target through space. Modern microwave ovens use electromagnetic waves with electric fields of higher frequencies and shorter wavelengths than RF heaters. Typical household microwave ovens operate at 2.45GHz, but there are also 915MHz ovens. This means that the wavelength used in microwave heating is 12cm or 33cm (4.7in or 13.0in). This provides efficient, but less penetrating dielectric heating. Although a set of capacitor-like plates can be used at microwave frequencies, they are not necessary because microwaves already exist as far-field type electromagnetic radiation, and their absorption does not need to be as close to a small antenna as RF heating. Therefore, the material to be heated (non-metal) can be simply placed on the path of the wave, and heating occurs in a non-contact process.
[0254] Therefore, microwave absorbing materials are able to dissipate electromagnetic waves by converting them into heat energy. Without being bound by theory, the microwave absorption capacity of a material depends mainly on its relative dielectric constant, relative magnetic permeability, cell impedance matching and material microstructure, such as its porosity and / or nanostructure or microstructure. When a beam of microwaves irradiates the surface of a microwave absorbing material, the appropriate matching conditions of the electromagnetic impedance can make the reflectivity of the incident microwaves almost zero, ultimately resulting in the transfer of heat energy to the absorbing material.
[0255] F. Microwave Heating of Carbon Materials
[0256] Carbon materials are capable of absorbing microwaves, i.e., they are susceptible to heating by microwave radiation, i.e., infrared radiation and radio waves in the region of the electromagnetic spectrum. More specifically, they are defined as those waves having a wavelength of 0.001 m to 1 m, which corresponds to frequencies of 300 GHz to 0.3 GHz. The ability of carbon to be heated in the presence of a microwave field is defined by its dielectric loss tangent: tanδ=ε" / ε'. The dielectric loss tangent consists of two parameters, the dielectric constant (or real dielectric constant, ε') and the dielectric loss factor (or imaginary dielectric constant, ε"); i.e., ε=ε'-iε", where ε is the complex dielectric constant. The dielectric constant (ε') determines how much of the incident energy is reflected and how much is absorbed, while the dielectric loss factor measures the dissipation of electrical energy within the material in the form of heat. For optimal microwave energy coupling, a moderate ε' value should be combined with a high ε" value (and thus a high tanδ value) to convert microwave energy into thermal energy. Therefore, although some materials do not have a high enough loss factor to make the dielectric heated (transmitted by microwaves), other materials (such as some inorganic oxides and most carbon materials) are excellent microwave absorbers. On the other hand, electrical conductor materials reflect microwaves. For example, graphite and highly graphitized carbon can reflect a considerable portion of microwave radiation. In the case of carbon, other very interesting phenomena can occur when delocalized π electrons move freely in a relatively wide area. The kinetic energy of some electrons can increase so that they can jump out of the material, causing the surrounding atmosphere to ionize. At the macroscopic level, this phenomenon is seen as spark or arc formation. However, at the macroscopic level, these hot spots are actually plasmas. Most of the time, from a spatial and temporal point of view, these plasmas can be regarded as microplasmas because they are confined to a tiny spatial region and only last for a fraction of a second. The intensive generation of such microplasmas can have important implications for the processes involved.
[0257] Without being bound by theory, heating carbon materials by microwave heating offers many advantages over conventional heating, such as: (i) non-contact heating; (ii) energy transfer instead of heat transfer; (iii) rapid heating; (iv) selective material heating; (v) volumetric heating; (vi) rapid start and stop; (vii) heating from within the bulk of the material; and (viii) a higher level of safety and automation [3]. The high capacity of carbon materials to absorb microwave energy and convert it into heat is exemplified in Table 1 (provided by reference, JA Menéndez, A. Arenillas, B. Fidalgo, Y. Fernández, L. Zubizarreta, EG Calvo, JM Bermúdez, "Microwave heating processes involving carbon materials", Fuel Processing Technology, 2010, 91(1), 1-8), which lists the dielectric loss tangent of different carbon examples. It can be seen that the loss tangent of most carbons (except coal) is higher than the loss tangent of distilled water (tan δ = 0.118 at 2.45 GHz and room temperature).
[0258] Table 1. Examples of dielectric loss tangents of different carbon materials at a frequency of 2.45 GHz and room temperature.
[0259] Carbon Type tanδ=ε” / ε' coal 0.02-0.08 Carbon foam 0.05-0.20 charcoal 0.11-0.29 Carbon Black 0.35-0.83 Activated carbon 0.22-2.95 Carbon Nanotubes 0.25-1.14
[0260] Given the potential of carbon to absorb microwaves, there is also the possibility of microwave-enhanced carbon-catalyzed reactions or reactions occurring on or within carbon particles. Without being bound by theory, there are at least two situations where microwaves enhance such reactions on or within carbon particles: (i) reactions that require high temperatures, and (ii) reactions involving chemical compounds, such as organic compounds, that have low dielectric losses and do not heat up sufficiently under microwave radiation. With respect to the present invention, carbon materials serve as both reaction surfaces (e.g., catalysts) and microwave susceptors.
[0261] G. Microwaves can decompose the silicon-containing part on the porous carbon matrix to produce silicon-carbon composites
[0262] The present invention describes a method for synthesizing a composite material from one or more microwave absorbing materials, wherein the microwave absorbing material is heated by exposure to microwave radiation, and one or more other raw materials are introduced that are thermally decomposed on or inside the pores of the microwave heating material. In a preferred embodiment, the microwave heating material is porous, for example, containing micropores, mesopores or macropores or a combination thereof. In a preferred embodiment, the porous induction heating material is a carbon material. The porous microwave heating carbon material may be inherently capable of absorbing microwaves, or may be doped with a substance that otherwise causes the doped material to be capable of absorbing microwaves. The porous matrix material is heated locally by microwave heating of the matrix particles without directly heating other materials in the reactor system, such as containers, reactor walls, and the atmosphere (air) in the reactor. This local heating instead allows highly efficient and highly localized decomposition of silicon-containing reactant raw materials. In this regard, suitable reactant raw materials include, but are not limited to, silicon-containing gases and silicon-containing liquids. In a preferred embodiment, the silicon-containing raw material is silane gas. Therefore, the method disclosed herein provides advantages for producing uniform silicon composite particles.
[0263] In general, the present invention relates to composite materials in which silicon is deposited within the pore volume of a porous scaffold material, which is a microwave absorbing material. The porous microwave absorbing scaffold material can comprise a variety of different materials. In certain preferred embodiments, the porous scaffold material is a porous carbon material comprising micropores, mesopores and / or macropores. In particular, the porous carbon material provides pores of 5nm to 1000nm, which are subsequently filled with silicon. Therefore, the present disclosure also relates to a method for making a composite material in which silicon is deposited within the pore volume of a porous scaffold material. A schematic diagram of the method is shown in Figure 1 . The resulting composites exhibit significant and durable lithium intercalation, thereby providing optimal lithium storage and application properties. These novel composites find utility in a variety of electrical energy storage devices, such as as electrode materials in lithium-based electrical energy storage devices (e.g., lithium-ion batteries). Electrodes comprising the novel composites disclosed herein exhibit reversible capacity, high first cycle efficiency, high power performance, or any combination thereof. The present invention has found that such improved electrochemical performance is related to the size of the silicon, the integrity of the silicon and the carbon material during cycling, the formation of a stable SEI layer, the physicochemical properties of the scaffold material (e.g., the surface area and pore volume characteristics of the carbon scaffold), and the approach used to manufacture and mix the material.
[0264] Thus, in one embodiment, the present disclosure provides for the manufacture of novel composite materials with durable lithium intercalation, wherein the composite comprises a porous scaffold and silicon. For example, the method may include the following steps:
[0265] a) generating a porous scaffold material that absorbs microwaves, wherein the porous scaffold material that absorbs microwaves comprises a pore volume of 5 nm to 1000 nm;
[0266] b) heating the microwave absorbing porous scaffold material by microwaves in the presence of a silicon-containing feedstock to a temperature sufficient to enable decomposition of the silicon-containing feedstock to produce a silicon-impregnated carbon material.
[0267] Thus, in one embodiment, the present disclosure provides for the manufacture of novel composite materials with durable lithium intercalation, wherein the composite comprises carbon and silicon. For example, the method may include the following steps:
[0268] a) mixing polymer precursor materials and storing them at a temperature and for a period of time sufficient to polymerize the precursors;
[0269] b) carbonizing the resulting polymer material to produce a microwave absorbing porous carbon material comprising a pore volume of 5 nm to 1000 nm;
[0270] c) heating the microwave absorbing porous carbon material by microwaves in the presence of a silicon-containing feedstock to a temperature sufficient to enable decomposition of the silicon-containing feedstock to produce a silicon-impregnated carbon material.
[0271] In an alternative embodiment, the present disclosure provides for the manufacture of a novel composite material with durable lithium intercalation, wherein the composite comprises carbon and silicon doped with a microwave absorbing material. For example, the method may include the following steps:
[0272] a) mixing polymer precursor materials and storing them at a temperature and for a period of time sufficient to polymerize the precursors;
[0273] b) carbonizing the resulting polymer material to produce a porous carbon material comprising a pore volume of 5 nm to 1000 nm;
[0274] c) doping the porous carbon material with a material that can be heated by microwaves;
[0275] d) heating the resulting microwave absorbing porous carbon material by microwaves in the presence of a silicon-containing feedstock to a temperature sufficient to enable decomposition of the silicon-containing feedstock to produce a silicon-impregnated carbon material.
[0276] In a related alternative embodiment, the present disclosure provides for the manufacture of a novel composite material with durable lithium intercalation, wherein the composite comprises carbon and silicon produced from a polymer material containing a microwave absorbing material. For example, the method may include the following steps:
[0277] a) mixing a polymer precursor material in the presence of a microwave absorbing material and storing at a temperature and for a period of time sufficient to polymerize the precursor;
[0278] b) carbonizing the resulting polymer material to produce a porous microwave absorbing carbon material comprising a pore volume of 5 nm to 1000 nm;
[0279] c) heating the microwave absorbing porous carbon material by microwaves in the presence of a silicon-containing feedstock to a temperature sufficient to enable decomposition of the silicon-containing feedstock to produce a silicon-impregnated carbon material.
[0280] Thus, in one embodiment, the present disclosure provides for the manufacture of a novel composite material with durable lithium intercalation, wherein the composite comprises a carbon layer surrounding a silicon-impregnated carbon material. For example, the method may include the following steps:
[0281] a) mixing polymer precursor materials and storing them at a temperature and for a period of time sufficient to polymerize the precursors;
[0282] b) carbonizing the resulting polymer material to produce a microwave absorbing porous carbon material comprising a pore volume of 5 nm to 1000 nm;
[0283] c) heating the microwave absorbing porous scaffold material by microwaves in the presence of a silicon-containing feedstock to a temperature sufficient to enable decomposition of the silicon-containing feedstock to produce a silicon-impregnated carbon material;
[0284] d) coating a carbon layer on the silicon-impregnated carbon material to produce a carbon-coated, silicon-impregnated carbon material.
[0285] Thus, in one embodiment, the present disclosure provides for the manufacture of a novel composite material with durable lithium intercalation, wherein the composite comprises a conductive polymer layer surrounding a silicon-impregnated carbon material. For example, the method may include the following steps:
[0286] a) mixing polymer precursor materials and storing them at a temperature and for a period of time sufficient to polymerize the precursors;
[0287] b) carbonizing the resulting polymer material to produce a microwave absorbing porous carbon material comprising a pore volume of 5 nm to 1000 nm;
[0288] c) heating the microwave absorbing porous scaffold material by microwaves in the presence of a silicon-containing feedstock to a temperature sufficient to enable decomposition of the silicon-containing feedstock to produce a silicon-impregnated carbon material;
[0289] d) coating a conductive polymer around the silicon-impregnated carbon material to produce a silicon-impregnated carbon material further embedded within the conductive polymer network.
[0290] Thus, the present disclosure provides novel compositions of matter and, among other things, methods of making the same, wherein the materials exhibit remarkably durable lithium intercalation when incorporated into electrodes of lithium-based energy storage devices. In some embodiments, the lithium-based electrical energy storage device is a lithium-ion battery or a lithium-ion capacitor.
[0291] H. Coating the Composite Material with a Conductive Polymer Material
[0292] The composite material comprising the porous silicon material may include various surface treatments or properties to further improve the electrochemical performance defined by capacity, stability and power performance. In one embodiment, the composite is covered with an ion conductive polymer having a thickness of 1 nm to 10 μm. In another embodiment, the composite is covered with a ceramic protective coating having a thickness of 1 nm to 10 μm. In another embodiment, the composite is covered with an organic film having a thickness of 1 nm to 10 μm. The thickness can be measured using various techniques known in the art, such as, but not limited to, XPS sputtering, FIB / SEM or SIMS.
[0293] The composite material can be coated with an ion conducting polymer. Example materials include, but are not limited to, polyaniline based materials, polypyrrole based materials, combinations of the two such as polypyrrole-co-aniline, polythiophene based materials, oligomers, PEDOT-PSS, polyvinylidene chloride and other vinylides and fluorides, neoprene, silicone, polyurethane, styrene-butadiene rubber based materials and other rubbers such as isoprene.
[0294] The composite material may be coated with a ceramic protective coating. Coating materials include, but are not limited to, oxide type coatings such as aluminum oxide, titanium dioxide, zirconium oxide, and chromium oxide. Coating materials may also be oxygen-free such as carbides, nitrides, borides, and silicides. The purpose of the ceramic is to protect the surface of the composite material.
[0295] The composite material can be coated with an organic material. The organic material can be found in nature or synthesized by synthesis. Examples of organic coating materials include, but are not limited to, lignin, cellulose, chitosan, polysaccharides, and lipids.
[0296] The act of coating particles is easily accomplished by those skilled in the art. Commonly used methods include vapor deposition methods (e.g., atomic layer deposition, chemical vapor deposition and plasma assisted deposition, physical vapor deposition), sputtering methods, spray drying, emulsions, spin coating, electrodeposition, and direct particle selective growth by seeding or other means.
[0297] The coating on the composite material is intended to prevent corrosion and provide mechanical stability during expansion and contraction. For this reason, the hardness and elasticity of the material are crucial. These hardness and elasticity values can be measured using methods known in the art. Depending on the choice of material, the Mohs hardness of the coating can be 0 to 10. Without being bound by theory, the Mohs hardness of the coating can be 0 to 5, 0 to 4, 0 to 3, 0 to 2 and 0 to 1. In another example, the Mohs hardness of the coating can be 5 to 10, 6 to 10, 7 to 10, 8 to 10 and 9 to 10. In the case of the limit, the coating can show a generally high Mohs hardness>10. Without being bound by theory, the hardness can also be measured using the Vickers metric instead of the Mohs metric.
[0298] In another embodiment, the Young's modulus of the coating can be measured at 0 to 1210 GPa. In one embodiment, the Young's modulus of the coating is 0.01 GPa to 11 GPa, 0.01 GPa to 5 GPa, 0.01 GPa to 2 GPa, 0.01 GPa to 0.5 GPa, 0.01 GPa to 0.1 GPa, and 1 GPa to 4 GPa. In another example, the Young's modulus of the coating can be greater than 11. The Young's modulus of the coating is 11 GPa to 1000 GPa, 20 GPa to 1000 GPa, 50 GPa to 1000 GPa, 100 GPa to 1000 GPa, 200 GPa to 1000 GPa, and 400 GPa to 700 GPa.
[0299] The thickness of the coating can change the performance of the composite material and can be directly related to the physical properties of the coating. In one embodiment, the thickness of the coating is 1 nm to 10 μm, 1 nm to 5 μm, 1 nm to 1 μm, 1 nm to 50 nm. In another embodiment, the thickness of the coating is 5 μm to 10 μm. In another embodiment, the coating is a single atomic monolayer.
[0300] The coating mass can vary relative to the composite particle mass, depending on the properties of the coating and the composite particles. Without being bound by theory, the ratio of the coating mass to the composite particle mass can change the weight capacity and volume capacity of the material. In this embodiment, the composite particle mass refers to any and all materials that are not considered to be conductive polymers or ceramic coatings. In one embodiment, the ratio of the coating mass to the composite particle mass is less than 1:50. In another embodiment, the ratio of the coating mass to the composite particle mass is 1:50 to 1:1, 1:50 to 1:5, 1:50 to 1:10, 1:50 to 1:20, 1:20 to 1:30. In another embodiment, the ratio of the coating mass to the composite particle mass exceeds 1:1, indicating that there is more coating than composite material.
[0301] The coating volume can vary relative to the composite particle volume, depending on the properties of the coating and the composite particle. Without being bound by theory, the ratio of the coating volume to the composite particle volume can change the weight capacity and volume capacity of the material. In this embodiment, the composite particle volume refers to any and all materials that are not considered to be conductive polymers or ceramic coatings. In one embodiment, the ratio of the coating volume to the composite particle volume is less than 1:50. In another embodiment, the ratio of the coating volume to the composite particle volume is 1:50 to 1:1, 1:50 to 1:5, 1:50 to 1:10, 1:50 to 1:20, 1:20 to 1:30. In another embodiment, the ratio of the coating volume to the composite particle volume exceeds 1:1, indicating that there is more coating than composite material.
[0302] The oxygen content in the coating on the composite material may be less than 80%, such as less than 70%, such as less than 60%, such as less than 50%, such as less than 40%, such as less than 30%, such as less than 20%, such as less than 10%. In certain embodiments, the oxygen content in the coating on the composite material is 10% to 80%. In certain embodiments, the oxygen content in the coating on the composite material is 20% to 70%. In certain embodiments, the oxygen content in the coating on the composite material is 30% to 60%. In certain embodiments, the oxygen content in the coating on the composite material is 40% to 50%. In other embodiments, the oxygen content in the coating on the composite material is less than 10%.
[0303] The nitrogen content in the coating on the composite material may be less than 50%, such as less than 30%, such as less than 20%, such as less than 15%, such as less than 10%, such as less than 5%, such as less than 1%, such as less than 0.1%. In certain embodiments, the nitrogen content in the coating on the composite material is 1% to 30%. In certain embodiments, the nitrogen content in the coating on the composite material is 1% to 20%. In certain embodiments, the nitrogen content in the coating on the composite material is 1% to 10%. In certain embodiments, the nitrogen content in the coating on the composite material is 5% to 10%.
[0304] In certain embodiments, the conductive polymer is pyrolyzed to achieve a pyrolyzed conductive polymer coating. There are various embodiments whereby the conductive polymer can be added as a second carbon composite having nano-featured silicon and / or nano-scale and nano-featured silicon impregnated into a carbon support. For example, the silicon-carbon composite can be suspended in a solvent containing a dissolved conductive polymer, and then the suspension can be dried as known in the art. In alternative embodiments, solid particles of the conductive polymer can be mixed with solid silicon particles, and the mixture of particles is stored at high temperatures. In preferred embodiments, the temperature is close to or above the glass transition temperature of the polymer. In other preferred embodiments, the temperature is close to or above the softening temperature of the polymer. In other preferred embodiments, the temperature is close to or above the melting temperature of the polymer. The high temperature can be about 100°C, or about 120°C, or about 140°C, or about 160°C, or about 180°C, or about 200°C. The pyrolysis can be carried out at an elevated temperature known in the art, such as 300° C., or 350° C., or 400° C., or 450° C., or 500° C., or 600° C., or 700° C., or 800° C. In certain embodiments, nanofeatured silicon or a mixture of nanofeatured and nanoscale silicon can be pyrolyzed at 850° C., 900° C., 1000° C., 1050° C., or 1100° C. Exemplary conductive polymers include, but are not limited to, polyacrylonitrile (PAN), polyaniline, polypyrrole, polyacetylene, polyphenylene, polyphenylene sulfide, polythiophene, polyfluorene, polypyrene, polyazulene, polynaphthalene, polycarbazole, polyindole, polyazepine, poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylene sulfide) (PPS), poly(p-phenylene vinylene) (PPV), and mixtures thereof. The ratio of nanofeatured silicon or nanofeatured and nanoscale silicon to conductive polymer can vary, for example, from 95:5 to 9:95. In certain embodiments, the ratio of silicon to conductive polymer is from 95:5 to 60:40 or from 90:10 to 70:30.
[0305] In another embodiment, the present disclosure provides the manufacture of a composite silicon-carbon material, wherein the silicon material is a nanoscale silicon material or a nanoscale silicon material with nanoscale features, which is impregnated in a carbon support according to a method generally as described herein, and the resulting silicon-carbon composite is coated with a second carbon coating, wherein the second carbon coating is achieved via coating with a conductive polymer. In certain embodiments, the conductive polymer is pyrolyzed to achieve a pyrolyzed conductive polymer coating. There are various embodiments, whereby the conductive polymer can be composited with nano-featured silicon and / or nano-featured silicon and carbon composites. For example, the silicon-carbon composite can be suspended in a solvent containing a dissolved conductive polymer, and then the suspension can be dried as known in the art. In alternative embodiments, solid particles of the conductive polymer can be mixed with solid silicon-carbon composite particles, and the mixture of particles is stored at high temperature. In preferred embodiments, the temperature is close to or above the glass transition temperature of the polymer. In other preferred embodiments, the temperature is close to or above the softening temperature of the polymer. In other preferred embodiments, the temperature is close to or above the melting temperature of the polymer. The high temperature can be about 100° C., or about 120° C., or about 140° C., or about 160° C., or about 180° C., or about 200° C. Pyrolysis can be performed at high temperatures known in the art, such as 300° C., or 350° C., or 400° C., or 450° C., or 500° C., or 600° C., or 700° C., or 800° C. In certain embodiments, nanofeatured silicon or a mixture of nanofeatured and nanoscale silicon can be pyrolyzed at 850° C., 900° C., 1000° C., 1050° C., or 1100° C. Exemplary conductive polymers include, but are not limited to, polyacrylonitrile (PAN), polyaniline, polypyrrole, polyacetylene, polyphenylene, polyphenylene sulfide, polythiophene, polyfluorene, polypyrene, polyazulene, polynaphthalene, polycarbazole, polyindole, polyazepine, poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylene sulfide) (PPS), poly(p-phenylene vinylene) (PPV), and mixtures thereof. The ratio of nano-featured silicon or nano-featured and nano-scale silicon and carbon composites to the conductive polymer can vary, for example, from 95:5 to 9:95. In certain embodiments, the ratio of the composite to the conductive polymer is from 95:5 to 60:40 or from 90:10 to 70:30. I. Electrochemical performance of composites with extremely durable lithium intercalation
[0306] As described above, the present disclosure relates to composite materials comprising a core of a porous carbon support, nano-silicon impregnated or otherwise introduced via CVD in the presence of silane gas on the porous carbon support, or with other suitable techniques, under an optional final coating, such as carbon achieved via CVD in the presence of propane, or other suitable techniques, or coated with a conductive polymer. Such composites exhibit extremely durable lithium insertion and are therefore highly useful as anode materials in lithium-based (or sodium-based) and other electrical storage devices. Although not wishing to be bound by theory, it is believed that due to filling in the pore volume structure of certain desired porous carbon supports (e.g., silicon fills pores of 5nm to 1000nm or other ranges disclosed elsewhere herein), together with the favorable properties of other components of the composite, including carbon or conductive polymer coatings, and at least in part, nano-scale silicon achieved by changes in its preparation methods and preparation parameters produces composite materials with different favorable properties, such as electrochemical performance when the composite comprises an anode of a lithium-ion energy storage device.
[0307] In certain embodiments, the electrochemical performance of the composites disclosed herein is tested in half-cells; or the performance of the composites with extremely durable lithium intercalation disclosed herein is tested in full cells, such as full-cell button cells, full-cell pouch cells, square cells, or other battery configurations known in the art. The anode composition comprising the composites with extremely durable lithium intercalation disclosed herein may also include various substances, as known in the art. Other formulation components include, but are not limited to, conductive additives, such as conductive carbons, such as Super P, Ketjenblack carbon, etc., conductive polymers, etc., binders, such as styrene-butadiene rubber sodium carboxymethylcellulose (SBR-Na CMC), polyvinylidene fluoride (PVDF), etc., and combinations thereof. Electrodes of various types and containing substances are known in the art. The weight % of active material in the electrode can vary, for example, 1% to 5%, for example, 5% to 15%, for example, 15% to 25%, for example, 25% to 35%, for example, 35% to 45%, for example, 45% to 55%, for example, 55% to 65%, for example, 65% to 75%, for example, 75% to 85%, for example, 85% to 95%. In a preferred embodiment, the active material accounts for 80% to 95% of the electrode. In certain embodiments, the amount of conductive additive in the electrode can vary, for example, 1% to 5%, 5% to 15%, for example, 15% to 25%, for example, 25% to 35%. In a preferred embodiment, the amount of conductive additive in the electrode is 5% to 25%. In certain embodiments, the amount of binder can vary, for example, 1% to 5%, 5% to 15%, for example, 15% to 25%, for example, 25% to 35%. In certain embodiments, the amount of conductive additive in the electrode is 5% to 25%.
[0308] Composites with extremely durable lithium intercalation disclosed herein improve the properties of many electrical energy storage devices, for example, composites with extremely durable lithium intercalation disclosed herein have been shown to improve the first cycle efficiency of lithium-based batteries. Thus, one embodiment of the present disclosure provides a composite with extremely durable lithium intercalation disclosed herein, wherein when the material is incorporated into an electrode of a lithium-based energy storage device (e.g., a lithium-ion battery), the material has a first cycle efficiency greater than 50%. For example, some embodiments provide a composite with extremely durable lithium intercalation disclosed herein, wherein the lithium has a first cycle efficiency greater than 50%. 2 / g surface area, wherein when the carbon material is incorporated into a lithium-based energy storage device, the carbon material has a first cycle efficiency greater than 50% and a reversible capacity of at least 600 mAh / g. In other embodiments, the first cycle efficiency is greater than 55%. In some other embodiments, the first cycle efficiency is greater than 60%. In other embodiments, the first cycle efficiency is greater than 65%. In other embodiments, the first cycle efficiency is greater than 70%. In other embodiments, the first cycle efficiency is greater than 75%, and in other embodiments, the first cycle efficiency is greater than 80%, greater than 90%, greater than 95%, greater than 98%, or greater than 99%.
[0309] The silicon-carbon composite material can be pre-lithiated, as known in the art. In certain embodiments, pre-lithiation is achieved electrochemically, for example in a half-cell, before assembling a lithiated anode comprising a porous silicon material into a full-cell lithium-ion battery. In certain embodiments, pre-lithiation is achieved by doping the cathode with a lithium-containing compound (e.g., a lithium-containing salt). In this article, examples of suitable lithium salts include, but are not limited to, dilithium tetrabromonickelate (II), dilithium tetrachlorocuprate (II), lithium azide, lithium benzoate, lithium bromide, lithium carbonate, lithium chloride, lithium cyclohexanebutyrate, lithium fluoride, lithium formate, lithium hexafluoroarsenate (V), lithium hexafluorophosphate, lithium hydroxide, lithium iodate, lithium iodide, lithium metaborate, lithium perchlorate, lithium phosphate, lithium sulfate, lithium tetraborate, lithium tetrachloroaluminate, lithium tetrafluoroborate, lithium thiocyanate, lithium trifluoromethanesulfonate, lithium trifluoromethanesulfonate, and combinations thereof.
[0310] Anodes comprising silicon-carbon composite materials can be paired with various cathode materials to produce full-cell lithium-ion batteries. Examples of suitable cathode materials are known in the art. Examples of such cathode materials include, but are not limited to, LiCoO2 (LCO), LiNi 0.8 Co 0.15 Al 0.05 O2(NCA), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NMC), LiMn2O4 and variants (LMO), and LiFePO4 (LFP).
[0311] For a full-cell lithium-ion battery comprising an anode (also comprising a silicon-carbon composite material), the pairing of the cathode and the anode can vary. For example, the ratio of the cathode capacity to the anode capacity can vary from 0.7 to 1.3. In certain embodiments, the ratio of the cathode capacity to the anode capacity can vary from 0.7 to 1.0, such as 0.8 to 1.0, such as 0.85 to 1.0, such as 0.9 to 1.0, such as 0.95 to 1.0. In other embodiments, the ratio of the cathode capacity to the anode capacity can vary from 1.0 to 1.3, such as 1.0 to 1.2, such as 1.0 to 1.15, such as 1.0 to 1.1, such as 1.0 to 1.05. In other embodiments, the ratio of the cathode capacity to the anode capacity can vary from 0.8 to 1.2, such as 0.9 to 1.1, such as 0.95 to 1.05.
[0312] For a full-cell lithium-ion battery comprising an anode (also comprising a silicon-carbon composite material), the voltage window for charging and discharging can vary. In this regard, the voltage window can vary as known in the art, depending on the various properties of the lithium-ion battery. For example, the choice of cathode plays a role in the selected voltage window, as known in the art. In terms of potential relative to Li / Li+, examples of voltage windows vary, for example, from 2.0V to 5.0V, such as 2.5V to 4.5V, such as 2.5V to 4.2V.
[0313] For a full-cell lithium-ion battery comprising an anode that also comprises a silicon-carbon composite material, the strategy for conditioning the battery can vary as is known in the art. For example, conditioning can be achieved by performing one or more charge and discharge cycles at various rates, such as at a rate slower than the desired cycle rate. As is known in the art, the conditioning process can also include the steps of unsealing the lithium-ion battery, evacuating any gases generated during the conditioning process, and then resealing the lithium-ion battery.
[0314] For a full-cell lithium-ion battery comprising an anode (also comprising a silicon-carbon composite material), the cycle rate can be varied as known in the art, for example, the rate can be C / 20 to 20C, such as C10 to 10C, such as C / 5 to 5C. In certain embodiments, the cycle rate is C / 10. In certain embodiments, the cycle rate is C / 5. In certain embodiments, the cycle rate is C / 2. In certain embodiments, the cycle rate is 1C. In certain embodiments, the cycle rate is 1C, and the rate is periodically reduced to a slower rate, such as cycling at 1C with a C / 10 rate for every 20 cycles. In certain embodiments, the cycle rate is 2C. In certain embodiments, the cycle rate is 4C. In certain embodiments, the cycle rate is 5C. In certain embodiments, the cycle rate is 10C. In certain embodiments, the cycle rate is 20C.
[0315] In some of the foregoing embodiments, the composites having the extremely durable lithium intercalation disclosed herein further comprise about 5 m 2 / g to about 400m 2 / g surface area or about 0.05cc / g to about 1.0cc / g pore volume or both. For example, in some embodiments, the surface area is about 200m 2 / g to about 300m 2 / g, or a surface area of about 250m 2 / g.
[0316] In some embodiments, the composites having the extremely durable lithium intercalation disclosed herein have a 2 / g surface area, for example, less than 100m 2 / g, for example, less than 50m 2 / g. In other embodiments, the composite material has a 2 / g surface area, for example, less than 20m 2 / g, for example, less than 10m 2 / g, for example, less than 5m 2 / g, for example, less than 2m 2 / g, for example, less than 1m 2 / g.
[0317] In other embodiments, the composites having the extremely durable lithium intercalation disclosed herein have a density of less than 50 m 2 / g surface area, for example less than 20m 2 / g, for example, less than 10m 2 / g, for example, less than 5m 2 / g, for example, less than 1m 2 / g, and wherein when the material is incorporated into a lithium-based energy storage device, the first cycle efficiency is greater than 50% and the reversible capacity is at least 600 mAh / g. In other embodiments, the first cycle efficiency is greater than 55%. In some other embodiments, the first cycle efficiency is greater than 60%. In other embodiments, the first cycle efficiency is greater than 65%. In other embodiments, the first cycle efficiency is greater than 70%. In other embodiments, the first cycle efficiency is greater than 75%, and in other embodiments, the first cycle efficiency is greater than 80%, greater than 90%, greater than 95%, greater than 98%, or greater than 99%. In some of the foregoing embodiments, the composite material also includes about 1m 2 / g to about 400m 2 / g surface area or about 0.01cc / g to about 1.0cc / g pore volume or both. For example, in some embodiments, the surface area is about 200m 2 / g to about 300m 2 / g, or a surface area of about 250m 2 / g.
[0318] The electrochemical properties (e.g., first cycle efficiency, capacity, etc.) of the extremely durable lithium intercalation composite disclosed herein can be determined by incorporating electrodes, which are known to those skilled in the art. The composite is tested electrochemically. The test method can vary depending on the electrode composition, as known in the art. In one example, pure silicon is tested at an upper voltage of 1.0V and a lower voltage of 10mV with a current of 400mA / g after two formation cycles between 1.0V and 70mV with a current of 200mA / g relative to the mass of the composite material. Alternatively, the composite material is tested by limiting the capacity at a predefined value and measuring the stability and voltage fluctuation of the composite.
[0319] Prior to pre-lithiation modification, the first cycle efficiency of the composite with extremely durable lithium insertion disclosed herein is determined by comparing the lithium inserted into the anode during the first cycle with the lithium extracted from the anode in the first cycle. When the insertion and extraction are equal, the efficiency is 100%. As is known in the art, the anode material can be tested in a half-cell, where the counter electrode is lithium metal, the electrolyte is 1M LiPF6 1:1 ethylene carbonate: diethyl carbonate (EC: DEC), and a commercial polypropylene separator is used. In certain embodiments, the electrolyte may include various additives known to provide improved performance, such as fluoroethylene carbonate (FEC) or other related fluorinated carbonate compounds, or ester co-solvents, such as methyl butyrate, vinylene carbonate, and other electrolyte additives known to improve the electrochemical performance of silicon-containing anode materials.
[0320] When tested in a half-cell, the coulombic efficiency can be averaged, for example, over 7 cycles to 25 cycles. In certain embodiments, the average efficiency of the composite with extremely durable lithium intercalation is greater than 0.9 or 90%. In certain embodiments, the average efficiency is greater than 0.95 or 95%. In preferred embodiments, the average efficiency is greater than 0.98 or 98%. In other preferred embodiments, the average efficiency is greater than 0.99 or 99%. In other preferred embodiments, the average efficiency is greater than 0.991 or 99.1%. In other preferred embodiments, the average efficiency is greater than 0.992 or 99.2%. In other preferred embodiments, the average efficiency is greater than 0.993 or 99.3%. In other preferred embodiments, the average efficiency is greater than 0.994 or 99.4%. In other preferred embodiments, the average efficiency is greater than 0.995 or 99.5%. In other preferred embodiments, the average efficiency is greater than 0.996 or 99.6%. In other preferred embodiments, the average efficiency is greater than 0.997 or 99.7%. In other preferred embodiments, the average efficiency is greater than 0.998 or 99.8%. In other preferred embodiments, the average efficiency is greater than 0.999 or 99.9%. In other preferred embodiments, the average efficiency is greater than 0.9999 or 99.99%.
[0321] In another embodiment, the present disclosure provides a composite material with extremely durable lithium insertion, wherein when the material is incorporated into an electrode of a lithium-based energy storage device (e.g., a lithium-ion battery), the composite has a volumetric capacity (i.e., reversible capacity) of at least 400 mAh / cc that is independent of an alloy electrochemical modifier. The volumetric capacity of the composite can be calculated by multiplying the maximum weight capacity (mAh / g) by the pycnometer value (skeletal density (g / cc)) in the absence of an electrochemical modifier. In other embodiments, this volumetric capacity is at least 450 mAh / cc. In some other embodiments, this volumetric capacity is at least 500 mAh / cc. In other embodiments, the volumetric capacity is at least 550 mAh / cc. In other embodiments, the volumetric capacity is at least 600 mAh / cc. In other embodiments, the volumetric capacity is at least 650 mAh / cc, and in other embodiments, the volumetric capacity is at least 700 mAh / cc. In other embodiments, the volumetric capacity of the carbon component of the composite is 700 mAh / cc to 1100 mAh / cc.
[0322] In another embodiment, the present disclosure provides a composite material with extremely durable lithium insertion, wherein when the composite material is incorporated into an electrode of a lithium-based energy storage device (e.g., a lithium-ion battery), the composite has a volumetric capacity (i.e., reversible capacity) of at least 800 mAh / cc. The volumetric capacity of the composite material can be calculated by multiplying the maximum weight capacity (mAh / g) by the specific gravity (skeleton density (g / cc)) before electrochemical testing. In other embodiments, the volumetric capacity is at least 900 mAh / cc. In some other embodiments, the volumetric capacity is at least 1000 mAh / cc. In other embodiments, the volumetric capacity is at least 1100 mAh / cc. In other embodiments, the volumetric capacity is at least 1200 mAh / cc. In other embodiments, the volumetric capacity is at least 1300 mAh / cc, and in other embodiments, the volumetric capacity is at least 1400 mAh / cc, at least 1500 mAh / cc, at least 1600 mAh / cc, at least 1700 mAh / cc, at least 1800 mAh / cc, or even at least 1900 mAh / cc. In other embodiments, the volumetric capacity is 2000 mAh / cc to 8000 mAh / cc. In other embodiments, the volumetric capacity is 4000 mAh / cc to 7000 mAh / cc. In some specific embodiments, the composite material has a volumetric capacity of about 2500 mAh / cc to about 3500 mAh / cc.
[0323] In another embodiment, the present disclosure provides a composite material with extremely durable lithium intercalation, wherein when the material is incorporated into an electrode of a lithium-based energy storage device (e.g., a lithium ion battery), the composite has a weight capacity (i.e., reversible capacity) of at least 150 mAh / g independent of alloying electrochemical modifiers. In other embodiments, the weight capacity is at least 200 mAh / g. In some other embodiments, this weight capacity is at least 300 mAh / g. In other embodiments, the weight capacity is at least 400 mAh / g. In other embodiments, the weight capacity is at least 500 mAh / g. In other embodiments, the weight capacity is at least 600mAh / g, and in other embodiments, the weight capacity is at least 700mAh / g, at least 800mAh / g, at least 900mAh / g, at least 1000mAh / g, at least 1100mAh / g, at least 1200mAh / g, at least 1300mAh / g, at least 1400mAh / g, at least 1600mAh / g, at least 1800mAh / g, at least 2000mAh / g, at least 2500mAh / g, at least 3000mAh / g, at least 3500mAh / g. In other embodiments, the weight capacity is 1200mAh / g to 3500mAh / g. In some specific embodiments, the composite material has a weight capacity of about 700mAh / g to about 2000mAh / g. In some specific embodiments, the composite material has a weight capacity of about 1000mAh / g to about 1500mAh / g. In some specific embodiments, the composite material has a weight capacity of about 550 mAh / g to about 750 mAh / g. In some specific embodiments, the composite material has a weight capacity of about 400 mAh / g to about 500 mAh / g. Certain embodiments of any of the above composite materials may include an electrochemical modifier as described in more detail below.
[0324] J. Physicochemical properties of composites with extremely durable lithium intercalation that affect electrochemical performance
[0325] As described above, conventional lithium-based energy storage devices contain graphite anode materials. Graphite carbon has many disadvantages in lithium-ion batteries. First, graphite undergoes phase and volume changes during battery operation. That is, when lithium is inserted between graphene sheets, the material physically expands and contracts, while the individual sheets physically move laterally to maintain a low energy storage state. Secondly, graphite has low capacity. Given the ordered and crystalline structure of graphite, six carbons are required to store one lithium ion. The structure cannot accommodate additional lithium. Third, the movement of lithium ions is restricted to a 2D plane, reducing the kinetics and rate capability of the material in the battery. This means that graphite does not operate well at high rates where power is required. This power disadvantage is one of the limiting factors for the use of lithium-ion batteries in all electric vehicles.
[0326] Thus, without being bound by theory, there are certain physicochemical properties of the composite material that allow for extremely durable lithium intercalation. In this context, exemplary, critical properties are silicon content, morphology, and size within the composite, as discussed below and throughout this disclosure.
[0327] In certain embodiments, the impregnated silicon particles embedded in the composite comprise nanoscale features. The nanoscale features may have a characteristic length scale of preferably less than 1 um, preferably less than 300 nm, preferably less than 150 nm, preferably less than 100 um, preferably less than 50 nm, preferably less than 30 nm, preferably less than 15 nm, preferably less than 10 nm, preferably less than 5 nm.
[0328] In certain embodiments, the shape of the silicon embedded in the composite is spherical. In certain other embodiments, the porous silicon particles are non-spherical, such as rod-shaped or fibrous structures. In a preferred embodiment, silicon exists as a layer coated inside the holes in the porous carbon support. The depth of this silicon layer can vary, for example, the depth can be 5nm to 10nm, for example 5nm to 20nm, for example 5nm to 30nm, for example 5nm to 33nm, for example 10nm to 30nm, for example 10nm to 50nm, for example 10nm to 100nm, for example 10nm to 150nm, for example 50nm to 150nm, for example 100nm to 300nm, for example 300nm to 1000nm.
[0329] In preferred embodiments, the silicon embedded in the composite is nanoscale and resides in the pores of the porous carbon scaffold. For example, the embedded silicon can be impregnated into the pores in the porous carbon particles by CVD deposition or other appropriate processes, and the porous carbon particles contain pore sizes of 5nm to 1000nm, such as 10nm to 500nm, such as 10nm to 200nm, such as 10nm to 100nm, such as 33nm to 150nm, such as 20nm to 100nm. With respect to the partial pore volume, other ranges of carbon pore sizes are also envisioned, whether microporous, mesoporous or macroporous.
[0330] In certain embodiments, the porous silicon particles embedded in the composite fill the pores in the porous carbon support material. The percentage of the pore volume in the porous carbon support filled with silicon can vary. For example, the silicon embedded in the porous carbon support material can account for 5% to 15% of the total available pore volume in the porous carbon support. In other embodiments, the silicon embedded in the porous carbon support material can account for 15% to 25% of the total available pore volume in the porous carbon support. In other embodiments, the silicon embedded in the porous carbon support material can account for 25% to 35% of the total available pore volume in the porous carbon support. In other embodiments, the silicon embedded in the porous carbon support material can account for 20% to 40% of the total available pore volume in the porous carbon support. In other embodiments, the silicon embedded in the porous carbon support material can account for 25% to 50% of the total available pore volume in the porous carbon support. In other embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, such as 30% to 60% of the total available pore volume in the porous carbon support. In other embodiments, the silicon embedded in the porous carbon support material can account for 60% to 80% of the total available pore volume in the porous carbon support. In other embodiments, the silicon embedded in the porous carbon support material can account for 80% to 100% of the total available pore volume in the porous carbon support.
[0331] In a preferred embodiment, the silicon embedded in the porous carbon support material occupies a certain proportion of the total available pore volume in the porous carbon support, and the remaining pore volume is available for silicon to expand when taking up lithium. In this article, without being bound by theory, this remaining pore volume may or may not be able to enter nitrogen (nitrogen), and therefore may or may not be observed when using nitrogen adsorption disclosed herein.
[0332] Thus, in some embodiments, the silicon embedded in the porous carbon scaffold material may account for 30% to 70% of the total available pore volume in the porous carbon scaffold, and the composite particles include a porous carbon scaffold and embedded silicon, wherein the embedded silicon includes at least 0.01 cm 3In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes at least 0.1 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes at least 0.2 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes at least 0.4 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes at least 0.6 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes at least 0.8 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes at least 0.8 cm 3 / g pore volume.
[0333] Thus, in some embodiments, the silicon embedded within the porous carbon scaffold material may account for 30% to 70% of the total available pore volume within the porous carbon scaffold, and the composite particles comprise a porous carbon scaffold and embedded silicon, wherein the embedded silicon comprises less than 0.5 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes less than 0.4 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes less than 0.3 cm 3In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes less than 0.2 cm 3 In some embodiments, the silicon embedded in the porous carbon support material may account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes less than 0.1 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes less than 0.05 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes less than 0.02 cm 3 In some embodiments, the silicon embedded in the porous carbon support material can account for 30% to 70% of the total available pore volume in the porous carbon support, and the composite particles include a porous carbon support and embedded silicon, wherein the embedded silicon includes less than 0.01 cm 3 / g pore volume.
[0334] In certain other embodiments, the silicon embedded in the pore volume of the porous silicon is substantially present in the macropores, as evidenced by a reduction in the macropore volume in the silicon-embedded composite material compared to the porous carbon scaffold material prior to the addition of the silicon. Thus, in some embodiments, the embedded silicon results in at least a 10% reduction in macropore volume, such as at least a 20% reduction in macropore volume, such as at least a 30% reduction in macropore volume, such as at least a 40% reduction in macropore volume, such as at least a 50% reduction in macropore volume, such as at least a 60% reduction in macropore volume, such as at least a 70% reduction in macropore volume, such as at least a 80% reduction in macropore volume, such as at least a 90% reduction in macropore volume.
[0335] In certain other embodiments, the silicon embedded in the pore volume of the porous silicon is substantially present in the mesopores, as evidenced by a reduction in the mesopore volume in the silicon-embedded composite material compared to the porous carbon scaffold material prior to the addition of the silicon. Thus, in some embodiments, the embedded silicon results in at least a 10% reduction in mesopore volume, such as at least a 20% reduction in mesopore volume, such as at least a 30% reduction in mesopore volume, such as at least a 40% reduction in mesopore volume, such as at least a 50% reduction in mesopore volume, such as at least a 60% reduction in mesopore volume, such as at least a 70% reduction in mesopore volume, such as at least a 80% reduction in mesopore volume, such as at least a 90% reduction in mesopore volume.
[0336] In certain other embodiments, the silicon embedded in the pore volume of the porous silicon is substantially present in the micropores, as evidenced by a reduction in the micropore volume in the silicon-embedded composite material compared to the porous carbon scaffold material prior to the addition of the silicon. Thus, in some embodiments, the embedded silicon results in a reduction in micropore volume of at least 10%, such as a reduction in micropore volume of at least 20%, such as a reduction in micropore volume of at least 30%, such as a reduction in micropore volume of at least 40%, such as a reduction in micropore volume of at least 50%, such as a reduction in micropore volume of at least 60%, such as a reduction in micropore volume of at least 70%, such as a reduction in micropore volume of at least 80%, such as a reduction in micropore volume of at least 90%.
[0337] In certain embodiments, silicon is embedded in substantially all available pre-volume within the porous carbon scaffold particles and also covers the surface of the particles, such that the silicon loading can represent greater than 100% of the total pore volume of the porous carbon scaffold prior to the addition of silicon. For example, herein, the silicon loading can be greater than 105%, such as greater than 110%, such as greater than 120%, such as greater than 130%, such as greater than 150%, such as greater than 200%.
[0338] In certain embodiments, the pore volume distribution of the composite material is verified by high resolution transmission electron spectroscopy (HRTEM).
[0339] In certain embodiments, the composite material comprises less than 20% micropores, greater than 30% mesopores, and greater than 30% macropores. In certain embodiments, the composite material comprises less than 10% micropores, greater than 30% mesopores, and greater than 30% macropores. In certain embodiments, the composite material comprises less than 5% micropores, greater than 30% mesopores, and greater than 30% macropores. In certain embodiments, the composite material comprises less than 5% micropores, greater than 40% mesopores, and greater than 40% macropores. In certain embodiments, the composite material comprises less than 1% micropores, greater than 40% mesopores, and greater than 40% macropores.
[0340] In certain embodiments, the composite material comprises less than 10% micropores, greater than 70% mesopores, and greater than 20% macropores. In certain embodiments, the composite material comprises less than 10% micropores, greater than 20% mesopores, and greater than 70% macropores. In certain embodiments, the composite material comprises less than 10% micropores, greater than 10% mesopores, and greater than 80% macropores. In certain embodiments, the composite material comprises less than 10% micropores, greater than 80% mesopores, and greater than 10% macropores.
[0341] In certain embodiments, the composite material comprises less than 5% micropores, greater than 70% mesopores, and greater than 20% macropores. In certain embodiments, the composite material comprises less than 5% micropores, greater than 20% mesopores, and greater than 70% macropores. In certain embodiments, the composite material comprises less than 5% micropores, greater than 5% mesopores, and greater than 80% macropores. In certain embodiments, the composite material comprises less than 5% micropores, greater than 80% mesopores, and greater than 10% macropores.
[0342] In certain embodiments, the composite material comprises less than 1% micropores, greater than 70% mesopores, and greater than 20% macropores. In certain embodiments, the composite material comprises less than 1% micropores, greater than 20% mesopores, and greater than 70% macropores. In certain embodiments, the composite material comprises less than 1% micropores, greater than 10% mesopores, and greater than 80% macropores. In certain embodiments, the composite material comprises less than 1% micropores, greater than 80% mesopores, and greater than 10% macropores.
[0343] In certain embodiments, the composite material comprises less than 4% micropores, greater than 84% mesopores, and less than 13% macropores.
[0344] In certain embodiments, the composite comprises a pore volume of 0.01 to 0.5, and the pore volume distribution comprises less than 20% micropores, more than 50% mesopores, and less than 30% macropores. In certain embodiments, the composite comprises 0.05 cm 3 / g to 0.4cm 3 / g pore volume, and the pore volume distribution comprises less than 10% micropores, more than 60% mesopores and less than 20% macropores. In certain embodiments, the composite comprises 0.1 cm 3 / g to 0.3cm 3 / g pore volume, and the pore volume distribution comprises less than 5% micropores, more than 70% mesopores and less than 15% macropores. In certain embodiments, the composite comprises 0.1 cm 3 / g to 0.3cm 3 / g of pore volume, and the pore volume distribution contains less than 5% micropores, more than 85% mesopores and less than 10% macropores.
[0345] In a preferred embodiment, silicon is embedded within a portion of the porous carbon scaffold, and the pores are covered with a coating surrounding the composite particles, for example, the coating may comprise carbon or a conductive polymer, as described elsewhere in this disclosure. Herein, and without being bound by theory, this pore volume may not enter nitrogen and therefore may not be detected by nitrogen adsorption. However, this resulting void space within the composite particles may be determined by other means, such as by measuring the tap density or envelope density, such as by pycnometry techniques.
[0346] Thus, the composite material with extremely durable lithium intercalation may comprise 30% to 70% of the total available pore volume within the porous carbon support as silicon intercalated within the porous carbon support material, and the composite particles may comprise less than 0.7 g / cm 3 The tap density is less than 0.6 g / cm 3 , for example, less than 0.5 g / cm 3 , for example, less than 0.4 g / cm 3 , for example, less than 0.3 g / cm 3 , for example, less than 0.2 g / cm 3 , for example, less than 0.15 g / cm 3 , for example, less than 0.1 g / cm 3 .
[0347] In some embodiments, the composite material with extremely durable lithium intercalation may include 30% to 70% of the total available pore volume within the porous carbon support as silicon intercalated within the porous carbon support material, and the composite particles may include less than 2.1 g / cm 3 The skeleton density determined by specific gravity is less than 2.0 g / cm 3 , for example, less than 1.9 g / cm 3 , for example, less than 1.8 g / cm 3 , for example, less than 1.7 g / cm 3 , for example, less than 1.6 g / cm 3 , for example, less than 1.4 g / cm 3 , for example, less than 1.2 g / cm 3 , for example, less than 1.0 g / cm 3 In certain embodiments, the composite material comprises 1.8 g / cm 3 Up to 2.2g / cm 3 The skeleton density is 1.9 g / cm 3 Up to 2.1g / cm3 , for example 2.0g / cm 3 Up to 2.1g / cm 3 .
[0348] The silicon content in the composite material that exhibits extremely durable lithium insertion can vary. For example, the silicon content in the composite can be 5% to 95% by weight. In certain embodiments, the silicon content in the composite can be 10% to 80%, such as 20% to 70%, such as 30% to 60%, such as 40% to 50%. In some embodiments, the silicon content in the composite can be 10% to 50%, such as 20% to 40%, such as 30% to 40%. In other embodiments, the silicon content in the composite can be 40% to 80%, such as 50% to 70%, such as 60% to 70%. In a specific embodiment, the silicon content in the composite can be 10% to 20%. In a specific embodiment, the silicon content in the composite can be 15% to 25%. In a specific embodiment, the silicon content in the composite can be 25% to 35%. In a specific embodiment, the silicon content in the composite can be 35% to 45%. In a specific embodiment, the silicon content in the composite can be 45% to 55%. In a specific embodiment, the silicon content in the composite can be 55% to 65%. In certain embodiments, the silicon content in the composite may be between 65% and 75%. In certain embodiments, the silicon content in the composite may be between 75% and 85%.
[0349] Since total pore volume (as measured by nitrogen adsorption) can be related in part to the storage of lithium ions, internal ion dynamics, and available composite / electrolyte surface capable of charge transfer, this is one parameter that can be tuned to obtain desired electrochemical properties.
[0350] Thus, the surface area and pore volume of a composite material that exhibits extremely durable lithium intercalation can vary. For example, the surface area of a composite material that exhibits extremely durable lithium intercalation can be 10 m 2 / g to 200m 2 In some embodiments, the surface area of the composite can be 10 m 2 / g to 100m 2 / g, for example 20m 2 / g to 200m 2 / g, for example 20m 2 / g to 150m 2 / g, for example 10m 2 / g to 100m 2 In some embodiments, the surface area of the composite can be 20 m 2 / g to 80m 2 / g, for example 20m2 / g to 70m 2 / g, for example 30m 2 / g to 70m 2 / g, for example 40m 2 / g to 60m 2 / g.
[0351] The pore volume of the composite material showing extremely durable lithium intercalation can be as small as 0.01 cm 3 / g to 0.2cm 3 In certain embodiments, the pore volume of the composite material may be 0.01 cm 3 / g at 0.15cm 3 / g, for example 0.01cm 3 / g to 0.1cm 3 / g, for example 0.01cm 3 / g to 0.05cm 3 / g.
[0352] The pore volume distribution of the composite material exhibiting extremely durable lithium intercalation can vary, for example, the micropore % can account for less than 30%, such as less than 20%, such as less than 10%, such as less than 5%, such as less than 4%, such as less than 3%, such as less than 2%, such as less than 1%, such as less than 0.5%, such as less than 0.2%, such as less than 0.1%. In certain embodiments, there is no detectable micropore volume in the composite material exhibiting extremely durable lithium intercalation.
[0353] In some embodiments, the pore volume distribution of the composite material exhibiting extremely durable lithium intercalation comprises 30% mesopores, such as less than 20% mesopores, such as less than 10% mesopores, such as less than 5% mesopores, such as less than 4% mesopores, such as less than 3% mesopores, such as less than 2% mesopores, such as less than 1% mesopores, such as less than 0.5% mesopores, such as less than 0.2% mesopores, such as less than 0.1% mesopores. In certain embodiments, there is no detectable mesopore volume in the composite material exhibiting extremely durable lithium intercalation.
[0354] In some embodiments, the pore volume distribution of the composite material exhibiting extremely durable lithium intercalation comprises greater than 50% macropores, such as greater than 60% macropores, such as greater than 70% macropores, such as greater than 80% macropores, such as greater than 90% macropores, such as greater than 95% macropores, such as greater than 98% macropores, such as greater than 99% macropores, such as greater than 99.5% macropores, such as greater than 99.9% macropores.
[0355] The pore volume distribution of the composite material exhibiting extremely durable lithium intercalation includes various embodiments of the above several paragraphs. For example, the composite material exhibiting extremely durable lithium intercalation includes less than 30% micropores, less than 30% mesopores, and greater than 50% macropores. In other embodiments, the composite material exhibiting extremely durable lithium intercalation includes less than 20% micropores, less than 20% mesopores, and greater than 70% macropores. In other embodiments, the composite material exhibiting extremely durable lithium intercalation includes less than 10% micropores, less than 10% mesopores, and greater than 80% macropores. In other embodiments, the composite material exhibiting extremely durable lithium intercalation includes less than 10% micropores, less than 10% mesopores, and greater than 90% macropores. In other embodiments, the composite material exhibiting extremely durable lithium intercalation includes less than 5% micropores, less than 5% mesopores, and greater than 90% macropores. In other embodiments, the composite material exhibiting extremely durable lithium intercalation includes less than 5% micropores, less than 5% mesopores, and greater than 95% macropores.
[0356] In certain embodiments, the surface layer of the composite material exhibits a low Young's modulus to absorb the volume deformation associated with the uptake and insertion of lithium ions without cracking or otherwise providing additional opportunities for new SEI formation. In this article, the surface layer is sufficient to provide a composite material comprising a Young's modulus of less than 100 GPa, such as less than 10 GPa, such as less than 1 GPa, such as less than 0.1 GPa.
[0357] In certain embodiments, the surface layer of the composite material exhibits a low bulk modulus so as to absorb the volume deformation associated with the uptake and insertion of lithium ions without cracking or otherwise providing additional opportunities for new SEI formation. In this article, the surface layer is sufficient to provide a composite material comprising a bulk modulus of less than 100 GPa, such as less than 10 GPa, such as less than 1 GPa, such as less than 0.1 GPa.
[0358] In certain other embodiments, the surface layer of the composite material exhibits a high bulk modulus so as to limit the volume deformation associated with the uptake and insertion of lithium ions, thereby avoiding crushing or otherwise denying additional opportunities for new SEI formation. In this article, the surface layer is sufficient to provide a composite material comprising a bulk modulus greater than 10 GPa, such as greater than 50 GPa, such as greater than 100 GPa, such as greater than 1000 GPa.
[0359] In some embodiments, the surface area of the composite material exhibiting extremely durable lithium intercalation may be greater than 500 m 2 In other embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion may be less than 300 m 2In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is 200 m 2 / g to 300m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is 100 m 2 / g to 200m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is 50 m 2 / g to 100m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is 10 m 2 / g to 50m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is less than 10 m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is less than 5 m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is less than 2 m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is less than 1 m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is less than 0.5 m 2 In some embodiments, the surface area of the composite material exhibiting extremely durable lithium insertion is less than 0.1 m 2 / g.
[0360] The surface area of the composite material can be modified by activation. The activation method can use steam, chemical activation, CO2 or other gases. Methods for activating carbon materials are well known in the art.
[0361] The volumetric capacity and gravimetric capacity can be determined by using many methods known in the art, for example by incorporating into an electrode half-cell of a button cell with a lithium metal counter electrode. The gravimetric capacity is determined by dividing the measured capacity by the mass of the electrochemically active carbon material. The volumetric capacity is determined by dividing the measured capacity by the volume of the electrode (including binder and conductive additive). Methods for determining the volumetric capacity and gravimetric capacity are described in more detail in the Examples.
[0362] The composite can contain lithium metal (by doping or by electrochemical cycling) in the pores of the composite, such as pores in porous carbon within the composite. Lithium plating within the pores is considered to be beneficial to the capacity and cycle stability of hard carbon. Plating within the pores can produce new nanofiber lithium. In some cases, lithium can be plated on the outside of the particles. External lithium plating is not conducive to overall performance, as explained in the embodiments. The presence of internal and external lithium metal can be measured by cutting the metal using a focused ion beam (FIB) and a scanning electron microscope (SEM). In contrast to hard carbon, metallic lithium is easily detected in SEM. After cycling, when the material has lithium inserted below 0V, the material can be sliced and imaged. In one embodiment, the material shows lithium in micropores. In another embodiment, the material shows lithium in mesopores. In another embodiment, the material does not show lithium plating on the surface of the material. In another embodiment, silicon is stored in a variety of pore sizes and shapes. Material shape and pore size distribution can uniquely and preferentially promote pore plating before surface plating. The ideal pore size for lithium storage is explained elsewhere in this disclosure.
[0363] The particle size distribution of the composite material exhibiting extremely durable lithium intercalation is important for determining power performance as well as volumetric capacity. As the loading increases, the volumetric capacity can increase. In one embodiment, the distribution is Gaussian and the shape is unimodal, bimodal or multimodal (>2 characteristic peaks). The properties of the particle size of the composite can be described by D0 (the smallest particle in the distribution), Dv50 (average particle size) and Dv100 (the maximum size of the largest particle). The best combination of particle loading and performance will be some combination of the following size ranges.
[0364] In one embodiment, the Dv0 of the composite material exhibiting extremely durable lithium insertion can be from 1 nm to 5 μm. In another embodiment, the Dv0 of the composite is from 5 nm to 1 μm, or from 5 nm to 500 nm, or from 5 nm to 100 nm, or from 10 nm to 50 nm. In another embodiment, the Dv0 of the composite is from 500 nm to 2 μm, or from 750 nm to 1 μm, or from 1 μm to 2 μm. In another embodiment, the Dv0 of the composite is from 2 μm to 5 μm or even greater than 5 μm. The particle size reduction in the above embodiments can be performed as known in the art, for example by jet milling in the presence of various gases, including air, nitrogen, argon, helium, supercritical vapor, and other gases known in the art.
[0365] In one embodiment, the Dv50 of the composite material exhibiting extremely durable lithium insertion is 5nm to 20μm. In another embodiment, the Dv50 of the composite is 5nm to 1μm, 5nm to 500nm, 5nm to 100nm, 10nm to 50nm. In another embodiment, the Dv50 of the composite is 500nm to 2μm, 750nm to 1μm, 1μm to 2μm. In another embodiment, the Dv50 of the composite is 2μm to 20μm, or 3μm to 10μm, or 4μm to 8μm, or greater than 20μm.
[0366] In one embodiment, the Dv100 of the composite material exhibiting extremely durable lithium insertion can be 8nm to 100μm. In another embodiment, the Dv100 of the composite is 5nm to 1μm, 5nm to 500nm, 5nm to 100nm, 10nm to 50nm. In another embodiment, the Dv100 of the composite is 500nm to 2μm, 750nm to 1μm, 1μm to 2μm. In another embodiment, the Dv100 of the composite is 2μm to 100μm, 5μm to 50μm, 8μm to 40μm, 10μm to 35μm, 15μm to 30μm, 20μm to 30μm, about 25μm, greater than 100μm.
[0367] The span (Dv90-Dv10) / (Dv50), where Dv10, Dv50 and Dv90 represent the particle sizes at 10%, 50% and 90% of the volume distribution, can vary, for example, from 100 to 10, 10 to 5, 5 to 2, 2 to 1; in some embodiments, the span can be less than 1. In certain embodiments, the particle size distribution of the composite comprising carbon and porous silicon material can be multimodal, for example, bimodal or trimodal.
[0368] In another embodiment, the present disclosure provides a composite material that exhibits extremely durable lithium insertion, wherein when the composite material is incorporated into an electrode of a lithium-based energy storage device, the composite material has a volumetric capacity that is at least 10% greater than when the lithium-based energy storage device contains a graphite electrode. In some embodiments, the lithium-based energy storage device is a lithium-ion battery. In other embodiments, the composite material has a volumetric capacity in a lithium-based energy storage device that is at least 5%, at least 10%, at least 15% greater than the volumetric capacity of the same energy storage device with a graphite electrode. In other embodiments, the composite material has a volumetric capacity in a lithium-based energy storage device that is at least 20%, at least 30%, at least 40%, at least 50%, at least 200%, at least 100%, at least 150%, or at least 200% greater than the volumetric capacity of the same energy storage device with a graphite electrode.
[0369] The composite material may be pre-lithiated as known in the art. These lithium atoms may or may not be separated from the carbon. The number of lithium atoms relative to 6 carbon atoms may be calculated by techniques known to those skilled in the art.
[0370] #Li=Q×3.6×MM / (C%×F)
[0371] Where Q is the lithium extraction capacity measured in mAh / g between 5 mV and 2.0 V relative to lithium metal, MM is 72 or the molecular mass of 6 carbons, F is the Faraday constant 96500, and C% is the mass percent of carbon present in the structure as measured by CHNO or XPS.
[0372] Composite materials that exhibit extremely durable lithium intercalation are characterized by a ratio of lithium atoms to carbon atoms (Li:C) that can vary from about 0:6 to 2:6. In some embodiments, the Li:C ratio is from about 0.05:6 to about 1.9:6. In other embodiments, the maximum Li:C ratio is 2.2:6, where the lithium is in ionic form rather than metallic form. In certain other embodiments, the Li:C ratio is from about 1.2:6 to about 2:6, from about 1.3:6 to about 1.9:6, from about 1.4:6 to about 1.9:6, from about 1.6:6 to about 1.8:6, or from about 1.7:6 to about 1.8:6. In other embodiments, the Li:C ratio is greater than 1:6, greater than 1.2:6, greater than 1.4:6, greater than 1.6:6, or even greater than 1.8:6. In even other embodiments, the Li:C ratio is about 1.4:6, about 1.5:6, about 1.6:6, about 1.6:6, about 1.7:6, about 1.8:6, or about 2: 6. In a particular embodiment, the Li:C ratio is about 1.78:6.
[0373] In certain other embodiments, the composite material exhibiting extremely durable lithium intercalation comprises a Li:C ratio of about 1:6 to about 2.5:6, about 1.4:6 to about 2.2:6, or about 1.4:6 to about 2:6. In other embodiments, the composite material may not need to contain lithium, but instead has a lithium uptake capacity (i.e., the capacity to take up a certain mass of lithium, such as when the material is cycled between two voltage conditions, in the case of a lithium ion half-cell, an exemplary voltage window is 0V to 3V, such as 0.005V to 2.7V, such as 0.005V to 1V, such as 0.005V to 0.8V). Although not wishing to be bound by theory, it is believed that the lithium uptake capacity of the composite material contributes to its excellent performance in lithium-based energy storage devices. The lithium uptake capacity is expressed as the ratio of lithium atoms taken up by the composite. In certain other embodiments, the composite material exhibiting extremely durable lithium intercalation comprises a lithium uptake capacity of about 1:6 to about 2.5:6, about 1.4:6 to about 2.2:6, or about 1.4:6 to about 2:6.
[0374] In certain other embodiments, the lithium uptake capacity is about 1.2:6 to about 2:6, about 1.3:6 to about 1.9:6, about 1.4:6 to about 1.9:6, about 1.6:6 to about 1.8:6, or about 1.7:6 to about 1.8:6. In other embodiments, the lithium uptake capacity is greater than 1:6, greater than 1.2:6, greater than 1.4:6, greater than 1.6:6, or even greater than 1.8:6. In even other embodiments, the Li:C ratio is about 1.4:6, about 1.5:6, about 1.6:6, about 1.6:6, about 1.7:6, about 1.8:6, or about 2:6. In a specific embodiment, the Li:C ratio is about 1.78:6.
[0375] In certain embodiments, the composite material exhibiting extremely durable intercalation is doped with an electrochemical modifier, such as lithium. Different methods of doping lithium can include chemical reactions, electrochemical reactions, physical mixing of particles, gas phase reactions, solid phase reactions, and liquid phase reactions. In other embodiments, the lithium is in the form of lithium metal.
[0376] As discussed in more detail below, the surface functions disclosed herein of the composite materials that exhibit extremely durable lithium intercalation can be varied to obtain desired chemical properties. One property of the surface functions that can be predicted is the pH of the composite material. The composite materials disclosed herein comprise a pH value of less than 1 to about 14, for example, less than 5, 5 to 8, or greater than 8. In some embodiments, the pH of the composite material is less than 4, less than 3, less than 2, or even less than 1. In other embodiments, the pH of the composite material is about 5 to 6, about 6 to 7, about 7 to 8, or 8 to 9 or 9 to 10. In other embodiments, the pH is high, and the pH of the composite material is greater than 8, greater than 9, greater than 10, greater than 11, greater than 12, or even greater than 13.
[0377] The pore size distribution of the carbon support can be important for the storage capacity of the material and the kinetics and power capacity of the system and the ability to incorporate a large amount of electrochemical modifiers. The pore size distribution can be micropore level to mesopore level to macropore level, and can be unimodal, bimodal or multimodal. Micropores with an average pore size less than 1nm can produce other storage sites and lithium (sodium) ion diffusion paths. Graphite sheets are usually spaced 0.33nm apart for lithium storage. Although it is not desired to be bound by theory, it is believed that a large number of pores of similar size can produce graphite-like structures in the pores, and other hard carbon types are stored in the overall structure. Mesopores are generally less than 100μm. These holes are ideal locations for nanoparticle dopants (such as metals), and provide paths for conductive additives and dielectrics for ion and electronic conduction. In some embodiments, the carbon material contains macropores greater than 100nm, which may be particularly suitable for large particle doping.
[0378] The pore size distribution of composite materials that exhibit extremely durable lithium intercalation can be important for the storage capacity of the material and the kinetic and power capabilities of the system and the ability to incorporate large amounts of electrochemical modifiers. The pore size distribution can range from micropores to mesopores to macropores and can be unimodal, bimodal or multimodal. In some embodiments, the composite material comprises micropores less than 100 nm, which can be particularly suitable for lithium diffusion.
[0379] Thus, in one embodiment, the composite material comprises a partial pore volume of pores of 1 nm or less that accounts for at least 50% of the total pore volume, at least 75% of the total pore volume, at least 90% of the total pore volume, or at least 99% of the total pore volume. In other embodiments, the composite material comprises a partial pore volume of pores of 10 nm or less that accounts for at least 50% of the total pore volume, at least 75% of the total pore volume, at least 90% of the total pore volume, or at least 99% of the total pore volume. In other embodiments, the composite material comprises a partial pore volume of pores of 50 nm or less that accounts for at least 50% of the total pore volume, at least 75% of the total pore volume, at least 90% of the total pore volume, or at least 99% of the total pore volume.
[0380] In another embodiment, the composite material comprises a portion of the pore surface area of pores at or below 100 nm that accounts for at least 50% of the total pore surface area, at least 75% of the total pore surface area, at least 90% of the total pore surface area, or at least 99% of the total pore surface area. In another embodiment, the composite material comprises a portion of the pore surface area of pores at or above 100 nm that accounts for at least 50% of the total pore surface area, at least 75% of the total pore surface area, at least 90% of the total pore surface area, or at least 99% of the total pore surface area.
[0381] In another embodiment, the composite material comprises pores that are predominantly 100 nm or less, such as 10 nm or less, such as 5 nm or less. Alternatively, the composite material comprises micropores of 0 nm to 2 nm and macropores of 2 nm to 100 nm. The ratio of pore volume or pore surface in the micropore range compared to the mesopore range may be 95:5 to 5:95.
[0382] The inventors have discovered that the degree of disorder in composite materials, with and without electrochemical modifiers, can have an effect on the electrochemical properties of the carbon material. Thus, controlling the degree of disorder in the composite material provides a possible means to improve the rate performance of the carbon, as smaller grain sizes can allow for lower resistance to lithium ion diffusion through the amorphous structure. The present invention includes embodiments containing high and low levels of disorder.
[0383] The disorder recorded by Raman spectroscopy is a measure of the size of the crystallites found within the amorphous structure and the crystalline structure (MAPimenta, G. Dresselhaus, M.S. Dresselhaus, L.G. Canado, A. Jorio, and R. Saito, "Studying disorder in graphite-based systems by Raman spectroscopy," Physical Chemistry Chemical Physics, Vol. 9, No. 11, p. 1276, 2007). An exemplary Raman spectrum of carbon is shown at Figure 4 For carbon structures, the crystal size (L a )(Equation 1)
[0384] L a (nm) = (2.4 × 10 -10 ) 4 laser R -1 (1)
[0385] in
[0386] R=I D / I G (2)
[0387] In some embodiments, R and L a The value of can vary, and its value can affect the electrochemical properties of the carbon material, such as the capacity of the second lithium insertion (the second lithium insertion is related to the first cycle efficiency, because the first cycle efficiency = (capacity at the first lithium insertion / capacity at the second lithium insertion) × 100). For example, in some embodiments, R is about 0 to about 1 or about 0.50 to about 0.95. In other embodiments, R is about 0.60 to about 0.90. In other embodiments, R is about 0.80 to about 0.90. In certain embodiments, L a L also varies and can be from about 1 nm to about 500 nm. In certain other embodiments, L a In other embodiments, L a From about 15 nm to about 30 nm, for example, from about 20 nm to about 30 nm or from about 25 nm to about 30 nm.
[0388] In related embodiments, the electrochemical properties of the material comprising the composite are related to the crystallinity level measured by X-ray diffraction (XRD). Although Raman measures crystal size, XRD is recorded at the periodic level of the overall structure by scattering of incident X-rays. The present invention includes materials that are non-graphitic (crystallinity <10%) and semi-graphitic (10% to 50% crystallinity). The crystallinity of the material is from about 0% to about 99%. In some embodiments, the material comprising the composite comprises less than 10% crystallinity, less than 5% crystallinity, or even less than 1% crystallinity (i.e., highly amorphous). In other embodiments, the material comprising the composite comprises 10% to 50% crystallinity. In other embodiments, the material comprising the composite comprises less than 50% crystallinity, less than 40% crystallinity, less than 30% crystallinity, or even less than 20% crystallinity.
[0389] In related embodiments, the electrochemical properties of the material comprising the complex are related to the crystallinity level measured by X-ray diffraction (XRD). The present invention includes materials that are amorphous (crystallinity <10) and semi-crystalline (10% to 50% crystallinity) and crystalline (>50%). The crystallinity of the material comprising the complex is from about 0% to about 99%. In some embodiments, the material comprising the complex comprises less than 10% crystallinity, less than 5% crystallinity, or even less than 1% crystallinity (i.e., highly amorphous). In other embodiments, the material comprising the complex comprises 10% to 50% crystallinity. In other embodiments, the material comprising the complex comprises less than 50% crystallinity, less than 40% crystallinity, less than 30% crystallinity, or even less than 20% crystallinity.
[0390] In a related embodiment, the electrochemical performance of the composite is related to an empirical value R calculated from small angle X-ray diffraction (SAXS), where R = B / A, B is the height of the double layer peak and A is the baseline of a single graphene sheet measured by SAXS.
[0391] SAXS has the ability to measure internal pores, which may be difficult to reach by gas adsorption techniques, but can store lithium. In certain embodiments, the R factor is less than 1, including monolayer graphene. In other embodiments, the R factor is about 0.1 to about 20 or about 1 to 10. In other embodiments, the R factor is 1 to 5, 1 to 2 or 1.5 to 2. In other embodiments, the R factor is 1.5 to 5, 1.75 to 3 or 2 to 2.5. Or, the R factor is greater than 10. SAXS figures can also be analyzed by the number of peaks found at 10 ° to 40 °. In some embodiments, the number of peaks found by SAXS at low scattering angles is 1, 2, 3 or even greater than 3.
[0392] In certain embodiments, the organic content of the material comprising the composite can be manipulated to provide a desired property, for example, by contacting the material with a hydrocarbon compound such as cyclohexane. Infrared spectroscopy (FTIR) can be used as a metric to determine the organic content of the surface and overall structure of the material. In one embodiment, the material comprising the composite does not substantially contain organic material. A substantially featureless FTIR spectrum indicates such an embodiment. In other embodiments, the carbon material without an electrochemical modifier comprises organic material on the surface or in the overall structure. In such embodiments, the FTIR spectrum generally describes large peaks and valleys indicating the presence of organic content.
[0393] When placed in a lithium support device for energy storage, the organic content can have a direct relationship with the electrochemical performance and reaction of the material. Materials containing the composite with a flat FTIR signal (no organic matter) often show a low extraction peak at a voltage distribution of 0.2V. It is well known in the art that the extraction voltage is typical of lithium stripping. In certain embodiments, the material containing the composite contains organic content and there is no or nearly no lithium stripping plateau.
[0394] Composite materials can also include different amounts of carbon, oxygen, hydrogen and nitrogen, as measured by gas chromatography CHNO analysis. In one embodiment, the carbon content of the composite is greater than 98wt.% or even greater than 99.9wt%, as measured by CHNO analysis. In another embodiment, the carbon content of the composite is about 10wt.% to about 99.9wt.%, such as about 50wt.% to about 98wt.% of total mass. In another embodiment, the carbon content of the composite is 90wt.% to 98wt.%, 92wt.% to 98wt.% or greater than 95% of total mass. In another embodiment, the carbon content of the composite is 80wt.% to 90wt.% of total mass. In another embodiment, the carbon content of the composite is 70wt.% to 80wt.% of total mass. In another embodiment, the carbon content of the composite ranges from 60wt.% to 70wt.% of total mass. In another embodiment, the carbon content of the composite ranges from 50wt.% to 60wt.% of total mass. In another embodiment, the carbon content of the composite ranges from 40 wt.% to 50 wt.% of the total mass. In another embodiment, the carbon content of the composite ranges from 30 wt.% to 40 wt.% of the total mass. In another embodiment, the carbon content of the composite ranges from 20 wt.% to 30 wt.% of the total mass. In another embodiment, the carbon content of the composite ranges from 10 wt.% to 20 wt.% of the total mass. In another embodiment, the carbon content of the composite ranges from 1 wt.% to 10 wt.% of the total mass.
[0395] In another embodiment, based on the total mass of all components in the composite material, the nitrogen content is 0 to 90wt.%, as measured by CHNO analysis. In another embodiment, the nitrogen content is 1wt.% to 10wt.% of the total mass. In another embodiment, the nitrogen content is 10wt.% to 20wt.% of the total mass. In another embodiment, the nitrogen content is 20wt.% to 30wt.% of the total mass. In another embodiment, the nitrogen content is greater than 30wt.%. In some more specific embodiments, the nitrogen content is about 1% to about 6%, while in other embodiments, the nitrogen content is about 0.1% to about 1%. In some of the above embodiments, the nitrogen content is based on the weight relative to the total weight of all components in the composite material.
[0396] Carbon and nitrogen content can also be measured as a ratio of C:N (carbon atoms to nitrogen atoms). In one embodiment, the C:N ratio is 1:0.001 to 0.001:1 or 1:0.001 to 1:1. In another embodiment, the C:N ratio is 1:0.001 to 1:0.01. In another embodiment, the C:N ratio is 1:0.01 to 1:1. In another embodiment, the nitrogen content exceeds the carbon content, for example, the C:N ratio can be about 0.01:1 to about 0.1:1 or 0.1:1 to about 0.5:1.
[0397] Composite materials containing silicon materials may also contain varying amounts of carbon, oxygen, nitrogen, Cl, and Na, to name a few ions, as measured by XPS analysis. In one embodiment, the carbon content is greater than 98 wt.%, as measured by XPS analysis. In another embodiment, the carbon content is 50 wt.% to 98 wt.% of the total mass. In another embodiment, the carbon content is 90 wt.% to 98 wt.% of the total mass. In another embodiment, the carbon content is 80 wt.% to 90 wt.% of the total mass. In another embodiment, the carbon content is 70 wt.% to 80 wt.% of the total mass. In another embodiment, the carbon content is 60 wt.% to 70 wt.% of the total mass.
[0398] In another embodiment, the carbon content is 10% to 99.9%, 10% to 99%, 10% to 98%, 50% to 99.9%, 50% to 99%, 50% to 98%, 75% to 99.9%, 75% to 99% or 75% to 98% of the total mass of all components in the carbon material as measured by XPS analysis.
[0399] In another embodiment, the nitrogen content is 0 to 90wt.%, as measured by XPS analysis. In another embodiment, the nitrogen content is 1wt.% to 75wt.% of the total mass. In another embodiment, the nitrogen content is 1wt.% to 50wt.% of the total mass. In another embodiment, the nitrogen content is 1wt.% to 25wt.% of the total mass. In another embodiment, the nitrogen content is 1wt.% to 20wt.% of the total mass. In another embodiment, the nitrogen content is 1wt.% to 10wt.% of the total mass. In another embodiment, the nitrogen content is 1wt.% to 6wt.% of the total mass. In another embodiment, the nitrogen content is 10wt.% to 20wt.% of the total mass. In another embodiment, the nitrogen content is 20wt.% to 30wt.% of the total mass. In another embodiment, the nitrogen content is greater than 30wt.%.
[0400] Carbon and nitrogen content can also be measured by XPS as a ratio of C:N. In one embodiment, the C:N ratio of the composite is 0.001:1 to 1:0.001. In one embodiment, the C:N ratio is 0.01:1 to 1:0.01. In one embodiment, the C:N ratio is 0.1:1 to 1:0.01. In one embodiment, the C:N ratio is 1:0.5 to 1:0.001. In one embodiment, the C:N ratio is 1:0.5 to 1:0.01. In one embodiment, the C:N ratio is 1:0.5 to 1:0.1. In one embodiment, the C:N ratio is 1:0.2 to 1:0.01. In one embodiment, the C:N ratio is 1:0.001 to 1:1. In another embodiment, the C:N ratio is 1:0.001 to 0.01. In another embodiment, the C:N ratio is 1:0.01 to 1:1. In another embodiment, the nitrogen content exceeds the carbon content.
[0401] The carbon and phosphorus content of the composite can be measured by XPS as a ratio of C: P. In one embodiment, the C: P ratio of the composite is 0.001: 1 to 1: 0.001. In one embodiment, the C: P ratio is 0.01: 1 to 1: 0.01. In one embodiment, the C: P ratio is 0.1: 1 to 1: 0.01. In one embodiment, the C: P ratio is 1: 0.5 to 1: 0.001. In one embodiment, the C: P ratio is 1: 0.5 to 1: 0.01. In one embodiment, the C: P ratio is 1: 0.5 to 1: 0.1. In one embodiment, the C: P ratio is 1: 0.2 to 1: 0.01. In one embodiment, the C: P ratio is 1: 0.001 to 1: 1. In another embodiment, the C: P ratio is 1: 0.001 to 0.01. In another embodiment, the C: P ratio is 1: 0.01 to 1: 1. In another embodiment, the nitrogen content exceeds the carbon content.
[0402] XPS can also be used to detect the individual bonds between elements. In the case of a composite, the interface between carbon and silicon can include a C-X bond, where X is the main element (e.g., the C-Si bond of a silicon electrochemical modifier) that forms an alloy with lithium. The presence of C-X can affect the performance of the material. This percentage of C-X bonds in the composite can be characterized using XPS. In one embodiment, the percentage of C-X bonds as measured by XPS is 0% to 50%. In another embodiment, the percentage of C-X bonds is 0% to 10%, 0% to 5%, 0% to 3%, 0% to 2%, 0% to 1%, 1% to 2%, 10% to 50% or greater than 50%. In another embodiment, C-X bonds also produce materials in situ that can form alloys with silicon by electrochemistry.
[0403] The carbon material comprising the composite material may contain sp3 and sp2 hybridized carbon. As is known in the art, the percentage of sp2 hybridization can be measured by XPS using Auger spectroscopy. It is speculated that for less than 100% sp 2 The remaining bonds are sp 3 The carbon material is about 1% sp 2 Hybridized to 100% sp 2 Other embodiments include sp 2 , about 50% to 95% of sp 2 , about 50% to about 75% sp 2 , about 65% to about 95% sp 2 or about 65% of sp 2 of carbon materials.
[0404] In certain embodiments, XPS can be examined to determine the specific properties of a specific bonding structure within a silicon-containing composite. For example, XPS can be examined in a region near 100 eV to determine the details of Si 2p bonding in a silicon structure. In certain embodiments, the silicon material comprises elemental silicon exhibiting an XPS peak at 99.4 eV. In certain embodiments, the silicon material comprises Si3N4 exhibiting an XPS peak at 101.7 eV. In certain embodiments, silicon comprises an organosilicon exhibiting an XPS peak at 102 eV. In certain embodiments, silicon comprises an organosilicon exhibiting an XPS peak at 103.5 eV.
[0405] The composite material can also incorporate a selected electrochemical modifier to optimize the electrochemical performance of the unmodified composite. The electrochemical modifier can be incorporated into the pore structure and / or on the surface of the porous carbon support, in the embedded silicon, or in the final carbon layer or conductive polymer, coating, or in many other ways. For example, in some embodiments, the composite material comprises a coating of an electrochemical modifier (e.g., silicon or Al2O3) on the surface of the carbon material. In some embodiments, the composite material comprises an electrochemical modifier greater than about 100ppm. In certain embodiments, the electrochemical modifier is selected from iron, tin, silicon, nickel, aluminum and manganese.
[0406] In certain embodiments, the electrochemical modifier comprises an element (e.g., silicon, tin, sulfur) having the ability to be lithiated at 3 to 0V relative to lithium metal. In other embodiments, the electrochemical modifier comprises a metal oxide (e.g., iron oxide, molybdenum oxide, titanium oxide) having the ability to be lithiated at 3V to 0V relative to lithium metal. In other embodiments, the electrochemical modifier comprises an element (e.g., aluminum, manganese, nickel, metal phosphate) that cannot be lithiated at 3V to 0V relative to lithium metal. In other embodiments, the electrochemical modifier comprises a non-metallic element (e.g., fluorine, nitrogen, hydrogen). In other embodiments, the electrochemical modifier comprises any of the aforementioned electrochemical modifiers or any combination thereof (e.g., tin-silicon, nickel-titanium oxide).
[0407] The electrochemical modifier can be provided in any number of forms. For example, in some embodiments, the electrochemical modifier comprises a salt. In other embodiments, the electrochemical modifier comprises one or more elements in elemental form, such as elemental iron, tin, silicon, nickel, or manganese. In other embodiments, the electrochemical modifier comprises one or more elements in oxidized form, such as iron oxide, tin oxide, silicon oxide, nickel oxide, aluminum oxide, or manganese oxide.
[0408] In other embodiments, the electrochemical modifier comprises iron. In other embodiments, the electrochemical modifier comprises tin. In other embodiments, the electrochemical modifier comprises silicon. In some other embodiments, the electrochemical modifier comprises nickel. In other embodiments, the electrochemical modifier comprises aluminum. In other embodiments, the electrochemical modifier comprises manganese. In other embodiments, the electrochemical modifier comprises Al2O3. In other embodiments, the electrochemical modifier comprises titanium. In other embodiments, the electrochemical modifier comprises titanium oxide. In other embodiments, the electrochemical modifier comprises lithium. In other embodiments, the electrochemical modifier comprises sulfur. In other embodiments, the electrochemical modifier comprises phosphorus. In other embodiments, the electrochemical modifier comprises molybdenum. In other embodiments, the electrochemical modifier comprises germanium. In other embodiments, the electrochemical modifier comprises arsenic. In other embodiments, the electrochemical modifier comprises gallium. In other embodiments, the electrochemical modifier comprises phosphorus. In other embodiments, the electrochemical modifier comprises selenium. In other embodiments, the electrochemical modifier comprises antimony. In other embodiments, the electrochemical modifier comprises bismuth. In other embodiments, the electrochemical modifier comprises tellurium. In other embodiments, the electrochemical modifier comprises indium.
[0409] Thus, in some embodiments, the composite material comprises more than one carbon allotrope, including hard carbon and a second allotrope selected from materials including, but not limited to, graphite, amorphous carbon (soft and hard), diamond, C60, carbon nanotubes (e.g., single-walled and / or multi-walled), graphene, and carbon fibers. In some embodiments, the second carbon form is graphite. In other embodiments, the second carbon form is soft carbon. The ratio of the carbon material (e.g., hard carbon) to the second carbon allotrope can be adjusted to suit any desired electrochemical application.
[0410] In certain embodiments, the mass ratio of hard carbon to the second carbon allotrope in the composite material is from about 0.01:1 to about 100:1. In other embodiments, the mass ratio of hard carbon to the second carbon allotrope is from about 1:1 to about 10:1 or about 5:1. In other embodiments, the mass ratio of hard carbon to the second carbon allotrope is from about 1:10 to about 10:1. In other embodiments, the mass ratio of hard carbon to the second carbon allotrope is from about 1:5 to about 5:1. In other embodiments, the mass ratio of hard carbon to the second carbon allotrope is from about 1:3 to about 3:1. In other embodiments, the mass ratio of hard carbon to the second carbon allotrope is from about 1:2 to about 2:1.
[0411] Multiple carbon allotropes can be combined in a single composite to further improve electrochemical performance. For example, hard carbon can be blended with graphite and soft carbon to change density and capacity or first cycle efficiency. Three or more carbon allotropes will have a synergistic effect, resulting in unique structures and properties. In certain embodiments, the mass ratio of the hard carbon present in the composite material to the mass sum of all other carbon allotropes is about 0.01:1 to about 100:1. In other embodiments, the mass ratio of the hard carbon in the composite material to the mass sum of all other carbon allotropes is about 1:1 to about 10:1 or about 5:1. In other embodiments, the mass ratio of the hard carbon in the composite material to the mass sum of all other carbon allotropes is about 1:10 to about 10:1. In other embodiments, the mass ratio of the hard carbon in the composite material to the mass sum of all other carbon allotropes is about 1:5 to about 5:1. In other embodiments, the mass ratio of the hard carbon in the composite material to the mass sum of all other carbon allotropes is about 1:3 to about 3:1. In other embodiments, the mass ratio of hard carbon to the sum of the mass of all other carbon allotropes in the composite material is from about 1:2 to about 2:1.
[0412] The electrochemical properties of the composite material can be modified at least in part by the amount of electrochemical modifier in the material, wherein the electrochemical modifier is an alloy material such as silicon, tin, indium, aluminum, germanium, gallium. Therefore, in some embodiments, the composite material comprises at least 0.10%, at least 0.25%, at least 0.50%, at least 1.0%, at least 5.0%, at least 10%, at least 25%, at least 50%, at least 75%, at least 90%, at least 95%, at least 99% or at least 99.5% of the electrochemical modifier. For example, in some embodiments, the composite material comprises 0.5% to 99.5% carbon and 0.5% to 99.5% electrochemical modifier. In a preferred embodiment, the composite material comprises 70%-99% silicon, such as 75% to 95%, such as 80% to 95%. The percentage of the electrochemical modifier is calculated based on weight percentage (wt%). In some other more specific embodiments, the electrochemical modifier comprises iron, tin, silicon, nickel and manganese. In a preferred embodiment, the composite material comprises 70%-99% silicon, such as 75% to 95%, such as 80% to 95%.
[0413] Unmodified carbon material has a purity not previously obtained with hard carbon material. Although not wishing to be bound by theory, it is believed that high-purity unmodified carbon material contributes to excellent electrochemical properties. In some embodiments, unmodified carbon material comprises low total TXRF impurities (excluding any intentionally included electrochemical modifier). Therefore, in some embodiments, the total TXRF impurity content of all other TXRF elements in the carbon material (excluding any intentionally included electrochemical modifier) is less than 1000ppm (as measured by proton induced x-ray emission). In other embodiments, the total TXRF impurity content of all other TXRF elements in the carbon material (excluding any intentionally included electrochemical modifier) is less than 800ppm, less than 500ppm, less than 300ppm, less than 200ppm, less than 150ppm, less than 100ppm, less than 50ppm, less than 25ppm, less than 10ppm, less than 5ppm or less than 1ppm.
[0414] In addition to low levels of unwanted TXRF impurities, the disclosed unmodified carbon materials can include a high total carbon content. In some instances, in addition to carbon, the carbon material can also include oxygen, hydrogen, nitrogen, and optional electrochemical modifiers. In some embodiments, based on weight / weight, the material includes at least 75% carbon, 80% carbon, 85% carbon, at least 90% carbon, at least 95% carbon, at least 96% carbon, at least 97% carbon, at least 98% carbon, or at least 99% carbon. In some other embodiments, based on weight / weight, the carbon material includes less than 10% oxygen, less than 5% oxygen, less than 3.0% oxygen, less than 2.5% oxygen, less than 1% oxygen, or less than 0.5% oxygen. In other embodiments, based on weight / weight, the carbon material includes less than 10% hydrogen, less than 5% hydrogen, less than 2.5% hydrogen, less than 1% hydrogen, less than 0.5% hydrogen, or less than 0.1% hydrogen. In other embodiments, the carbon material contains less than 5% nitrogen, less than 2.5% nitrogen, less than 1% nitrogen, less than 0.5% nitrogen, less than 0.25% nitrogen, or less than 0.01% nitrogen on a weight / weight basis. The oxygen content, hydrogen content, and nitrogen content of the disclosed carbon materials can be determined by combustion analysis. Techniques for determining elemental composition by combustion analysis are well known in the art.
[0415] In some cases, the total ash content of the unmodified carbon material can have an effect on the electrochemical performance of the carbon material. Thus, in some embodiments, the ash content of the carbon material (excluding any intentionally included electrochemical modifier) is 0.1% to 0.001% by weight ash, for example, in some specific embodiments, the ash content of the carbon material (excluding any intentionally included electrochemical modifier) is less than 0.1%, less than 0.08%, less than 0.05%, less than 0.03%, less than 0.025%, less than 0.01%, less than 0.0075%, less than 0.005% or less than 0.001%.
[0416] In other embodiments, the composite material comprising the porous silicon material comprises less than 500 ppm of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and less than 0.08% ash content (excluding any intentionally included electrochemical modifiers). In further embodiments, the composite material comprises less than 300 ppm of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and less than 0.05% ash content (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises less than 200 ppm of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and less than 0.05% ash content (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises less than 200 ppm of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and less than 0.025% ash content (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises less than 100 ppm of total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and less than 0.02% ash content (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises less than 50 ppm of total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and less than 0.01% ash content (excluding any intentionally included electrochemical modifiers).
[0417] In other embodiments, the composite material comprising the porous silicon material comprises greater than 500 ppm of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 0.08% (excluding any intentionally included electrochemical modifiers). In further embodiments, the composite material comprises greater than 5000 ppm of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 0.5% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 1% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 0.5% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 2% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 1% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 3% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 2% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 4% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 3% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 5% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 4% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 6% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 5% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 7% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 6% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 8% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 7% (excluding any intentionally included electrochemical modifiers). In other further embodiments, the composite material comprises greater than 9% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and an ash content of greater than 8% (excluding any intentionally included electrochemical modifiers).In other further embodiments, the composite material comprises greater than 10% of the total TXRF impurity content of all other elements (excluding any intentionally included electrochemical modifiers) and greater than 9% ash content (excluding any intentionally included electrochemical modifiers).
[0418] The amount of a separate TXRF impurity present in the disclosed composite material (comprising a porous silicon material) can be determined by proton induced X-ray emission. A separate TXRF impurity can contribute to the overall electrochemical performance of the disclosed composite material in different ways. Therefore, in some embodiments, the level of sodium present in the composite material is less than 1000ppm, less than 500ppm, less than 100ppm, less than 50ppm, less than 10ppm, or less than 1ppm. In some embodiments, the level of magnesium present in the composite material is less than 1000ppm, less than 100ppm, less than 50ppm, less than 10ppm, or less than 1ppm. In some embodiments, the level of aluminum present in the composite material is less than 1000ppm, less than 100ppm, less than 50ppm, less than 10ppm, or less than 1ppm. In some embodiments, the level of silicon present in the composite material is less than 500ppm, less than 300ppm, less than 100ppm, less than 50ppm, less than 20ppm, less than 10ppm, or less than 1ppm. In some embodiments, the level of phosphorus present in the composite material is less than 1000ppm, less than 100ppm, less than 50ppm, less than 10ppm, or less than 1ppm. In some embodiments, the level of sulfur present in the composite material is less than 1000ppm, less than 100ppm, less than 50ppm, less than 30ppm, less than 10ppm, less than 5ppm, or less than 1ppm. In some embodiments, the level of chlorine present in the composite material is less than 1000ppm, less than 100ppm, less than 50ppm, less than 10ppm, or less than 1ppm. In some embodiments, the level of potassium present in the composite material is less than 1000ppm, less than 100ppm, less than 50ppm, less than 10ppm, or less than 1ppm. In other embodiments, the level of calcium present in the composite material is less than 100ppm, less than 50ppm, less than 20ppm, less than 10ppm, less than 5ppm, or less than 1ppm. In some embodiments, the level of chromium present in the composite material is less than 1000 ppm, less than 100 ppm, less than 50 ppm, less than 10 ppm, less than 5 ppm, less than 4 ppm, less than 3 ppm, less than 2 ppm, or less than 1 ppm. In other embodiments, the level of iron present in the composite material is less than 50 ppm, less than 20 ppm, less than 10 ppm, less than 5 ppm, less than 4 ppm, less than 3 ppm, less than 2 ppm, or less than 1 ppm. In other embodiments, the level of nickel present in the composite material is less than 20 ppm, less than 10 ppm, less than 5 ppm, less than 4 ppm, less than 3 ppm, less than 2 ppm, or less than 1 ppm.In some other embodiments, the level of copper present in the composite material is less than 140ppm, less than 100ppm, less than 40ppm, less than 20ppm, less than 10ppm, less than 5ppm, less than 4ppm, less than 3ppm, less than 2ppm, or less than 1ppm. In other embodiments, the level of zinc present in the composite material is less than 20ppm, less than 10ppm, less than 5ppm, less than 2ppm, or less than 1ppm. In other embodiments, the sum of all other TXRF impurities present in the composite material (excluding any intentionally included electrochemical modifiers) is less than 1000ppm, less than 500ppm, less than 300ppm, less than 200ppm, less than 100ppm, less than 50ppm, less than 25ppm, less than 10ppm, or less than 1ppm. As described above, in some embodiments, other impurities such as hydrogen, oxygen, and / or nitrogen may be present at a level of less than 10% to less than 0.01%.
[0419] In some embodiments, the unmodified composite material comprising the porous silicon material comprises unwanted TXRF impurities that are close to or below the detection limit of proton induced X-ray emission analysis. For example, in some embodiments, the unmodified composite material comprises less than 50 ppm of sodium, less than 15 ppm of magnesium, less than 10 ppm of aluminum, less than 8 ppm of silicon, less than 4 ppm of phosphorus, less than 3 ppm of sulfur, less than 3 ppm of chlorine, less than 2 ppm of potassium, less than 3 ppm of calcium, less than 2 ppm of scandium, less than 1 ppm of titanium, less than 1 ppm of vanadium, less than 0.5 ppm of chromium, less than 0.5 ppm of manganese, less than 0.5 ppm of iron, less than 0.25 ppm of less than 0.25 ppm of cobalt, less than 0.25 ppm of nickel, less than 0.25 ppm of copper, less than 0.5 ppm of zinc, less than 0.5 ppm of gallium, less than 0.5 ppm of germanium, less than 0.5 ppm of arsenic, less than 0.5 ppm of selenium, less than 1 ppm of bromine, less than 1 ppm of rubidium, less than 1.5 ppm of strontium, less than 2 ppm of yttrium, less than 3 ppm of zirconium, less than 2 ppm of niobium, less than 4 ppm of molybdenum, less than 4 ppm of technetium, less than 7 ppm of rubidium, less than 6 ppm of rhodium, less than 6 ppm palladium, less than 9ppm silver, less than 6ppm cadmium, less than 6ppm indium, less than 5ppm tin, less than 6ppm antimony, less than 6ppm tellurium, less than 5ppm iodine, less than 4ppm cesium, less than 4ppm barium, less than 3ppm lanthanum, less than 3ppm cerium, less than 2ppm praseodymium, less than 2ppm neodymium, less than 1.5ppm promethium, less than 1ppm samarium, less than 1ppm europium, less than 1ppm gadolinium, less than 1ppm terbium, less than 1ppm Dysprosium, less than 1 ppm tantalum, less than 1 ppm erbium, less than 1 ppm thulium, less than 1 ppm ytterbium, less than 1 ppm lutetium, less than 1 ppm hafnium, less than 1 ppm tantalum, less than 1 ppm tungsten, less than 1.5 ppm rhenium, less than 1 ppm osmium, less than 1 ppm iridium, less than 1 ppm platinum, less than 1 ppm silver, less than 1 ppm mercury, less than 1 ppm thallium, less than 1 ppm lead, less than 1.5 ppm bismuth, less than 2 ppm thorium, or less than 4 ppm uranium.
[0420] In some embodiments, the unmodified composite material comprising porous silicon material comprises unwanted TXRF impurities close to or below the detection limit of proton induced X-ray emission analysis. In some specific embodiments, the unmodified composite material comprises less than 100 ppm of sodium, less than 300 ppm of silicon, less than 50 ppm of sulfur, less than 100 ppm of calcium, less than 20 ppm of iron, less than 10 ppm of nickel, less than 140 ppm of copper, less than 5 ppm of chromium and less than 5 ppm of zinc, as measured by TXRF. In other specific embodiments, the composite material comprises less than 50 ppm of sodium, less than 30 ppm of sulfur, less than 100 ppm of silicon, less than 50 ppm of calcium, less than 10 ppm of iron, less than 5 ppm of nickel, less than 20 ppm of copper, less than 2 ppm of chromium and less than 5 ppm of zinc.
[0421] In other specific embodiments, the unmodified composite material comprising porous silicon material comprises less than 50 ppm sodium, less than 50 ppm silicon, less than 30 ppm sulfur, less than 10 ppm calcium, less than 2 ppm iron, less than 1 ppm nickel, less than 1 ppm copper, less than 1 ppm chromium, and less than 1 ppm zinc.
[0422] In some other specific embodiments, the unmodified composite material comprising porous silicon material comprises less than 100 ppm sodium, less than 50 ppm magnesium, less than 50 ppm aluminum, less than 10 ppm sulfur, less than 10 ppm chlorine, less than 10 ppm potassium, less than 1 ppm chromium, and less than 1 ppm manganese.
[0423] In certain embodiments, a composite material comprising a porous silicon material comprises carbon and two or more different electrochemical modifiers. In embodiments, the composite material comprises silicon and one or more of the following substances (or combinations thereof): phosphorus, nitrogen, sulfur, boron or aluminum. In certain embodiments, the composite material comprises carbon, silicon and 1%-20% of a Group 13 element or a combination thereof. In certain other embodiments, the composite material comprises carbon, silicon and 1%-20% of a Group 15 element or a combination thereof. In certain other embodiments, the composite material comprises carbon, silicon and 1%-20% of lithium, sodium or potassium or a combination thereof. In certain other embodiments, the composite material comprises carbon, silicon and 1%-20% of lithium, sodium or potassium or a combination thereof. In certain other embodiments, the composite material comprises carbon, silicon and 1%-20% of lithium, sodium or potassium or a combination thereof.
[0424] The particle size of the composite material can expand upon lithiation compared to the non-lithiation state. For example, the expansion factor is defined as the ratio of the average particle size of the particles of the composite material comprising the porous silicon material upon lithiation divided by the average particle size under non-lithiation conditions. As described in the art, such expansion factors can be relatively large for previously known non-optimal silicon-containing materials, for example, about 4 (corresponding to a 400% volume expansion upon lithiation). The inventors have discovered that composite materials comprising porous silicon materials can exhibit a lower degree of expansion, for example, the expansion factor can vary from 3.5 to 4, 3.0 to 3.5, 2.5 to 3.0, 2.0 to 2.5, 1.5 to 2.0, 1.0 to 1.5.
[0425] It is envisioned that the composite material in some embodiments will contain a portion of trapped pore volume, i.e., void volume that is inaccessible to nitrogen as detected by nitrogen adsorption measurements. Without being bound by theory, this trapped pore volume is important because it provides volume into which silicon can expand upon lithiation.
[0426] Therefore, the composite material herein comprises a ratio of a pore volume cut-off to a measured pore volume (as determined by nitrogen adsorption) of 0.01:1 to 100:1. In certain embodiments, the composite material comprises a ratio of a pore volume cut-off to a measured pore volume of 0.01:1 to 0.05:1. In certain embodiments, the composite material comprises a ratio of a pore volume cut-off to a measured pore volume of 0.05:1 to 0.1:1. In certain embodiments, the composite material comprises a ratio of a pore volume cut-off to a measured pore volume of 0.1:1 to 0.2:1. In certain embodiments, the composite material comprises a ratio of a pore volume cut-off to a measured pore volume of 0.2:1 to 0.5:1. In certain embodiments, the composite material comprises a ratio of a pore volume cut-off to a measured pore volume of 0.5:1 to 1:1. In certain embodiments, the composite material comprises a ratio of a pore volume cut-off to a measured pore volume of 1:1 to 2:1. In certain embodiments, the composite material comprises a ratio of a pore volume cut-off to a measured pore volume of 2:1 to 5:1. In certain embodiments, the composite material comprises a ratio of the retained pore volume to the measured pore volume of 5: 1 to 10: 1. In certain embodiments, the composite material comprises a ratio of the retained pore volume to the measured pore volume of 10: 1 to 20: 1. In certain embodiments, the composite material comprises a ratio of the retained pore volume to the measured pore volume of 20: 1 to 50: 1. In certain embodiments, the composite material comprises a ratio of the retained pore volume to the measured pore volume of 50: 1 to 100: 1.
[0427] In certain preferred embodiments, the composite particles comprise a ratio of trapped void volume to silicon volume of 0.1: 1 to 10: 1. For example, the composite particles comprise a ratio of trapped void volume to silicon volume of 1: 1 to 5: 1 or 5: 1 to 10: 1. In preferred embodiments, the composite particles comprise a ratio of trapped void volume to silicon volume of 2: 1 to 5: 1 or about 3: 1 to effectively accommodate maximum silicon expansion upon lithiation. Example
[0428] Example 1
[0429] Performance Model of New Composite Materials
[0430] A full cell model was developed to simulate the approximate size and energy of an 18650-type cell. LCO was selected as the default cathode. The model accounts for material properties (density, filler, volume expansion), electrochemical performance characteristics (operating voltage, capacity, irreversible capacity), and cell-level variations (electrolyte required, void volume), etc. Table 2 compares cell-level properties from commercially available cells and outputs from the model. Similar values were calculated using the model, providing confidence in the model's ability to represent system-level variations.
[0431] Table 2. Validation of performance models for commercial batteries
[0432]
[0433] Second, the values in Table 3 demonstrate the cell level performance changes when the anode is modified to include the novel composite materials disclosed herein. At the cell level, there is a significant increase in volumetric energy density (~43%), although there is a limited change in Wh / kg due in part to other SEI losses. Without being bound by theory, pre-lithiation further increases the weight energy density.
[0434] Table 3. Performance models applied to new composite materials
[0435]
[0436] Example 2
[0437] Examples of porous carbon scaffold materials
[0438] A variety of porous carbon scaffold materials are available for investigation. A range of carbon physicochemical properties are listed in Table 4.
[0439] Carbon 1 is a commercial carbon; in addition to the properties reported in Table 2, Dv100 is 11.62 microns, Dv10 is 0.6 microns, and tap density is 0.27 g / cm 3, pH was 5.3, ash content was 0.016%, and the sum of all impurities determined by PIXE was as follows: silicon = 48.680 ppm, calcium = 12.910 ppm, iron = 22.830 ppm, nickel = 3.604 ppm, chromium = 5.521.
[0440] Carbon 2 was commercial carbon; in addition to the properties reported in Table 1, Dv100 was 18.662 microns, Dv10 was 1.2 microns, span of particle size was 1.194, uniformity of particle size distribution was 0.367, and tap density was 0.2347 g / cm 3 , pH was 6.709, ash content was 0.005%, and the sum of all impurities determined by PIXE was as follows: calcium = 20.5 ppm, iron = 4.14 ppm, zinc = 2.24 ppm, titanium = 6.7 ppm.
[0441] Carbon 3 is a commercial carbon; in addition to the properties reported in Table 1, Dv100 is 21.2 microns, Dv10 is 3.8 microns, span of particle size is 1.261, uniformity of particle size distribution is 0.387, and tap density is 0.52 / cm 3 , pH was 9.418, ash content was 0.075%, and the sum of all impurities determined by PIXE was as follows: silicon = 29.012 ppm, iron = 3.183 ppm, zinc = 0.555, potassium = 6.952 ppm.
[0442] Carbon 4 is produced from resorcinol formaldehyde resin as follows. First, 388 g of deionized water is mixed with 26 mL of glacial acetic acid and 156 g of resorcinol in a 1 L beaker. The solution is mixed on a stirring plate until all of the resorcinol is dissolved. The solution is continuously mixed, and 2.2 g of ammonium acetate is added and dissolved. Secondly, 212 mL of formaldehyde solution (37 wt % formaldehyde in water) is added to the stirred solution. The solution is allowed to stir for 5-10 minutes. The final solution is then poured into a 1 L polypropylene bottle and placed at 85 ° C for 24 hours. The resulting solidified and solid resin is then freeze-dried to remove all excess water, acid and formaldehyde to produce a cryogel, which is then pyrolyzed according to the method described herein.
[0443] Carbon 5 and Carbon 6 are commercial carbons.
[0444] Carbon 7 is a commercial carbon; in addition to the properties reported in Table 1, Dv100 is 35.2 microns, Dv10 is 2.69 microns, the span of particle size is 1.765, the uniformity of particle size distribution is 0.539, and the tap density is 1.015 g / cm 3 -1.020g / cm 3 , pH is 3.099.
[0445] Carbon 8 is commercial carbon.
[0446] Carbon 9 was produced from urea-citric acid resin as follows. First, 400 g of pre-dried urea was mixed with 200 g of pre-dried citric acid. The mixture was then ground together into a very fine powder. The powder mixture was poured into a curing vessel and placed at 140° C. for 24 hours. The resulting cured and solid resin was then pyrolyzed according to the method described herein.
[0447] Carbon 10 is a commercial carbon; in addition to the properties reported in Table 1, Dv100 is 18.6 microns, Dv10 is 2.48 microns, the span of particle size is 1.348, the uniformity of particle size distribution is 0.406, and the tap density is 0.32 g / cm 3 , pH is 7.616.
[0448] Carbon 11 is graphite.
[0449] Carbon 12 is commercial carbon. Carbon 13 is commercial carbon 1, which was then heated to 1100° C. for 1 hour in argon with 5 mol % H 2 gas.
[0450] Carbon 14 is a hard carbon produced according to the procedures described herein in a solvent-free process employing a polyol and an organic acid.
[0451] Carbon 15 is a hard carbon produced according to the procedure described herein using an epoxy compound and phosphoric acid.
[0452] Table 4. Various properties of the carbon according to Example 2.
[0453]
[0454] Example 3
[0455] Various composite materials produced via silicon deposition on porous silicon scaffolds
[0456] Various composite materials were produced according to the present disclosure, and in this example, silicon was embedded in a porous carbon support via a chemical vapor deposition technique using silane gas, as generally described herein. For this particular example, the samples were processed in a tube furnace with a 2 mol% silane gas flow mixed with nitrogen and maintained for various times and temperatures as described. An overview of the sample processing is shown in Table 5. The final loading of silicon in the silicon-carbon composite can be determined as known in the art, for example, by observing the weight loss using thermogravimetric analysis (TGA) using techniques known in the art.
[0457] Table 5. Summary of composite samples produced according to Example 3.
[0458]
[0459]
[0460] Example 4
[0461] Various composite materials were produced via silicon deposition on a porous silicon support followed by chemical vapor deposition to create a carbon layer around the particles.
[0462] Certain samples from the previous examples were further processed to produce a surface carbon layer via chemical vapor deposition, also achieved in a tube furnace, using propane gas at high temperature for a certain period of time, as described. The preparation data are summarized in Table 6.
[0463] Table 6. Summary of composite samples produced according to Example 4.
[0464] sample Propane set temperature (℃) Time (min.) 9 850 30 10 850 30 11 800 15 12 800 15 13 800 10 14 800 15 39 750 30 40 750 30 41 750 30 42 750 30 43 750 10 44 750 10 57 750 30 58 800 30 59 800 30
[0465] Example 5
[0466] Physical and chemical properties of various composite materials.
[0467] The surface area, pore volume and pore volume distribution of various samples according to the above examples were determined by nitrogen adsorption as described within this disclosure. Table 7 summarizes the data.
[0468] Table 7. Physicochemical properties of various composite samples.
[0469]
[0470]
[0471] Example 6
[0472] Electrochemical properties of various composite materials
[0473] Various composites were produced according to the above examples. The electrochemical properties of the samples were studied. The data of the materials tested as anodes in half-cells are shown in Table 8, wherein the anodes comprise active materials, binders, and conductive carbon, which account for 60%, 20%, and 20% of the electrode mass, respectively. These samples were assembled into half-cells and tested for five cycles at a rate of C / 10, and further cycled at C / 5. The electrochemical test data are summarized in Table 8. Unless otherwise stated, the average coulombic efficiency and capacity retention from the 7th cycle to the 25th cycle are reported, and the capacity of the 6th cycle is reported.
[0474] Table 8. Electrochemical properties of various composite samples.
[0475]
[0476]
[0477] N / A means information is not available or pending.
[0478] Example 7
[0479] Electrochemical characterization of various composite materials in blends with graphite.
[0480] Various composites were produced according to the above examples. The electrochemical properties of the selected numbered samples were studied. Table 9 shows data for materials tested as anodes in half-cells, wherein the anodes comprise active materials, binders, and conductive carbon, which account for 80%, 10%, and 10% of the electrode mass, respectively. The active material also comprises graphite, and the % of graphite and the % of the sample are adjustable to achieve an approximate capacity of 500mAh / g-800mAh / g. For sample 13, the electrode comprises 24% of sample 13% and 76% of graphite. For sample 14, the electrode comprises 30% of sample 14 and 70% of graphite. For sample 15, the electrode comprises 19% of sample 15% and 81% of graphite. For sample 32, the electrode comprises 24% of sample 32% and 76% of graphite. For sample 33, the electrode comprises 27% of sample 33% and 73% of graphite. For sample 35, the electrode comprises 24% of sample 35% and 76% of graphite. For sample 50, the electrode contained 25% sample 50 and 75% graphite. These samples were assembled into half cells and tested for five cycles at a rate of C / 10 and further cycled at C / 5. The electrochemical test data are summarized in Table 8. Unless otherwise stated, the average coulombic efficiency and capacity retention from the 7th cycle to the 25th cycle are reported, and the capacity of the 6th cycle is reported.
[0481] Table 9. Electrochemical properties of various composite samples in graphite blends.
[0482]
[0483] Example 8
[0484] The pores of the microporous carbon material are filled via silicon deposition.
[0485] The pore volume distribution of the microporous carbon (Carbon 3) was examined before and after treatment with silane for 120 min (Sample 31) or 150 min (Sample 34) to produce a composite material comprising silicon and carbon. The pore volume distributions of these samples are described in Figure 2 As can be seen, there is a significant decrease in the pore volume in the micropore range, consistent with the filling of the micropores within the carbon scaffold with silicon.
[0486] Example 9
[0487] The pores of the mixed microporous, mesoporous and macroporous carbon materials are filled via silicon deposition.
[0488] The pore volume distribution of the carbon with mixed microporous, mesoporous and macroporous properties (Carbon 2) was examined before and after treatment with silane for 60 min (Sample 11) or 90 min (Sample 9) to produce a composite material comprising silicon and carbon. The pore volume distribution of these samples is described in Figure 3 As can be seen, there is a significant decrease in the pore volume of the micropore range, mesopore range, and macropore range, consistent with filling the micropores, mesopores, and macropores within the carbon scaffold with silicon.
[0489] Example 10
[0490] The pores of the microporous carbon material are filled via silicon deposition.
[0491] The pore volume distribution of the carbon having macroporous properties (Carbon 4) was examined before and after treatment with silane for 90 minutes (Sample 8), or after treatment with silane for 90 minutes and with propane for an additional 30 minutes (Sample 10), or after treatment with silane for 120 minutes and with propane for an additional 10 minutes (Sample 13) to produce a composite material comprising silicon and carbon. The pore volume distributions of these samples are described in Figure 4 As can be seen, there is a significant reduction in pore volume in the macropore range, consistent with filling the macropores within the carbon scaffold with silicon. In addition, in the case of subsequent propane treatment (additional carbon forms a layer on the particle surface), there is additional loss in macropore volume, without being bound by theory, this observation is consistent with providing a CVD carbon coating for capping off the macropores, and a reduction in macropore volume.
[0492] Therefore, it is envisioned that the composite material in some embodiments will contain some trapped pore volume, i.e., void volume that is inaccessible to nitrogen, as detected by nitrogen adsorption measurements. Without being bound by theory, this trapped pore volume is important in that it provides volume into which silicon can expand upon lithiation.
[0493] Embodiment 11
[0494] The pores in the porous carbon scaffold were decapsulated via CVD.
[0495] Carbon coating a porous material by thermal chemical vapor deposition will cap the macropores rather than fill the pores with carbon. This is best observed by carbon CVD on pure macroporous carbon (Carbon 3). As can be seen in the table below, the specific surface area of the material ranges from 1720 m 2 / g down to 6m 2 / g. The pore volume is also reduced to negligible values. Evidence for coverage can be seen in the nitrogen pycnometry data, particle density and acetone pycnometry. The particles were measured by compressing the powder in a mold at a pressure of 2000 kg / cm2. The acetone pycnometry was measured by immersing the powder in acetone and measuring the liquid displacement. The starting apparent skeletal density of the pure microporous carbon was 2.24 g / cc. After CVD of the carbon on the material, the apparent skeletal density dropped to 1.49 g / cc, indicating that void space was created in the material. The data are summarized in Table 10 and graphically shown as pore volume distribution in Figure 5 Displayed in.
[0496] Table 10. Examples of covering micropores in carbon scaffold particles.
[0497]
[0498] Example 12
[0499] Electrochemical characterization of composite materials in full-cell coin cells.
[0500] Check the electrochemical properties of the composite sample used as the anode material, the anode contains 80% active material, 10% conductive carbon and 10% binder, wherein the active agent also contains 30% of the sample to be tested and 70% graphite. Alternatively, check the electrochemical properties of the composite sample for the anode, the anode contains 80% active material, 10% conductive carbon and 10% binder. Alternatively, check the electrochemical properties of the composite sample for the anode, the anode contains 90% active material, 5% conductive carbon and 5% binder. Alternatively, check the electrochemical properties of the composite sample for the anode, the anode contains 90% active material, 2% conductive carbon and 8% binder. Alternatively, check the electrochemical properties of the composite sample for the anode, the anode contains 93% active material, 2% conductive carbon and 5% binder. The active material herein contains the sample to be tested, such as a silicon-carbon composite and graphite, wherein the active material contains 10%-60% silicon-carbon composite and 40%-90% graphite.
[0501] The full cell coin cell was constructed as follows. The anode and cathode were paired by collecting the half-cell absolute 5th cycle insert (anode) capacity and the first cycle extract (cathode) capacity, and the electrodes were matched to meet the 5%-15% excess anode ratio. The coin cell was constructed using a LiNiCoAlO anode. After fabrication, the cell was electrochemically formed with 5 charge / discharge sequences at 2.0V-4.2V. The first two sequences were performed at C / 10 current at 4.2V maintaining C / 20, and the next three sequences were performed at C / 5, also maintaining C / 20. To evaluate the cycling stability, the cell was cycled at C / 2 at 2.0V-4.2V, maintaining C / 20.
[0502] Alternatively, the cells were electrochemically formed with 2 charge / discharge sequences at 2.5V-4.2V, wherein the first sequence was performed at C / 10 current at 4.2V holding C / 20. The subsequent sequence was performed at C / 5 holding C / 10. To evaluate the cycling stability, the cells were cycled at 2.0V-4.2V at 1C, holding C / 20. During the cycling stability stage, some of these cells had periodic cycles run at C / 10 at 2.5V-4.2V, and holding C / 5 (at a rate of once every 20 cycles).
[0503] Example 13
[0504] Calculation of the mean free path of the deposition gas.
[0505] The mean free path (MFP) for various temperatures, pressures and gases was calculated for molecules of the 150 pm or 300 pm class according to the kinetic theory of gases known in the art (see Table 11). Other calculations are envisioned as known in the art.
[0506] Table 11. Example of mean free path calculation for deposition gases.
[0507] Gas molecule size Temperature (C) Pressure(kpa) MFP(nm) 150pm 400 10.1 2301 150pm 400 101 231 150pm 500 10.1 2643 150pm 500 101 264 150pm 600 10.1 2985 150pm 600 101 298 300pm 400 10.1 575 300pm 400 101 58 300pm 500 10.1 661 300pm 500 101 66 300pm 600 10.1 746 300pm 600 101 75
[0508] Embodiment 14
[0509] Expansion measurement of various anode materials
[0510] The anode is subjected to the following procedures generally described herein. The anode material to be tested is generally diluted with graphite to achieve 400mAh / g-700mAh / g. The graphite percentage in the blend of each sample is described below, and in such cases, the electrode preparation is generally composed of 80% active material (material in the graphite blend), 10% conductive enhancer such as SuperP, and 10% adhesive such as SBR-CMC. In some cases, the material is tested in the absence of graphite, and such cases generally include 80% active material, 20% conductive enhancer, and 20% adhesive in the anode preparation. In some cases, in the anode preparation, the anode generally includes 90% active material, 5% conductive enhancer, and 5% adhesive. The electrode used is 1M LiPF6 EC:DEC+10%FEC, and lithium metal is used as cathode to construct a half-cell button cell. As generally described herein, the battery is tested by electrochemistry. The voltage was cycled at 0.8V to 0.005V for 5 cycles at a C / 10 rate, followed by 25 cycles at a C / 5 rate. After the cycle, the button cell was raised to 100% of the state of charge at the final moment, then disassembled, and the anode thickness was measured compared to the initial thickness before the electrochemical test. The different types of samples produced were: graphite-based, carbon-composite nano-silicon, carbon-composite nano-featured silicon, carbon-composite silicon oxide (SiOx), and carbon-silicon composites (C-Si-C composites) produced by the final carbon coating obtained by hydrocarbon chemical vapor deposition via silane deposition on a porous carbon support. Samples were produced according to the general procedure described elsewhere herein. Also included were some samples containing bare nano-silicon, which was not composited with carbon. Unless otherwise stated, capacity (weight capacity or volume capacity) refers to the capacity of unlithiated materials. These samples are summarized in Table 12 below.
[0511] For the uncompounded (i.e., so-called bare) nano-silicon relative to the same nano-silicon in the silicon-carbon composite material, Figure 6 The data of anode expansion relative to weight capacity is shown in . As can be seen, the bare material expands significantly with increasing weight capacity in the blend of nano-silicon and graphite. In contrast, when nano-silicon is composited with carbon, there is a significantly reduced expansion for the carbon composite nano-silicon and graphite blend. Figure 7 Anode expansion versus gravimetric capacity is shown for various samples. For anode expansion versus volumetric capacity (in the unlithiated state), data are shown in Figure 8The carbon composite nano-silicon samples, carbon composite nano-featured silicon samples and carbon composite silicon oxide (SiOx) samples showed similar expansion as their respective weight contents blended with graphite increased. In contrast, it was surprisingly and unexpectedly found that the expansion of the samples containing carbon silicon composite (C-Si-C) produced via silane deposition on a porous carbon support and then a final carbon coating achieved via hydrocarbon chemical vapor deposition was significantly reduced.
[0512]
[0513] Without being bound by theory, the lower expansion of the C-Si-C samples translates into a reduced tendency for the material to crack (i.e., unstable SEI information when cycled in a battery). It is envisioned from the data that the C-Si-C composite can exhibit, for example, less than 30% anode expansion and greater than 400 mAh / g gravimetric capacity when blended with graphite or another suitable matrix or tested as a pure material. In certain embodiments, the C-Si-C composite can exhibit less than 30% anode expansion and greater than 500 mAh / g gravimetric capacity. In certain embodiments, the C-Si-C composite can exhibit less than 30% anode expansion and greater than 600 mAh / g gravimetric capacity. In certain embodiments, the C-Si-C composite can exhibit less than 30% anode expansion and greater than 800 mAh / g gravimetric capacity. In certain embodiments, the C-Si-C composite can exhibit less than 30% anode expansion and greater than 1000 mAh / g gravimetric capacity.
[0514] In other embodiments, the C-Si-C composite may exhibit, for example, less than 40% anode expansion and a weight capacity of greater than 500 mAh / g when blended with graphite or another suitable matrix or tested as a pure material. In other embodiments, the C-Si-C composite may exhibit less than 40% anode expansion and a weight capacity of greater than 600 mAh / g. In other embodiments, the C-Si-C composite may exhibit less than 40% anode expansion and a weight capacity of greater than 800 mAh / g. In other embodiments, the C-Si-C composite may exhibit less than 40% anode expansion and a weight capacity of greater than 1000 mAh / g.
[0515] In other embodiments, the C-Si-C composite can exhibit, for example, less than 50% anode expansion and greater than 800 mAh / g gravimetric capacity when blended with graphite or another suitable matrix or tested as a pure material. In other embodiments, the C-Si-C composite can exhibit, for example, less than 60% anode expansion and greater than 1000 mAh / g gravimetric capacity when blended with graphite or another suitable matrix or tested as a pure material.
[0516] In some embodiments, the C-Si-C composite can exhibit, for example, when blended with graphite or another suitable matrix or when tested as a pure material, less than 20% anode expansion and a weight capacity of greater than 500 mAh / g. In other embodiments, the C-Si-C composite can exhibit less than 20% anode expansion and a weight capacity of greater than 600 mAh / g. In other embodiments, the C-Si-C composite can exhibit less than 20% anode expansion and a weight capacity of greater than 800 mAh / g. In other embodiments, the C-Si-C composite can exhibit less than 20% anode expansion and a weight capacity of greater than 1000 mAh / g.
[0517] Figure 8 Data showing expansion of the samples versus volumetric capacity. It can be seen that the carbon composite nano-silicon sample, the carbon composite nano-featured silicon sample, and the carbon composite silicon oxide (SiOx) sample show similar expansion as the weight capacity of their respective blends with graphite increases. A highly surprising and unexpected discovery is that the C-Si-C sample shows a highly flat dependence on expansion on volumetric capacity.
[0518] Without being bound by theory, the lower expansion of the C-Si-C samples translates into a reduced tendency for the material to crack (i.e., an unstable SEI signal when cycled in a battery). It is envisioned from the data that C-Si-C composites may exhibit, for example, less than 30% anode expansion and greater than 400 mAh / cm when blended with graphite or another suitable matrix or when tested as pure material. 3 In certain embodiments, the C-Si-C composite can exhibit less than 30% anode expansion and greater than 500 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 30% anode expansion and greater than 600 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 30% anode expansion and greater than 800 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 30% anode expansion and greater than 1000 mAh / cm 3 volume capacity.
[0519] In other embodiments, the C-Si-C composite can exhibit, for example, less than 40% anode expansion and greater than 400 mAh / cm2 when blended with graphite or another suitable matrix or when tested as a pure material. 3In certain embodiments, the C-Si-C composite can exhibit an anode expansion of less than 40% and a capacity of greater than 500 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 40% anode expansion and greater than 600 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 40% anode expansion and greater than 800 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 40% anode expansion and greater than 1000 mAh / cm 3 volume capacity.
[0520] In other embodiments, the C-Si-C composite can exhibit, for example, less than 50% anode expansion and greater than 400 mAh / cm2 when blended with graphite or another suitable matrix or when tested as a pure material. 3 In certain embodiments, the C-Si-C composite can exhibit less than 50% anode expansion and greater than 500 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 50% anode expansion and greater than 600 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 50% anode expansion and greater than 800 mAh / cm 3 In certain embodiments, the C-Si-C composite can exhibit less than 50% anode expansion and greater than 1000 mAh / cm 3 volume capacity.
[0521] Embodiment 15
[0522] Cycling data of various samples in Li-ion full cells.
[0523] The full-cell button cell was constructed as a sample of graphite, carbon-composite nanosilicon, carbon-composite silicon oxide (SiOx), and a sample (C-Si-C) containing a carbon-silicon composite produced by a final carbon coating deposited on a porous carbon support via silane and then achieved via hydrocarbon chemical vapor deposition. The cathode material was NCA, and the electrolyte was 1M LiPF6 EC:DEC+10% FEC. The anode capacity was about 650mAh / g, as measured in a half-cell. Cycling was achieved at a rate of C / 2, and the voltage window was 2.0V to 4.2V, and I / 2 was maintained. Fig. 9The cycling stability data is described in terms of Wh / L relative to the average data for graphite. The coulombic efficiency of the C-Si-C sample was 0.9999 + / - 0.0016 (n = 5 cells).
[0524] Example 16
[0525] The pores of the mixed microporous and mesoporous carbon materials are filled via silicon deposition.
[0526] The pore volume distribution of carbon (Carbon 13) containing micropores and mesopores was examined before and after treatment with 2 mol% silane at 380 sccm flow and 450°C for 60 min or 120 min to produce a composite material containing silicon and carbon. The pore volume distribution of these samples is described in Fig.10 As can be seen, there is a significant reduction in pore volume in the micropore range and the mesopore range, consistent with filling the micropores and mesopores with silicon. The data show that the reduction in micropores is more significant than the reduction in mesopores, indicating that the preferential deposition of silicon helps reduce mesopores more than micropores.
[0527] The same conclusion can be drawn from the data of the pore volume distribution of various samples. The pore volume distribution measured by the porous carbon support containing 41% of silicon loaded on the porous support contains 48% of micropores, 52% of mesopores and 0% of macropores. The pore volume distribution measured by the sample treated with silane for 60min (causing 26% of silicon loaded on the porous support) contains 45% of micropores, 54% of mesopores and 1% of macropores. These values are very similar to the starting support. On the contrary, the pore volume distribution measured by the sample treated with silane for 120min (causing 41% of silicon loaded on the porous support) contains 5% of micropores, 45% of mesopores and 50% of macropores. In terms of percentage reduction, the micropore volume of the sample treated with silane for 60min (causing 26% of silicon loaded on the porous support) shows a 58% reduction in micropore volume compared with the starting support, and shows a 79% reduction in micropore volume compared with the starting support. In terms of percentage reduction, the sample treated with silane for 120 min (resulting in 41% silicon loading on the porous scaffold) exhibited a 100% reduction in micropore volume compared to the starting scaffold and a 99% reduction in micropore volume compared to the starting scaffold.
[0528] Embodiment 17
[0529] Gravimetric data indicated coverage of the micropores within the microporous carbon scaffold via hydrocarbon CVD.
[0530] The microporous carbon scaffold material was subjected to hydrocarbon CVD treatment substantially according to the methods described herein. Prior to hydrocarbon CVD treatment, the surface area, pore volume and density measured via pycnometry were 1744 m 2 / g, 0.72cm 3 / g and 2.24g / cm 3 After hydrocarbon CVD treatment, the surface area, pore volume and density measured by pycnometry were 6m 2 / g, 0.701cm 3 / g and 1.49g / cm 3 Without being bound by theory, a significant reduction in surface area and pore volume, along with a significant reduction in skeletal density, is consistent with capping of carbon micropores. Thus, hydrocarbon treatments or equivalent processes known in the art are suitable for decapping carbon pores, such as carbon pores loaded with silicon deposited according to the principles generally described herein. Without being bound by theory, such capping allows the internal porosity within the particle to accommodate silicon expansion while minimizing expansion of the encapsulated volume of the particle.
[0531] Embodiment 18
[0532] Effect of porous carbon scaffold particle size on silane deposition and electrochemical properties of the resulting silicon-carbon scaffolds.
[0533] For silicon deposition via silane gas as generally described herein, various pyrolytic carbons with different particle sizes and containing mixed micropores and mesopores were examined. The samples included carbons that were granular (up to and exceeding 1 mm) and particles that were size reduced using a FRITSCH Planetary Mill (FM) or a Jet Mill (JM). The data are shown in Table 13, including electrochemical testing in half cells as generally described herein.
[0534] Table 13. Silicon carbon composites according to Example 18.
[0535]
[0536] It can be seen that all the carbon support particles tested, from Dv50 greater than 1mm to those carbon support particles falling to about 4um, all can be doped with silicon via silane deposition technology. There is a significant trend to improve electrochemical performance (e.g., higher FCE and higher average CE) via reducing the carbon support particle size. Not subject to theoretical constraints, the further reduction of carbon particle size is also additionally beneficial, such as the Dv50 of 2um to 5um or the Dv50 of 2um to 3um or the Dv50 of 1um to 3um or the Dv50 of 1um to 2um. Alternatively, relative to the carbon support particles of the present invention, the Dv50 less than 1um is shown, and it is envisioned that the carbon support Dv50 will show excellent properties, and the technology for realizing this is known in the art. For example, the carbon support particle size can be 0.1um to 1um, such as 0.2 micron to 0.8 micron, such as 0.4um to 0.6um.
[0537] Embodiment 19
[0538] Silicon deposition on macroporous carbon scaffolds via silane decomposition and electrochemical properties of the resulting silicon-carbon composites.
[0539] Various macroporous carbon scaffolds were treated with silane to produce silicon carbon composites substantially as d...
Claims
1. A method for preparing silicon-carbon composite particles, the method comprising: a. Providing a porous carbon framework comprising micropores; b. heating the porous carbon framework at a high temperature in the presence of a silicon-containing gas, thereby impregnating silicon into the micropores of the porous carbon framework to provide a silicon-carbon composite; and c. performing particle size reduction of the silicon-carbon composite to provide silicon-carbon composite particles, The silicon-carbon composite particles have a diameter of 0.05 cm 3 / g to 0.5cm 3 / g of nitrogen cannot enter the volume.
2. The method of claim 1, wherein the silicon impregnated within the micropores of the porous carbon framework is nanoscale.
3. The method of claim 1, wherein the porous carbon framework comprises a pyrolyzed carbon material.
4. The method of claim 1, wherein the porous carbon framework comprises a pyrolyzed and activated carbon material.
5. The method of claim 1, wherein the particle size reduction is performed by jet milling.
6. The method of claim 5, wherein the jet milling is performed in the presence of nitrogen.
7. The method of claim 1, wherein the elevated temperature is 300°C to 900°C.
8. The method of claim 1, wherein the porous carbon framework comprises more than 0.5 cm 3 / g pore volume.
9. The method of claim 1, wherein the porous carbon framework comprises more than 500 m 2 / g of surface area.
10. The method of claim 1, wherein the porous carbon framework comprises more than 750 m 2 / g of surface area.
11. The method of claim 1, wherein the silicon-carbon composite particles contain pores, and most of the pores have a diameter of 5 nm or less. 12 . The method of claim 1 , wherein the silicon-carbon composite particles have a Dv,0 of 1 nm to 5 μm.
13. The method of claim 1, wherein the silicon-carbon composite particles have a Dv,0 greater than 5 μm.
14. The method of claim 1, wherein the silicon carbon composite particles have a Dv,100 of 8 nm to 100 μm.
15. The method of claim 1, wherein the silicon carbon composite particles have a Dv,100 greater than 100 μm.
16. The method of claim 1, wherein the silicon carbon composite particles have a silicon content of 5 wt% to 95 wt%.
17. The method of claim 1, wherein the silicon carbon composite particles have an oxygen content of less than 10 wt%.
18. The method of claim 1, wherein the porous carbon framework is heated in a fluidized bed reactor.
19. The method of claim 1, wherein the porous carbon framework further comprises mesopores.
Citation Information
Patent Citations
Carbon materials comprising an electrochemical modifier
US20110159375A1
Carbon - lead blends for use in hybrid energy storage devices
US20130004841A1
Activated carbon cryogels and related methods
US7723262B2
Manufacturing methods for the production of carbon materials
US8293818B2
Ultrapure synthetic carbon materials
US8404384B2